Gas barrier laminate
By installing Zn and phosphorus compounds in the gas barrier laminate and forming a crosslinked structure with polyamines, the problem of deterioration of barrier properties of gas barrier materials after cooking in the prior art is solved, and gas barrier properties and productivity are achieved Improve balance.
Patent Information
- Application Number
- CN202280094677.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-12
- Publication Date
- 2025-01-03
AI Technical Summary
The barrier properties of the conventional gas barrier materials deteriorate after cooking, and it is difficult to improve the productivity and barrier balance at the same time.
By setting a specific composition ratio of Zn and phosphorus compounds in the gas barrier laminate and forming a crosslinked structure with polyamines, a gas barrier layer with water resistance is formed, so as to ensure a balance of barrier properties and productivity after cooking treatment.
The gas barrier performance with excellent balance in various layer structures is achieved, which ensures good barrier performance after cooking and improves productivity.
Smart Images

Figure CN119255911A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a gas barrier laminate and related technologies. Background Art
[0002] Generally, as a gas barrier material against water vapor or oxygen, a laminated body is used in which an inorganic layer having a gas barrier property is provided on a base layer.
[0003] However, the inorganic layer cannot withstand friction and the like, and such a gas barrier laminate may have cracks generated in the inorganic layer due to friction or stretching during post-processing such as printing, lamination, or filling of contents, thereby reducing the gas barrier properties.
[0004] Therefore, as a gas barrier layer, for example, Patent Document 1 (International Publication No. 2016 / 017544) discloses a gas barrier coating material comprising a polycarboxylic acid, a polyamine compound, a polyvalent metal compound and a base, wherein (the number of moles of -COO- groups contained in the above-mentioned polycarboxylic acid) / (the number of moles of amino groups contained in the above-mentioned polyamine compound) = 100 / 20 to 100 / 90.
[0005] Patent Document 1 discloses that, by using such a gas barrier coating material, a gas barrier film and a laminate thereof having excellent gas barrier properties, particularly oxygen barrier properties, under both low humidity and high humidity conditions can be provided.
[0006] In addition, Patent Document 2 (International Publication No. 03 / 091317) discloses a film made of a polycarboxylic acid (A) and a polyvalent metal compound (B), wherein the peak ratio (A) of the infrared absorption spectrum of the film is 1560 / A 1700 ) is greater than 0.25.
[0007] Patent document 2 discloses the following: If such a film is used, a film can be obtained that has excellent gas barrier properties such as oxygen even in a high humidity atmosphere, is water-resistant (the appearance, shape and gas barrier properties will not be damaged by the influence of neutral water, high-temperature water vapor and hot water), and is easily soluble in acid and / or alkali.
[0008] In addition, Patent Document 3 (International Publication No. 2016 / 088534) discloses a gas barrier polymer formed by heating a mixture containing a polycarboxylic acid and a polyamine compound. In the infrared absorption spectrum of the gas barrier polymer, the infrared absorption spectrum of the gas barrier polymer is 1493 cm -1 Above 1780cm -1 The total peak area within the following absorption band range is defined as A and the peak area at 1598 cm -1 Above 1690cm-1 When the total peak area in the following absorption band range is defined as B, the area ratio of the amide bond represented by B / A is 0.370 or more.
[0009] Patent Document 3 discloses that such a polymer can achieve a gas barrier polymer for a gas barrier film and a gas barrier laminate that has excellent gas barrier properties under both high humidity and after boiling / retorting and has an excellent balance among appearance, dimensional stability and productivity.
[0010] Furthermore, as prior arts regarding gas barrier materials, the following Patent Documents 4 to 6 can be cited.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: International Publication No. 2016 / 017544
[0014] Patent document 2: International Publication No. 03 / 091317
[0015] Patent Document 3: International Publication No. 2016 / 088534
[0016] Patent Document 4: Japanese Patent Application Publication No. 2005-225940
[0017] Patent Document 5: Japanese Patent Application Publication No. 2013-10857
[0018] Patent Document 6: International Publication No. 2011 / 122036 Summary of the invention
[0019] Problems to be solved by the invention
[0020] The technical level required for various properties of gas barrier materials is gradually increasing.
[0021] According to the knowledge and preliminary studies of the inventors of the present application, conventional gas barrier materials such as those described in Patent Documents 1 to 3 have the following problems.
[0022] The gas barrier materials composed of a system including a polycarboxylic acid and a polyvalent metal compound as described in Patent Documents 1 or 2 have a problem in that the barrier properties deteriorate after retorting due to the two-layer laminate structure.
[0023] In addition, the gas barrier material composed of a system including a polycarboxylic acid and a polyamine compound as described in Patent Document 3 has a problem that the barrier performance deteriorates after retorting due to the three-layer laminate structure.
[0024] As described above, the inventors of the present application have found that conventional gas barrier materials such as those described in Patent Documents 1 to 3 have a problem in that the barrier performance after retorting is deteriorated due to the laminated structure.
[0025] That is, the inventors of the present application have found that conventional gas barrier materials have room for improvement from the viewpoint of barrier performance after retorting.
[0026] The present invention has been made in view of the above circumstances. One object of the present invention is to provide a barrier laminate that can be used as a barrier film having good barrier properties after retorting, for example, water vapor transmission rate in a two-layer laminate structure.
[0027] (The purpose of this invention is particularly related to the first invention described later.)
[0028] Gas barrier materials are required to further improve the barrier properties of gases such as water vapor. For example, when making retort food, a retort treatment is performed, that is, the food is packaged with a gas barrier material and then heated, and it is required to obtain good barrier properties even after the retort treatment.
[0029] One of the objects of the present invention is to provide a gas barrier material having improved barrier properties against gases such as water vapor.
[0030] (The purpose of this invention is particularly related to the second invention described later.)
[0031] According to the findings of the inventors of the present application, conventional gas barrier materials such as those described in Patent Documents 1 to 3 have a problem in that the barrier performance deteriorates after retorting, depending on the laminated structure.
[0032] One of the objects of the present invention is to provide a barrier laminate that can be used as a barrier film having good barrier properties after retorting regardless of the laminate structure.
[0033] (The purpose of this invention is particularly related to the third invention described later.)
[0034] According to the inventors of the present application, there is still room for improvement in gas barrier materials from the perspective of improving productivity and barrier properties in a well-balanced manner. Although there have been many technologies aimed at improving barrier properties, no technology has been reported to improve barrier properties and productivity in a well-balanced manner.
[0035] One of the objects of the present invention is to provide a gas barrier material having an excellent balance between productivity and barrier properties and capable of exhibiting ideal barrier properties in various layer structures.
[0036] (The purpose of this invention is particularly related to the fourth invention described later.)
[0037] The technical level required for various properties of gas barrier materials is gradually increasing. According to the inventors' understanding, gas barrier materials such as those described in Patent Documents 4 and 5 require long-term heating at high temperature in order to crosslink polycarboxylic acid and polyamine, which sometimes reduces productivity.
[0038] Furthermore, if the heat treatment time for cross-linking the polycarboxylic acid and the polyamine is shortened in order to improve the productivity of such a gas barrier material, the ratio of the amide bond formed by cross-linking the polycarboxylic acid and the polyamine decreases, and the barrier properties may be reduced.
[0039] Thus, the inventors of the present application have found that there is room for improvement in existing gas barrier materials from the perspective of improving productivity and barrier properties in a well-balanced manner. Although there have been many technologies aimed at improving barrier properties, no technology has been reported to improve barrier properties and productivity in a well-balanced manner.
[0040] One of the objects of the present invention is to provide a gas barrier material having an excellent balance between productivity and barrier properties.
[0041] (The purpose of this invention is particularly related to the fifth invention described later.)
[0042] Means for solving problems
[0043] The inventors of the present application have repeatedly conducted in-depth studies to achieve at least one of the above-mentioned problems. As a result, it was found that the barrier properties of the following laminate after steaming treatment are good, the laminate is a gas barrier layer having a gas barrier layer in which Zn is within a specific composition ratio according to, for example, X-ray photoelectron spectroscopy (XPS) analysis and the intensity ratio of a specific peak from Zn observed by time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis is within a certain range, and the laminate has a gas barrier layer in which the composition ratio of N is within a specific range according to XPS analysis and the intensity ratio of a specific peak from N observed by TOF-SIMS analysis is within a specific range. In addition, the following first invention was completed.
[0044] In addition, the inventors of the present application have completed the following second invention, third invention, fourth invention, and fifth invention.
[0045] [First Invention] 1.
[0047] A gas barrier laminate comprising a substrate layer, a gas barrier layer provided on at least one surface of the substrate layer, and an inorganic layer provided between the substrate layer and the gas barrier layer.
[0048] The composition ratio of Zn measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is 1 to 10 atomic %.
[0049] In the case where the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, 64 ZnPO4H - The mass peak intensity is set as I( 64 ZnPO4H - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - )hour,
[0050] I( 64 ZnPO4H - ) / I(C3H3O2 - ) is 6×10 -4 Above 5×10 -2 the following,
[0051] The composition ratio of N measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is greater than 0 atomic % and less than 12 atomic %,
[0052] In the case where the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, CN - The mass peak intensity is set as I(CN - )hour,
[0053] I(CN - ) / I(C3H3O2 - ) is greater than 0 and less than 2. 2.
[0055] The gas barrier laminate as described in 1., wherein the PO2 - The mass peak intensity is set as I(PO2 - ) and PO3 - The mass peak intensity is set as I(PO3 - )hour,
[0056] (I(PO2 - )+I(PO3 - )) / I(C3H3O2 - ) has a value of 0.02 or more and 5 or less. 3.
[0058] The gas barrier laminate as described in 1. or 2., wherein the I(PO2 - ) and the aforementioned I(PO3 -) intensity ratio, that is, I(PO2 - ) / I(PO3 - ) has a value of 0.05 or more and 1 or less. 4.
[0060] The gas barrier layered product according to any one of 1. to 3., wherein the gas barrier layer is composed of a cured product of a mixture containing at least a polycarboxylic acid, Zn, and a phosphorus compound containing one or more -P-OH groups or a salt thereof. 5.
[0062] The gas barrier layered product according to 4., wherein the concentration of P atoms of the phosphorus compound or its salt in the mixture is 5×10 -4 mol or more and 0.3 mol or less. 6.
[0064] The gas barrier layered product according to 4. or 5., wherein the mixture further contains a polyamine. 7.
[0066] The gas barrier layered product according to 6., wherein the polyamine is polyethyleneimine. 8.
[0068] The gas barrier layered product according to any one of 4. to 7., wherein the polycarboxylic acid comprises one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid. 9.
[0070] The gas barrier layered product according to any one of 1. to 8., wherein the gas barrier layer has a thickness of 0.05 μm or more and 10 μm or less.
[0071] [Second Invention] 1.
[0073] A gas barrier laminate comprising a substrate layer, a gas barrier layer provided on at least one surface of the substrate layer, and an inorganic layer provided between the substrate layer and the gas barrier layer.
[0074] When the gas barrier layer was subjected to time-of-flight secondary ion mass spectrometry, PO2 - The mass peak intensity is set as I(PO2 - ), PO3 - The mass peak intensity is set as I(PO3 - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 -), {I(PO2 - )+I(PO3 - )} / I(C3H3O2 - ) is 0.02 to 5,
[0075] The gas barrier layer contains one or more metal elements selected from the group consisting of Zn, Ca, Mg, Ba and Al, and the composition ratio of the metal elements in the gas barrier layer obtained by performing X-ray photoelectron spectroscopy on the gas barrier layer is 1 to 15 atomic %. 2.
[0077] The gas barrier laminate according to 1., wherein when the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, CN - The mass peak intensity is set as I(CN - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - ), I(CN - ) / I(C3H3O2 - ) value is less than 2. 3.
[0079] The gas barrier laminate according to 1. or 2., wherein in an absorption spectrum obtained by infrared spectroscopy of the gas barrier layer by total reflection measurement,
[0080] In will 1493cm -1 Above 1780cm -1 The total peak area within the following absorption band range is defined as A and the peak area at 1493 cm -1 Above 1598cm -1 When the total peak area in the following absorption band range is defined as D, the area ratio D / A is 0.5 or more. 4.
[0082] The gas barrier layered product according to any one of 1. to 3., wherein the inorganic layer is in contact with the base layer, or a primer layer is provided between the inorganic layer and the base layer. 5.
[0084] The gas barrier layered product according to any one of 1. to 4., wherein the inorganic layer contains one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide, and aluminum. 6.
[0086] The gas barrier layered product according to any one of 1. to 5., wherein the gas barrier layer has a thickness of 0.01 to 15 μm. 7.
[0088] The gas barrier layered product according to any one of 1. to 6., wherein a sealant layer is further provided on the surface of the gas barrier layer opposite to the inorganic substance layer. 8.
[0090] The gas barrier layered product according to 7., wherein the sealant layer is in contact with the gas barrier layer, or the gas barrier layer and the sealant layer are bonded to each other via an adhesive layer. 9.
[0092] The gas barrier laminate according to 7., wherein a layer containing polyamide is provided between the gas barrier layer and the sealant layer. 10.
[0094] The gas barrier layered product according to any one of 1. to 9., which is used for food packaging. 11.
[0096] The gas barrier layered product according to any one of 1. to 10., which is used for production of retort foods. 12.
[0098] A packaging bag comprising the gas barrier layered product according to any one of 1. to 11. 13.
[0100] A food packaged with the gas barrier layered product according to any one of 1. to 12.
[0101] [Third Invention] 1.
[0103] A gas barrier laminate comprising a substrate layer, a gas barrier layer provided on at least one surface of the substrate layer, and an inorganic layer provided between the substrate layer and the gas barrier layer.
[0104] The composition ratio of Zn measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is 1 to 10 atomic %.
[0105] In the case where the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, 64 ZnPO4H - The mass peak intensity is set as I( 64 ZnPO4H - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - )hour,
[0106] I( 64 ZnPO4H - ) / I(C3H3O2 - ) is 7×10 -4 Above 5×10 -2 the following. 2.
[0108] The gas barrier laminate as described in 1., wherein the PO2 - The mass peak intensity is set as I(PO2 - ) and PO3 - The mass peak intensity is set as I(PO3 - )hour,
[0109] (I(PO2 - )+I(PO3 - )) / I(C3H3O2 - ) has a value of 0.02 or more and 5 or less. 3.
[0111] The gas barrier laminate as described in 1. or 2., wherein the I(PO2 - ) and the aforementioned I(PO3 - ) intensity ratio, that is, I(PO2 - ) / I(PO3 - ) has a value of 0.05 or more and 1 or less. 4.
[0113] The gas barrier layered product according to any one of 1. to 3., wherein the gas barrier layer is composed of a cured product of a mixture containing at least a polycarboxylic acid, Zn, and a phosphorus compound containing one or more -P-OH groups or a salt thereof. 5.
[0115] The gas barrier laminate according to 4., wherein the concentration of the phosphorus compound containing one or more -P-OH groups or its salt in the mixture is 5×10 -4 mol or more and 0.3 mol or less. 6.
[0117] The gas barrier layered product according to 4. or 5., wherein the polycarboxylic acid comprises one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid. 7.
[0119] The gas barrier layered product according to any one of 1. to 6., wherein the thickness of the gas barrier layer is 0.05 μm or more and 10 μm or less.
[0120] [Fourth Invention] [1]
[0122] A gas barrier layered product comprising:
[0123] Base material layer,
[0124] a gas barrier layer provided on at least one surface of the substrate layer, and
[0125] An inorganic layer disposed between the substrate layer and the gas barrier layer;
[0126] The gas barrier layer is composed of a cured product of a mixture containing a polycarboxylic acid, a polyamine compound, a polyvalent metal compound, and a phosphorus compound containing one or more -P-OH groups or a salt thereof. [2]
[0128] The gas barrier layered product according to [1] further comprises a primer layer provided between the substrate layer and the inorganic substance layer. [3]
[0130] A gas barrier laminate as described in [1] or [2], wherein the inorganic layer is a vapor-deposited film provided on the substrate layer, or is a vapor-deposited film provided on the intermediate layer when there is an intermediate layer between the substrate layer and the inorganic layer, and the inorganic layer is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum. [4]
[0132] The gas barrier layered product according to any one of [1] to [3], wherein in the infrared absorption spectrum of the gas barrier layer,
[0133] 1300cm -1 Above 1490cm -1 The maximum peak height of absorbance in the following range is defined as α,
[0134] 1690cm -1 Above 1780cm -1 When the maximum peak height of the absorbance in the following range is γ,
[0135] The ratio of the free carboxyl group to the NH3 complex represented by γ / α is 0.00 or more and 1.00 or less. [5]
[0137] The gas barrier layered product according to any one of [1] to [4], wherein in the infrared absorption spectrum of the gas barrier layer,
[0138] 1493cm -1 Above 1780cm -1 The total peak area within the following absorption band range is set as A,
[0139] 1598cm -1 Above 1690cm -1 The total peak area within the following absorption band range is set as B,
[0140] 1690cm -1 Above 1780cm -1 The total peak area within the following absorption band range is set as C,
[0141] 1493cm -1 Above 1598cm -1 When the total peak area within the following absorption band range is set as D,
[0142] The area ratio of the amide bond represented by B / A is 0.200 or more and 0.370 or less,
[0143] The area ratio of carboxylic acid represented by C / A is 0.150 or less,
[0144] The area ratio of the carboxylate represented by D / A is 0.580 or more and 0.800 or less. [6]
[0146] The gas barrier layered product according to any one of [1] to [5], wherein the gas barrier layer has a thickness of 0.01 μm to 15 μm. [7]
[0148] The gas barrier layered product according to any one of [1] to [6], wherein the polyvalent metal compound is a compound of one or more divalent or higher metals selected from the group consisting of Zn, Ca, Mg, Ba and Al. [8]
[0150] The gas barrier layered product as described in any one of [1] to [7], wherein (the number of moles of P atoms derived from the phosphorus compound or its salt in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is 0.001 to 0.3. [9]
[0152] The gas barrier layered product according to any one of [1] to [8], wherein the phosphorus compound is one or more selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, polyphosphoric acid, phosphonic acid, and salts thereof.
[10]
[0154] The gas barrier layered product as described in any one of [1] to [9], wherein (the number of moles of the polyvalent metal derived from the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is 0.10 to 0.80.
[11]
[0156] The gas barrier layered product as described in any one of [1] to
[10] , wherein (the number of moles of the polyvalent metal derived from the polyvalent metal compound in the mixture) / (the number of moles of the amino groups derived from the polyamine compound in the mixture) is 0.25 to 0.65.
[12]
[0158] The gas barrier layered product according to any one of [1] to
[11] , wherein the polycarboxylic acid comprises one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid.
[13]
[0160] The gas barrier layered product according to any one of [1] to
[12] , wherein the polyamine compound comprises polyethyleneimine.
[14]
[0162] The gas barrier layered product according to any one of [1] to
[13] , wherein the base layer comprises one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate.
[0163] [Fifth Invention] [1]
[0165] A gas barrier layered product comprising:
[0166] Base material layer,
[0167] a gas barrier layer provided on at least one surface of the substrate layer, and
[0168] An inorganic layer disposed between the substrate layer and the gas barrier layer;
[0169] The gas barrier layer is composed of a cured product of a mixture containing a polycarboxylic acid, a polyamine compound, and a polyvalent metal compound. [2]
[0171] The gas barrier layered product according to [1] further comprises a primer layer provided between the substrate layer and the inorganic substance layer. [3]
[0173] A gas barrier laminate as described in [1] or [2], wherein the inorganic layer is a vapor-deposited film provided on the substrate layer, or is a vapor-deposited film provided on the intermediate layer when there is an intermediate layer between the substrate layer and the inorganic layer, and the inorganic layer is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum. [4]
[0175] The gas barrier layered product according to any one of [1] to [3], wherein the inorganic layer includes an aluminum oxide layer composed of aluminum oxide. [5]
[0177] The gas barrier layered product according to any one of [1] to [4], wherein in the infrared absorption spectrum of the gas barrier layer,
[0178] 1300cm -1 Above 1490cm -1 The maximum peak height of absorbance in the following range is defined as α,
[0179] 1690cm -1 Above 1780cm -1 When the maximum peak height of the absorbance in the following range is γ,
[0180] The ratio of the free carboxyl group to the NH3 complex represented by γ / α is 0.00 or more and 1.00 or less. [6]
[0182] The gas barrier layered product according to any one of [1] to [5], wherein in the infrared absorption spectrum of the gas barrier layer,
[0183] 1493cm -1 Above 1780cm -1 The total peak area within the following absorption band range is set as A,
[0184] 1598cm -1 Above 1690cm -1 The total peak area within the following absorption band range is set as B,
[0185] 1690cm -1 Above 1780cm -1 The total peak area within the following absorption band range is set as C,
[0186] 1493cm -1 Above 1598cm -1 When the total peak area within the following absorption band range is set as D,
[0187] The area ratio of the amide bond represented by B / A is 0.200 or more and 0.370 or less,
[0188] The area ratio of carboxylic acid represented by C / A is 0.150 or less,
[0189] The area ratio of the carboxylate represented by D / A is 0.580 or more and 0.800 or less. [7]
[0191] The gas barrier layered product according to any one of [1] to [6], wherein the gas barrier layer has a thickness of 0.01 μm to 15 μm. [8]
[0193] The gas barrier layered product according to any one of [1] to [7], wherein the polyvalent metal compound is a compound of one or more divalent or higher metals selected from the group consisting of Zn, Ca, Mg, Ba and Al. [9]
[0195] The gas barrier layered product as described in any one of [1] to [8], wherein (the number of moles of the polyvalent metal derived from the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is 0.10 to 0.80.
[10]
[0197] The gas barrier layered product as described in any one of [1] to [9], wherein (the number of moles of the polyvalent metal derived from the polyvalent metal compound in the mixture) / (the number of moles of the amino groups derived from the polyamine compound in the mixture) is 0.25 or more and 0.75 or less.
[11]
[0199] The gas barrier layered product according to any one of [1] to
[10] , wherein the polycarboxylic acid comprises one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid.
[12]
[0201] The gas barrier layered product according to any one of [1] to
[11] , wherein the polyamine compound comprises polyethyleneimine.
[13]
[0203] The gas barrier layered product according to any one of [1] to
[12] , wherein the substrate layer is a layer comprising one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate.
[0204] Effects of the Invention
[0205] According to the present invention, for example, a gas barrier laminate having excellent barrier properties after retorting can be provided.
[0206] According to the present invention, for example, a gas barrier material having improved gas barrier properties can be provided.
[0207] According to the present invention, for example, a gas barrier laminate having excellent barrier properties after retorting can be provided regardless of the laminate structure.
[0208] According to the present invention, for example, it is possible to provide a gas barrier material which has an excellent balance between productivity and barrier properties and can exhibit ideal barrier properties in various layer structures.
[0209] According to the present invention, for example, a gas barrier material having an excellent balance between productivity and barrier properties can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0210] [ Figure 1 ] is a cross-sectional view schematically showing an example of the structure of a double-layer laminated structure gas barrier layered product in the first embodiment.
[0211] [ Figure 2 ] is a cross-sectional view schematically showing an example of the structure of a three-layer laminated structure gas barrier layered product in the first embodiment.
[0212] [ Figure 3 ] is the triangular function Y used for data analysis of mass spectrometry in the first embodiment. j (m) Explanatory diagram (graph).
[0213] [ Figure 4 ] is a diagram (graph) showing an example of curve fitting of data of mass spectrometry analysis in the first embodiment.
[0214] [ Figure 5 ] is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the second embodiment.
[0215] [ Figure 6 ] is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the second embodiment.
[0216] [ Figure 7] is the triangular function Y used for data analysis of mass spectrometry in the second embodiment. j (m) Explanatory diagram (graph).
[0217] [ Figure 8 ] is a diagram (curve graph) showing an example of curve fitting of data of mass spectrometry analysis in the second embodiment.
[0218] [ Fig. 9 ] is a cross-sectional view schematically showing an example of the structure of a double-layer laminated structure gas barrier layered product in the third embodiment.
[0219] [ Fig.10 ] is a cross-sectional view schematically showing an example of the structure of a three-layer laminated structure gas barrier layered product in the third embodiment.
[0220] [ Fig.11 ] is the triangular function Y used for data analysis of mass spectrometry in the third embodiment. j (m) Explanatory diagram (graph).
[0221] [ Fig.12 ] is a diagram (curve graph) showing an example of curve fitting of data of mass spectrometry analysis in the third embodiment.
[0222] [ Fig.13 ] is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the fourth embodiment.
[0223] [ Fig.14 ] is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the fourth embodiment.
[0224] [ Fig.15 ] is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the fifth embodiment.
[0225] [ Fig.16 ] is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the fifth embodiment. DETAILED DESCRIPTION
[0226] Hereinafter, embodiments of the first to fifth inventions will be described with reference to the drawings.
[0227] Respectively, the embodiment of the first invention is recorded as the first embodiment, the embodiment of the second invention is recorded as the second embodiment, the embodiment of the third invention is recorded as the third embodiment, the embodiment of the fourth invention is recorded as the fourth embodiment, and the embodiment of the fifth invention is recorded as the fifth embodiment.
[0228] All drawings are schematic diagrams for explanation and do not necessarily correspond to actual dimensional ratios.
[0229] Regarding the reference numerals in the drawings, the same reference numerals may represent different elements in different embodiments. Figure 2 In the figure, reference numeral 10 indicates a "three-layer laminated structure barrier film", but on the other hand, in the figure used to explain the fourth embodiment Fig.13 In the drawings, reference numeral 10 denotes a “gas barrier film”.
[0230] Unless otherwise specified, "-" between numerical values herein means above to below.
[0231] In the description of the group (atomic group) in this specification, the description without description of substitution or unsubstituted includes both the case of not having a substituent and the case of having a substituent. For example, the so-called "alkyl" includes not only an alkyl group without a substituent (unsubstituted alkyl group) but also an alkyl group with a substituent (substituted alkyl group).
[0232] In the present specification, the expression "(meth)acrylic-" means a concept including both "acrylic-" and "methacrylic-". The same applies to similar expressions such as "(meth)acrylate".
[0233] <First Embodiment>
[0234] The gas barrier layered product according to the first embodiment is the following gas barrier layered product:
[0235] The invention comprises a substrate layer, a gas barrier layer provided on at least one surface of the substrate layer, and an inorganic layer provided between the substrate layer and the gas barrier layer.
[0236] The composition ratio of Zn measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is 1 to 10 atomic %.
[0237] In the case where the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, 64 ZnPO4H - The peak intensity is set as I( 64 ZnPO4H - ) and C3H3O2 - The peak intensity is set as I(C3H3O2 - )hour,
[0238] I( 64 ZnPO4H - ) / I(C3H3O2- ) is 6×10 -4 Above 5×10 -2 the following,
[0239] The composition ratio of N measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is greater than 0 atomic % and less than 12 atomic %,
[0240] The CN measured by time-of-flight secondary ion mass spectrometry of the gas barrier layer - The peak intensity is set as I(CN - )hour,
[0241] I(CN - ) / I(C3H3O2 - ) is greater than 0 and less than 2.
[0242] The fact that the composition ratio of Zn measured by performing X-ray photoelectron spectroscopy is 1 to 10 atomic % means that Zn is contained in the gas barrier layer at a certain concentration.
[0243] In addition, C3H3O2 was detected from the gas barrier layer by mass spectrometry. - This means that the gas barrier layer contains polyacrylic acid or its derivatives / similar compounds (polyacrylic acid, etc.). - ) is a value related to the amount (concentration) of carboxyl groups in the gas barrier layer.
[0244] Since the gas barrier layer contains Zn at a certain concentration and there is a polycarboxylic acid having a carboxyl group in the gas barrier layer stack, it is believed that the polycarboxylic acid in the gas barrier layer forms a crosslinked body with Zn, and the gas barrier layer forming the Zn crosslinked body together with the inorganic layer arranged between the substrate layer and the gas barrier layer is responsible for the gas barrier property of the gas barrier layer stack.
[0245] In addition, the gas barrier layer was detected by mass spectrometry. 64 ZnPO4H - This means that there is a bond between a phosphorus compound represented by phosphoric acid and Zn in the gas barrier layer, and it is believed that I( 64 ZnPO4H - ) is a value related to the amount (concentration) of the bond between the phosphorus compound and Zn. It is also inferred that Zn is not only bonded to the carboxyl group of the polycarboxylic acid, but also part of Zn is chemically bonded to each other via the polybasic phosphoric acid compound.
[0246] In addition, it is believed that I( 64 ZnPO4H - ) / I(C3H3O2 -) is a value related to the amount (concentration) of bonds between the phosphorus compound and Zn relative to the carboxyl group of the polycarboxylic acid.
[0247] However, zinc phosphate is known as a water-insoluble compound, and the bond between the phosphorus compound and Zn is a bond that is not easily cut by hydration caused by retorting treatment, etc. Therefore, it is believed that the presence of the bond between the phosphorus compound and Zn in the gas barrier layer suppresses the excessive expansion and contraction of the gas barrier layer due to retorting treatment, etc., which damages the adjacent inorganic layer and thus significantly reduces the gas barrier properties.
[0248] On the other hand, CN was detected from the gas barrier layer by mass spectrometry. - This means that the gas barrier layer contains polyamine. It is considered that the composition ratio of N measured by X-ray photoelectron spectroscopy is greater than 0 atomic % and less than 12 atomic % and I (CN - ) / I(C3H3O2 - ) is greater than 0 and not greater than 2, which means that a polyamine is also present in the gas barrier layer containing a polycarboxylic acid, and is a value related to the amount (concentration) of amino groups derived from the polyamine.
[0249] Since polyamines and polycarboxylic acids are present in the gas barrier layer at a certain concentration, the carboxyl group from the polycarboxylic acid will not only bond with Zn, but also bond with the amino group. In addition, amide crosslinking can be formed by the dehydration condensation reaction of the carboxyl group and the amino group. It is believed that the polycarboxylic acid forms a crosslinked body based on ionic crosslinking and amide crosslinking with good balance using Zn and polyamines, and the gas barrier layer formed by the metal crosslinked body is responsible for the gas barrier property of the gas barrier laminate together with the inorganic layer disposed between the substrate layer and the gas barrier layer.
[0250] That is, since the composition ratio of Zn is 1 to 10 atomic %, I( 64 ZnPO4H - ) / I(C3H3O2 - ) is 6×10 -4 Above 5×10 -2 Below, in addition, the composition ratio of N is greater than 0 atomic % and is 12 atomic % or less, I (CN - ) / I(C3H3O2 - ) is greater than 0 and less than 2, so the barrier properties after cooking are maintained well.
[0251] Figure 1, a schematic cross-sectional view of an example of a double-layer laminated structure barrier film including a gas barrier laminate according to the first embodiment is shown. The double-layer laminated structure barrier film 1 includes a gas barrier laminate 8. The gas barrier laminate 8 includes a substrate layer 2, a gas barrier layer 5 located on at least one surface of the substrate layer 2, and an inorganic layer 4 located between the substrate layer 2 and the gas barrier layer 5. In addition, a primer layer (UC layer) 3 may be provided below the inorganic layer 4, that is, above the substrate layer 2. With respect to the double-layer laminated structure barrier film 1, for example, the gas barrier laminate 8 may be bonded to the unstretched polypropylene (CPP) 7 via an adhesive layer 6.
[0252] in addition, Figure 2 2 is a schematic cross-sectional view of an example of a three-layer laminated structure barrier film including a gas barrier laminate according to the first embodiment. In the three-layer laminated structure barrier film 10, for example, a nylon film 9 may be bonded to the first adhesive layer 61 of the barrier laminate 8 provided with the first adhesive layer 61, and the nylon film 9 and the unstretched polypropylene 7 may be bonded via the second adhesive layer 62.
[0253] The gas barrier layer 5 of the gas barrier laminate 8 according to the first embodiment is a layer in which at least zinc (Zn) and nitrogen (N) are detected by X-ray photoelectron spectroscopy (XPS) analysis. In addition, by time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis, 64 ZnPO4H - Peak, C3H3O2 - Peak, CN - The peak.
[0254] In the gas barrier layer of the gas barrier layered product according to the first embodiment, a high water resistance 64 ZnPO4H - The peak of FIG. 1 is obtained, thereby achieving a gas barrier laminate with excellent barrier performance after steaming.
[0255] [XPS analysis]
[0256] The composition of Zn contained in the gas barrier layer is 1 atom% or more, preferably 1.5 atom% or more, and more preferably 2 atom% or more in XPS analysis. In addition, the composition of Zn contained in the gas barrier layer is 10 atom% or less, preferably 8 atom% or less, and more preferably 7 atom% or less. This corresponds to the peak intensity of Zn relative to the peak intensity of carbon, that is, Zn / C is 0.01 or more and 0.2 or less (atom / atom%).
[0257] As described above, the presence of a certain amount of Zn in the gas barrier layer improves the barrier properties after retorting.
[0258] In addition, the composition of the N contained in the gas barrier layer is greater than 0% in XPS analysis, preferably 2 atomic % or more, and more preferably 3 atomic %. In addition, the composition of the N is 12 atomic % or less, preferably 10 atomic % or less, and more preferably 9 atomic % or less. This corresponds to the peak intensity of N relative to the peak intensity of carbon, that is, N / C is 0 or more and 0.2 or less (atom / atom %).
[0259] As described above, when the composition ratio of N in the gas barrier layer is greater than 0 atomic % and is 12 atomic % or less, the barrier performance after retorting becomes good.
[0260] An example of specific conditions applicable to the XPS analysis of the first embodiment is shown below.
[0261] Analyzer: AXIS-NOVA manufactured by KRATOS
[0262] X-ray source: monochromatized Al-Kα
[0263] X-ray source output: 15kV, 10mA
[0264] Analysis area: 300×700μm
[0265] During analysis: Use a neutralizing gun for charge calibration
[0266] In the XPS analysis, a 1×1 cm measurement sample cut from the gas barrier layer can be used. In addition, in order to analyze the interior of the gas barrier layer, it is preferred to sputter-etch the surface of the gas barrier layer before analysis. In order to reduce damage to the gas barrier layer, it is desirable to use an Ar-gas cluster ion beam (Ar-GCIB) source for sputter etching. Ar-gas cluster ion beam is known as a method of etching in a manner that does not damage the chemical structure of the sample to be tested.
[0267] In XPS analysis, the detected elements are determined by scanning the wide energy spectrum, and the spectrum is obtained for each element by narrow scanning. Then, the background is calculated based on the obtained spectrum using the Shirley method and the background is removed from the spectrum. For each element measured, the spectrum without background is obtained, and the atomic composition ratio (atomic %) of the detected element is calculated based on the obtained peak area using the relative sensitivity coefficient method.
[0268] It should be noted that the detection sensitivity of the atomic composition ratio in ordinary XPS analysis is considered to be about 0.1 atomic %. For example, when a trace amount of a phosphorus compound is added to the gas barrier layer, the content of P may not be detected by XPS analysis.
[0269] [TOF-SIMS analysis]
[0270] In the TOF-SIMS analysis of the gas barrier layer, the fragments detected 64 ZnPO4H - The peak intensity is set as I( 64 ZnPO4H - ) and C3H3O2 - The peak intensity of the fragment is set as I(C3H3O2 - )hour,
[0271] I( 64 ZnPO4H - ) / I(C3H3O2 - ) is 6×10 -4 Above, preferably 7×10 -4 More preferably, 1×10 -3 In addition, 5×10 -2 Below, preferably 3×10 -2 Below, more preferably 2×10 -2 the following.
[0272] As described above, when the water-resistant bond is detected 64 ZnPO4H - The mass peak of 64 ZnPO4H - ) / I(C3H3O2 - ) is within the above range, a gas barrier laminate having good barrier properties after steaming is obtained. 64 ZnPO4H - ) / I(C3H3O2 - ) is too large, the fine particles of the zinc phosphate compound grow in the gas barrier layer, causing non-uniformity in the gas barrier layer and showing a tendency for the barrier properties after steaming to deteriorate.
[0273] In addition, CN in the fragments detected by TOF-SIMS analysis of the gas barrier layer - The mass peak intensity is set as I(CN - )hour,
[0274] I(CN - ) / I(C3H3O2 - ) is greater than 0, preferably greater than 0.2, and more preferably greater than 0.4. - ) / I(C3H3O2 - ) is 2 or less, preferably 1.8 or less, and more preferably 1.5 or less.
[0275] Such a gas barrier layer can provide a gas barrier laminate having excellent barrier performance after retorting.
[0276] An example of specific conditions applicable to the TOF-SIMS analysis of the first embodiment is shown below.
[0277] In order to analyze the inside of the gas barrier layer, it is preferred to sputter-etch the surface of the gas barrier layer using Ar-gas cluster ion beam (Ar-GCIB) attached to the TOF-SIMS analyzer before TOF-SIMS analysis. The use of Ar-GCIB can reduce damage to the gas barrier layer.
[0278] An example of specific conditions applicable to Ar-GCIB in the first embodiment is shown.
[0279] GCIB: 5kV, 5μA
[0280] GCIB processing time: the time point when the spectral pattern of TOF-SIMS no longer changes
[0281] TOF-SIMS analysis can be performed, for example, as follows.
[0282] Analyzer: PHI nano-TOFII manufactured by ULVAC-PHI
[0283] Primary ion: Bi3 2+
[0284] Primary ion source output: 30kV, 0.5μA
[0285] Analysis area: 300×300μm (scanning area of primary ion beam)
[0286] During the analysis, charge neutralization can be performed by irradiation with low-energy electron beams or low-energy Ar ions provided with the device. In addition, in the TOF-SIMS analysis, a 1×1 cm measurement sample cut out from the gas barrier layer can be used, similarly to the XPS analysis.
[0287] At this time, the PO2 observed by TOF-SIMS analysis of the gas barrier layer - The mass peak intensity is set as I(PO2 - ) and PO3 - The mass peak intensity is set as I(PO3 - )hour,
[0288] (I(PO2 - )+I(PO3 - )) / I(C3H3O2 - ) is preferably 0.02 or more, more preferably 0.05 or more, and still more preferably 0.07 or more.- )+I(PO3 - ) / I(C3H3O2 - ) is preferably 5 or less, more preferably 3 or less, and further preferably 2.5 or less.
[0289] PO2 detected - PO3 - The mass peak of means that the gas barrier layer contains a phosphorus compound containing one or more P-OH groups, represented by phosphoric acid. - )+I(PO3 - )) / I(C3H3O2 - ) is a value related to the amount (concentration) of the phosphorus compound relative to the carboxyl groups of the polycarboxylic acid in the gas barrier layer.
[0290] At this time, the above I(PO2 - ) and I(PO3 - ) intensity ratio, that is, I(PO2 - ) / I(PO3 - ) is preferably 0.05 or more, more preferably 0.08 or more, and still more preferably 0.1. - ) / I(PO3 - ) is 1 or less, preferably 0.9 or less, and more preferably 0.8 or less.
[0291] In TOF-SIMS analysis, PO2 was detected - and PO3 - The mass peak of this point refers to phosphorus compounds containing one or more P-OH groups, such as phosphoric acid (H3PO4), and its ratio, that is, I(PO2 - ) / I(PO3 - ) becomes a value reflecting the type of phosphorus-based compound.
[0292] I( 64 ZnPO4H - ) / I(C3H3O2 - ) affects the type of phosphorus compound. That is, it is also related to I(PO2 - ) / I(PO3 - ) value. The above I(PO2 - ) / I(PO3 - ) is 0.05 or more and 1 or less, which can make I( 64 ZnPO4H - ) / I(C3H3O2 -) is within an appropriate range, and the barrier performance of the gas barrier layered product after retorting of the first embodiment can be well maintained.
[0293] The analysis method of data obtained by TOF-SIMS can be performed as follows.
[0294] In order to perform detailed spectrum analysis, in the first embodiment, the mass number m is obtained by the analysis device for each of the positive and negative secondary ions. i and the corresponding count c i As a pair of raw data columns and total ion counts (TotalIon Counts, C T ). Here, i = 0, 1, 2, ..., N, and the original data sequence is for m i It should be noted that C T is the total count of secondary ions detected by the detector.
[0295] The mass number range around the mass spectrum peak of interest is set to i=n1, n1+1, ..., n2. i The data c of the count of this range obtained by analysis i Specifically, by using the background level b 0 and K triangular functions Y j (m i ) to fit the curve of c i Here, b 0 is a constant.
[0296] [Mathematical formula 1]
[0297]
[0298] Y j (m i )yes Figure 3 As shown in the mass number x 0 j When the peak value Y 0 j The function is expressed by the following formula.
[0299] [Mathematical formula 2]
[0300]
[0301] Here, b 0 、x 0 j , Y 0 j , B - j , B +j becomes the fitting parameter. In addition, regarding j, j=1, ..., K. For example, the background of the spectrum is not a constant value but varies with respect to m i In the case of linear changes, b 0 With the triangular function Y j (m i ) combination to approximate the background. When the mass spectrum peak of interest is a single peak, the background is removed and approximation is performed using one triangular function. When the mass spectrum peak of interest is close to other mass peaks, the other mass peaks are also included and approximated using multiple triangular functions. When the mass spectrum peak of interest that has been approximated is set to the j=kth peak among the K triangular functions, the peak intensity I is calculated by setting i=n1, ..., n2 to Y k (m i The total ion count (C T ) is expressed as a normalized value and is obtained by the following formula.
[0302] [Mathematical formula 3]
[0303]
[0304] If there is a tail in the mass spectrum peak, it becomes difficult to define the range of the mass number corresponding to the count. In the first embodiment, in order to avoid this, the mass spectrum peak is approximated by a triangular function. Thus, the count of the tail of the mass spectrum peak is ignored. Curve fitting is performed in a manner that the central part of the mass spectrum peak is consistent with the triangular function.
[0305] In addition, other components overlapping with the target peak component may be observed (for example, other types of mass peaks with the same mass number). In such cases, the target peak component is obtained by approximating the other components overlapping with the target peak component using a triangular function.
[0306] The mass numbers of the fragments concerned in the first embodiment are calculated in advance and shown below. The atomic mass numbers of isotopes are referred to http: / / physics.nist.gov / .
[0307] [Table 1]
[0308]
[0309] [ 64 ZnPO4H - Calculation of mass peak intensity]
[0310] It is known that Zn has five isotopes. In TOF-SIMS analysis, the main isotopes detected are 64 Zn, 66 Zn,68 In the first embodiment, the fragments with the highest abundance ratio are focused on. 64 Zn. In the expression 64 In the fragments of the bond between Zn and phosphorus compounds containing P-OH, 64 ZnPO4H - , 64 ZnP2O6H - , 64 ZnP2O7H - , 64 ZnP3O9 - etc., but focus on the mass peak with greater intensity 64 ZnPO4H - .
[0311] Focusing on the range of mass number of negative secondary ion spectrum = 159.5 to 160.3, according to the equivalent 64 Zn 31 P 16 O4 1 H - The triangular function and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as 64 ZnPO4H - The mass peak intensity.
[0312] An example of curve fitting is shown in Figure 4 The calculation results of the parameters used at this time and the total count are shown in Table 2. Figure 4 In the example shown, according to the target 64 ZnP O4 - The triangular function and m obtained by approximating the mass peak i The total number of counts obtained from the data is 1514. The total ion count of negative secondary ions (C T ) = 8571746, so 64 ZnPO4H - The mass peak intensity I( 64 ZnPO4H - )for:
[0313] I( 64 ZnPO4H - ) = 1514 / 8571746 = 1.77 × 10 -4 .
[0314] [Table 2]
[0315]
[0316] For an example showing curve fitting Figure 4 To supplement.
[0317] (i) To obtain measurement data c near the target peak position i The approximation curve y i , need "background b 0 ” and the curves of “the triangular function approximation of other components”, and “the triangular function Y j (m i )” curve.
[0318] (ii) Figure 4 In the example of i The "approximation curve y i ”, using the “background b 0 ”, “Triangular function Y as the target j (m i )" (in Table 2, j=2), and two curves of "triangular function approximation of other components" (in Table 2, j=0, 1).
[0319] [C3H3O2 - Calculation of mass peak intensity]
[0320] Focusing on the range of mass number of negative secondary ion spectrum = 70.7 to 71.4, according to the curve fitting, the equivalent 12 C3 1 H3 16 O2 - The triangular function Y is obtained by approximating the mass peak near 71.013 k (m i ) and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as C3H3O2 - The mass peak intensity I(C3H3O2 - ).
[0321] [PO2 - Calculation of mass peak intensity]
[0322] Focusing on the range of mass number of negative secondary ion spectrum = 62.5 to 63.3, according to the equivalent 31 P 16 O2 - The triangular function and m iThe data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as PO2 - The mass peak intensity I(PO2 - ).
[0323] [PO3 - Calculation of mass peak intensity]
[0324] Focusing on the range of mass number of negative secondary ion spectrum = 78.5 to 79.3, according to the equivalent 31 P 16 O3 - The triangular function and m obtained by approximating the mass peak near 78.959 i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as PO3 - The mass peak intensity I(PO3 - ).
[0325] [CN - Calculation of mass peak intensity]
[0326] Focusing on the range of mass number of negative secondary ion spectrum = 25.5 to 26.3, according to the equivalent 12 C 14 N - The triangular function and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as CN - The mass peak intensity I(CN - ).
[0327] The gas barrier layer is preferably formed of a cured product of a mixture containing a polycarboxylic acid, Zn, and a phosphorus compound containing one or more -P-OH groups, such as phosphoric acid (H3PO4), or a salt thereof.
[0328] If the gas barrier layer is formed from a cured product of a mixture containing these components, the carboxyl groups from the polycarboxylic acid form metal ion crosslinks via Zn, and Zn also reacts with the phosphorus compound containing a P-OH group to form a bond having water resistance. Although the detailed mechanism is unclear, it is believed that since these metal ion crosslinks formed via Zn and the bonds between Zn and the phosphorus compound are uniformly and appropriately present in the gas barrier layer, a dense gas barrier layer is formed, and excessive expansion and contraction of the gas barrier layer due to steaming treatment, etc. is suppressed.
[0329] The Zn composition ratio of the gas barrier layer according to the first embodiment and the I(64 ZnPO4H - ) / I(C3H3O2 - ) value, I(PO2 - )+I(PO3 - ) / I(C3H3O2 - ) value, I(PO2 - ) / I(PO3 - ) can be controlled by appropriately adjusting the manufacturing conditions of the gas barrier layer.
[0330] In the first embodiment, for example, the concentration of phosphoric acid relative to the polycarboxylic acid can be cited as a factor for controlling the Zn composition ratio and I( 64 ZnPO4H - ) / I(C3H3O2 - )’s value.
[0331] The polycarboxylic acid, zinc or its compound, phosphorus compound, and other components that can be added that can be applied to the first embodiment will be described in detail below.
[0332] (Polycarboxylic Acid)
[0333] Polycarboxylic acid is a compound having two or more carboxyl groups in the molecule. Specifically, homopolymers of α,β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, 3-hexenedioic acid, or copolymers thereof may be cited. In addition, copolymers of the above-mentioned α,β-unsaturated carboxylic acids with esters such as ethyl esters, olefins such as ethylene, etc. may also be mentioned.
[0334] Among them, homopolymers of acrylic acid and methacrylic acid or copolymers thereof are preferred, one or more polymers selected from polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid are more preferred, at least one polymer selected from polyacrylic acid and polymethacrylic acid is further preferred, and at least one polymer selected from homopolymers of acrylic acid and homopolymers of methacrylic acid is particularly preferred.
[0335] Here, in the first embodiment, the so-called polyacrylic acid includes both homopolymers of acrylic acid and copolymers of acrylic acid and other monomers. In the case of a copolymer of acrylic acid and other monomers, the polyacrylic acid contains generally 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from acrylic acid in 100% by mass of the polymer.
[0336] In the first embodiment, the polymethacrylic acid includes both homopolymers of methacrylic acid and copolymers of methacrylic acid and other monomers. In the case of copolymers of methacrylic acid and other monomers, the polymethacrylic acid contains structural units derived from methacrylic acid in an amount of usually 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more, based on 100% by mass of the polymer.
[0337] The polycarboxylic acid is a polymer obtained by polymerizing carboxylic acid monomers. The molecular weight of the polycarboxylic acid is preferably 500 to 2,500,000, more preferably 5,000 to 2,000,000, more preferably 10,000 to 1,500,000, and even more preferably 100,000 to 1,200,000 from the viewpoint of excellent balance between gas barrier properties and handling properties.
[0338] Here, the molecular weight of the polycarboxylic acid is a weight average molecular weight calculated as polyethylene oxide, and can be measured using gel permeation chromatography (GPC).
[0339] By neutralizing the polycarboxylic acid with a volatile base, the occurrence of gelation can be suppressed when the zinc and polyamines described later are mixed with the polycarboxylic acid. Therefore, in the polycarboxylic acid, from the viewpoint of preventing gelation, it is preferred to prepare a partially neutralized or completely neutralized product of the carboxyl group with a volatile base. The neutralized product can be obtained by partially or completely neutralizing the carboxyl group of the polycarboxylic acid with a volatile base (i.e., preparing a carboxylate salt partially or completely for the carboxyl group of the polycarboxylic acid). Thus, gelation can be prevented when adding polyamines and zinc.
[0340] The partially neutralized product is prepared by adding a volatile base to an aqueous solution of a polycarboxylic acid polymer, and the desired neutralization degree can be obtained by adjusting the amount ratio of the polycarboxylic acid to the volatile base. In the first embodiment, from the viewpoint of fully suppressing gelation caused by the neutralization reaction with the amino group of the polyamine, the neutralization degree of the polycarboxylic acid obtained by the volatile base is preferably 30 to 100 equivalents, and more preferably 50 to 100 equivalents.
[0341] As the volatile base, any water-soluble base can be used.
[0342] Examples of the volatile base include ammonia, morpholine, alkylamines, tertiary amines such as 2-dimethylaminoethanol, N-methylmorpholine, ethylenediamine, and triethylamine, or aqueous solutions thereof, or mixtures thereof. From the viewpoint of obtaining good gas barrier properties, aqueous ammonia solutions are preferred.
[0343] The mixture constituting the gas barrier layered product according to the first embodiment preferably further contains an ammonium carbonate salt. The ammonium carbonate salt is a substance added to make zinc described later in the form of an ammonium zinc carbonate complex to improve the solubility of zinc and to prepare a uniform solution containing zinc.
[0344] Examples of the carbonate-based ammonium salt include ammonium carbonate and ammonium hydrogen carbonate. Ammonium carbonate is preferred because it is easily volatilized and is unlikely to remain in the resulting gas barrier layer.
[0345] (Zinc)
[0346] Zinc (Zn) can form water-resistant Zn phosphate bonds with phosphorus compounds, which can be detected by TOF-SIMS analysis 64 ZnPO4H - In the case where the gas barrier layer contains a polycarboxylic acid, a salt is formed with the polycarboxylic acid. Zn is zinc or a zinc compound that can be added to the mixture forming the gas barrier layer. For example, metallic zinc, zinc oxide (ZnO), a zinc compound, etc. can be used. The amount of zinc added can be set to 0.1 mol or more and 0.5 mol or less relative to 1 mol of the carboxyl group of the polycarboxylic acid.
[0347] (Phosphorus compounds)
[0348] As described above, when the barrier layer is subjected to mass spectrometry analysis, PO2 is preferably detected. - and / or PO3 - In order to provide such a barrier layer, the mixture before curing preferably contains a phosphorus compound or a salt thereof.
[0349] The phosphorus compound or the phosphorus compound in the salt thereof contains one or more -P-OH groups in the molecular structure. The phosphorus compound may be added to the mixture in the form of a salt.
[0350] From the viewpoint of further improving the water vapor barrier property after retorting, the phosphorus compound preferably contains 2 or more -P-OH groups, and more preferably contains 3 or more -P-OH groups. In addition, from the viewpoint of productivity, the number of -P-OH groups in the phosphorus compound may be, for example, 10 or less.
[0351] Specific examples of the phosphorus compound include phosphoric acid, phosphorous acid, phosphonic acid, hypophosphorous acid, polyphosphoric acid, and derivatives thereof.
[0352] Specifically, the polyphosphoric acid has a condensed structure of two or more phosphoric acids in its molecular structure, and examples thereof include diphosphoric acid (pyrophosphoric acid), triphosphoric acid, and polyphosphoric acid in which four or more phosphoric acids are condensed.
[0353] Specific examples of derivatives include esters of the above-mentioned phosphorus compounds such as phosphorylated starch and phosphoric acid cross-linked starch; halides such as chlorides; acid anhydrides such as tetraphosphorus decoxide; and compounds having a structure in which the hydrogen atoms bonded to the phosphorus atoms are replaced by alkyl groups, such as nitrilotris(methylenephosphonic acid) and N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid).
[0354] From the viewpoint of further improving the balance between barrier properties and productivity, the phosphorus compound is one or more selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, polyphosphoric acid, phosphonic acid and salts thereof, and more preferably at least one selected from the group consisting of phosphoric acid, phosphorous acid, phosphonic acid and salts thereof.
[0355] Specific examples of the salt in the salt of the phosphorus compound include salts of monovalent metals such as sodium and potassium; and ammonium salts. From the viewpoint of barrier properties, the salt of the phosphorus compound is preferably an ammonium salt.
[0356] The concentration of P atoms of the phosphorus compound is typically 5×10 -4 mol or more, preferably 1×10 -3 mol or more, more preferably 3×10 -3 In the case of a phosphorus compound containing one P atom in the chemical formula such as phosphoric acid, the number of moles of the P atom has the same meaning as the number of moles of the phosphorus compound.
[0357] It is believed that if the phosphorus compound or the phosphorus compound derived from the salt thereof has such a concentration, a Zn bond can be reliably formed with the water-resistant phosphorus compound, thereby suppressing the excessive expansion and contraction of the gas barrier layer due to the retorting treatment, etc., thereby further improving the gas barrier property of the gas barrier layered product after the retorting treatment. The existence of the bond between the phosphorus compound and Zn is obtained by the aforementioned TOF-SIMS analysis. 64 ZnPO4H - The mass peak reflects.
[0358] (Polyamine)
[0359] The mixture constituting the gas barrier layered product according to the first embodiment preferably further contains a polyamine. The inclusion of a polyamine can improve the barrier properties of the obtained gas barrier layered product and can improve the interlayer adhesion of the obtained gas barrier layered product, thereby improving the delamination resistance.
[0360] Polyamines are polymers having two or more amino groups in the main chain, side chain or terminal. Specifically, aliphatic polyamines such as polyallylamine, polyvinylamine, polyethyleneimine, poly(propyleneimine) and the like can be cited; polyamides having amino groups on the side chains such as polylysine and polyarginine; and the like. In addition, polyamines obtained by modifying a portion of the amino groups can also be used. From the perspective of obtaining good gas barrier properties, polyethyleneimine is more preferred. The amount of polyamine added can be set to be greater than 0 mol and less than 0.9 mol relative to 1 mol of carboxyl groups contained in the above-mentioned polycarboxylic acid.
[0361] From the viewpoint of excellent balance between gas barrier properties and handling properties, the weight average molecular weight of the polyamine is preferably 50 to 2,000,000, more preferably 100 to 1,000,000, further preferably 1,500 to 500,000, further more preferably 1,500 to 100,000, further more preferably 1,500 to 50,000, further more preferably 3,500 to 20,000, further more preferably 5,000 to 15,000, particularly preferably 7,000 to 12,000.
[0362] Here, in the first embodiment, the molecular weight of the polyamine can be measured using a boiling point elevation method or a viscosity method.
[0363] (Method for producing gas barrier layer)
[0364] The gas barrier layer according to the first embodiment can be produced, for example, as follows.
[0365] First, a completely or partially neutralized solution of the carboxyl groups constituting the polycarboxylic acid is prepared.
[0366] A volatile base is added to the polycarboxylic acid to completely or partially neutralize the carboxyl groups of the polycarboxylic acid. By neutralizing the carboxyl groups of the polycarboxylic acid, gelation caused by the reaction of the carboxyl groups constituting the polycarboxylic acid with the zinc and amino groups constituting the polyamine when zinc and polyamine are added in the subsequent process can be effectively prevented, thereby obtaining a uniform intermediate of a gas barrier coating material.
[0367] Next, a zinc salt compound and a carbonate-based ammonium salt are added to the above intermediate and dissolved, and a zinc salt is formed with the -COO- group constituting the polycarboxylic acid through the generated zinc ions. At this time, the -COO- group that forms a salt with the zinc ion refers to both the carboxyl group that has not been neutralized with the base and the -COO- group that has been neutralized with the base. In the case of the -COO- group that has been neutralized with the base, the zinc ion from the above zinc is replaced and coordinated to form a zinc salt of the -COO- group. Then, phosphoric acid is added after the zinc salt is formed, thereby obtaining a coating material (mixture) for gas barrier. At this time, polyamines can be further added.
[0368] The gas barrier coating material (mixture) thus manufactured is applied to the inorganic layer described later, dried and solidified, thereby forming a gas barrier layer. The method for applying the gas barrier coating material to the substrate layer is not particularly limited, and the usual method can be used. For example, various known coating machines such as Meyer rod coater, air knife coater, direct gravure coater, gravure offset press, arc gravure coater, reverse gravure press and jet nozzle method, top feed reverse coater, bottom feed reverse coater and nozzle feed reverse coater, five-roll coater, lip coater, rod coater, rod reverse coater, die coater, etc. can be cited for coating.
[0369] The coating amount (wet thickness) of the gas barrier coating material (mixture) is preferably 0.05 μm or more, more preferably 1 μm or more, and preferably 300 μm or less, more preferably 200 μm or less, and further preferably 100 μm or less.
[0370] In addition, the average thickness of the gas barrier layer after drying and curing is preferably 0.05 μm to 10 μm, more preferably 0.08 μm to 5 μm, and further preferably 0.1 μm to 1 μm. If it is below the above upper limit, the warping of the obtained gas barrier laminate and gas barrier film can be suppressed. In addition, if it is above the above lower limit, the barrier performance of the obtained gas barrier laminate and gas barrier film can be made better.
[0371] As for drying and heat treatment, heat treatment may be performed after drying, or drying and heat treatment may be performed simultaneously.
[0372] As for the method of drying and heating treatment, there is no particular limitation as long as the purpose of the present invention can be achieved, and it can be a method that can cure the gas barrier coating material or a method that can heat the cured gas barrier coating material. For example, there can be cited methods based on convection heat transfer such as ovens and dryers; methods based on conduction heat transfer such as heating rollers; methods based on radiation heat transfer using electromagnetic waves such as infrared, far-infrared and near-infrared heaters; and methods based on internal heating such as microwaves. As a device for drying and heating treatment, from the viewpoint of manufacturing efficiency, it is preferably a device that can perform both drying and heating treatment. Specifically, from the viewpoint of being able to be used for various purposes such as drying, heating, and annealing, it is preferred to use a hot air oven, and from the viewpoint of excellent heat conduction efficiency to the film, it is preferred to use a heating roller. In addition, the methods for drying and heating treatment can also be appropriately combined. A hot air oven and a heating roller can be used together. For example, when the gas barrier coating material is dried by a hot air oven and then heated by a heating roller, the time of the heating treatment process is shortened, which is preferred from the viewpoint of manufacturing efficiency. In addition, it is preferred to perform the drying and heating treatment only using a hot air oven.
[0373] For example, it is desirable to perform the heat treatment under the following conditions: the heat treatment temperature is 80 to 250°C and the heat treatment time is 1 second to 10 minutes; preferably the heat treatment temperature is 120 to 240°C and the heat treatment time is 1 second to 1 minute; more preferably the heat treatment temperature is 170 to 230°C and the heat treatment time is 1 second to 30 seconds. Furthermore, by using a heating roller as described above, the heat treatment can be performed in a short time. It is important to adjust the heat treatment temperature and the heat treatment time according to the wet thickness of the gas barrier coating material.
[0374] In the gas barrier coating material (mixture), the zinc salt of the -COO- group constituting the polycarboxylic acid forms a metal crosslink and a water-resistant Zn phosphate bond (as reflected in the above-mentioned TOF-SIMS analysis). 64 ZnPO4H - A gas barrier layer having excellent gas barrier properties can be obtained by drying and heat treatment.
[0375] (Inorganic layer)
[0376] Examples of the inorganic substance constituting the inorganic substance layer 4 include metals, metal oxides, metal nitrides, metal fluorides, metal oxynitrides, and the like that can form a thin film having barrier properties.
[0377] As the inorganic material constituting the inorganic layer 4, for example, one or more of the simple substances, oxides, nitrides, fluorides, or oxynitrides of periodic table 6A elements such as selenium and tellurium, etc., can be cited as inorganic materials constituting the inorganic material layer 4, for example, beryllium, magnesium, calcium, strontium, barium and other periodic table 2A group elements; titanium, zirconium, ruthenium, hafnium, tantalum and other periodic table transition elements; zinc and other periodic table 2B group elements; aluminum, gallium, indium, thallium and other periodic table 3A group elements; silicon, germanium, tin and other periodic table 4A group elements; selenium, tellurium and other periodic table 6A group elements, etc.
[0378] It should be noted that, in the first embodiment, the group names of the periodic table are expressed in the old CAS format.
[0379] Among the above-mentioned inorganic substances, one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide, and aluminum are preferred, and aluminum oxide is more preferred, from the viewpoint of excellent balance between barrier properties and cost.
[0380] It should be noted that silicon oxide may contain silicon monoxide and silicon monoxide in addition to silicon dioxide.
[0381] The inorganic layer is formed by the above-mentioned inorganic substance. The inorganic layer 4 can be composed of a single inorganic layer or a plurality of inorganic layers. In addition, when the inorganic layer 4 is composed of a plurality of inorganic layers, it can be composed of the same type of inorganic layers or different types of inorganic layers.
[0382] From the viewpoint of the balance among barrier properties, adhesion, handleability, etc., the thickness of the inorganic layer 4 is usually 1 nm to 1000 nm, preferably 1 nm to 500 nm.
[0383] In the first embodiment, the thickness of the inorganic substance layer can be determined from an observation image obtained by a transmission electron microscope or a scanning electron microscope.
[0384] The method for forming the inorganic layer is not particularly limited. For example, the inorganic layer 4 can be formed on one or both sides of the substrate layer 2 by vacuum evaporation, ion plating, sputtering, chemical vapor deposition, physical vapor deposition, chemical vapor deposition (CVD), plasma CVD, sol-gel, etc. Among them, sputtering, ion plating, chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma CVD, etc., film formation under reduced pressure is ideal. Therefore, it is predicted that chemically active molecular species containing silicon such as silicon nitride and silicon oxynitride react quickly, thereby improving the smoothness of the surface of the inorganic layer 4 and reducing pores.
[0385] In order to rapidly carry out these bonding reactions, it is desirable that the inorganic atom, compound be a chemically active molecular species or atomic species.
[0386] (Base material layer)
[0387] The substrate layer 2 can be used without particular limitation as long as it is a substrate layer on which a solution of a gas barrier coating material can be applied. For example, organic materials such as thermosetting resins, thermoplastic resins, or paper, inorganic materials such as glass, pottery, ceramics, silicon oxide, silicon oxynitride, silicon nitride, concrete, aluminum, aluminum oxide, iron, copper, stainless steel, etc., and a substrate layer of a multilayer structure formed by a combination of organic materials or a combination of organic materials and inorganic materials can be cited. Among them, for example, in the case of various film uses such as packaging materials and panels, plastic films using thermosetting resins, thermoplastic resins, or organic materials such as paper are preferably used.
[0388] As the thermosetting resin, a known thermosetting resin can be used, for example, epoxy resin, unsaturated polyester resin, phenol resin, urea-melamine resin, polyurethane resin, silicone resin, polyimide, etc. can be mentioned.
[0389] As the thermoplastic resin, known thermoplastic resins can be used, for example, polyolefins (polyethylene, polypropylene, poly(4-methyl-1-pentene), poly(1-butene), etc.), polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyamides (nylon-6, nylon-66, poly(m-xylylene adipamide), etc.), polyvinyl chloride, polyimide, ethylene-vinyl acetate copolymer or its saponified product, polyvinyl alcohol, polyacrylonitrile, polycarbonate, polystyrene, ionomer, fluororesin, or mixtures thereof.
[0390] Among them, from the viewpoint of achieving good transparency, one or more resins selected from the group consisting of polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide and polybutylene terephthalate are preferred, and from the viewpoint of excellent pinhole resistance, breakage resistance and heat resistance, one or more resins selected from the group consisting of polyamide, polyethylene terephthalate and polybutylene terephthalate are preferred.
[0391] In addition, depending on the application of the gas barrier layered product 8, the base layer 2 formed of a thermoplastic resin may be a single layer or may be two or more layers.
[0392] Alternatively, the base layer may be prepared by stretching a film made of the above-mentioned thermosetting resin or thermoplastic resin in at least one direction, preferably in two directions.
[0393] As the substrate layer 2 involved in the first embodiment, from the viewpoint of excellent transparency, rigidity and heat resistance, it is preferably a biaxially stretched film formed of one or more thermoplastic resins selected from polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide and polybutylene terephthalate, and more preferably a biaxially stretched film formed of one or more thermoplastic resins selected from polyamide, polyethylene terephthalate and polybutylene terephthalate.
[0394] The surface of the base material layer 2 may be coated with polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, acrylic resin, urethane resin or the like.
[0395] Furthermore, the base material layer 2 may be subjected to a surface treatment to improve adhesion, and specifically, may be subjected to a surface activation treatment such as a corona treatment, a flame treatment, a plasma treatment, or a primer coating treatment.
[0396] From the viewpoint of obtaining good film properties, the thickness of the base material layer 2 is preferably 1 to 1000 μm, more preferably 1 to 500 μm, and even more preferably 1 to 300 μm.
[0397] The shape of the base material layer 2 is not particularly limited, and examples thereof include a sheet or film shape, a tray, a cup, a hollow body, and the like.
[0398] (Base coating)
[0399] In the gas barrier laminate 8, a primer layer 3 may be formed on the surface of the substrate layer 2 from the viewpoint of improving the adhesion between the substrate layer 2 and the inorganic layer 4. The primer layer is preferably a layer formed of an epoxy (meth)acrylate compound or a urethane (meth)acrylate compound.
[0400] The primer layer 3 is preferably a layer formed by curing at least one selected from epoxy (meth)acrylate compounds and urethane (meth)acrylate compounds.
[0401] Examples of epoxy (meth) acrylate compounds include compounds obtained by reacting epoxy compounds such as bisphenol A epoxy compounds, bisphenol F epoxy compounds, bisphenol S epoxy compounds, phenol Novolac epoxy compounds, cresol Novolac epoxy compounds, and aliphatic epoxy compounds with acrylic acid or methacrylic acid, and acid-modified epoxy (meth) acrylates obtained by reacting the above epoxy compounds with carboxylic acids or their anhydrides. These epoxy (meth) acrylate compounds are applied to the surface of the substrate layer together with a diluent containing a photopolymerization initiator and, if necessary, other photopolymerization initiators or a thermoreactive monomer, and then irradiated with ultraviolet rays to form a primer layer through a crosslinking reaction.
[0402] Examples of the urethane (meth)acrylate compound include compounds obtained by subjecting an oligomer composed of a polyol compound and a polyisocyanate compound (hereinafter also referred to as a polyurethane oligomer) to acrylate.
[0403] Polyurethane oligomers can be obtained from condensation products of polyisocyanate compounds and polyol compounds. As specific polyisocyanate compounds, examples include methylene bis (p-phenylene diisocyanate), adducts of hexamethylene diisocyanate hexanetriol, hexamethylene diisocyanate, toluene diisocyanate, adducts of toluene diisocyanate trimethylolpropane, 1,5-naphthalene diisocyanate, thiopropyl diisocyanate, ethylbenzene-2,4-diisocyanate, 2,4-toluene diisocyanate dimer, hydrogenated xylylene diisocyanate, tris (4-phenylisocyanate) thiophosphate, etc., and as specific polyol compounds, there are polyether polyols such as polyoxytetramethylene glycol, polyester polyols such as polyadipate polyols and polycarbonate polyols, copolymers of acrylates and hydroxyethyl methacrylate, etc. Examples of the monomer constituting the acrylic acid ester include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and phenyl (meth)acrylate.
[0404] These epoxy (meth)acrylate compounds and urethane (meth)acrylate compounds can be used together as needed. In addition, various known methods can be mentioned as methods for polymerizing them, and specifically, methods such as irradiation with energy rays containing ionizing rays or heating can be mentioned.
[0405] When the primer layer is formed by ultraviolet curing, it is preferred to use acetophenones, benzophenones, Michler's benzoyl benzoate, α-amyl oxime ester or thioxanthones as photopolymerization initiators, and n-butylamine, triethylamine, tri-n-butylphosphine as photosensitizers. In addition, in the first embodiment, epoxy (meth) acrylate compounds and carbamate (meth) acrylate compounds can also be used in combination.
[0406] In addition, these epoxy (meth)acrylate compounds and urethane (meth)acrylate compounds can be diluted with (meth)acrylic monomers. Examples of such (meth)acrylic monomers include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, phenyl (meth)acrylate, trimethylolpropane tri(meth)acrylate as a multifunctional monomer, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate.
[0407] Among them, when a urethane (meth)acrylate compound is used as the primer layer, the oxygen barrier property of the obtained gas barrier layered product 8 can be further improved.
[0408] The thickness of the primer layer in the first embodiment is usually 0.01 to 100 g / m 2 In the range of 0.05 to 50 g / m 2 within the range.
[0409] (Adhesive layer)
[0410] In addition, an adhesive layer 6 may be provided on the gas barrier layer 5. The adhesive layer 6 may contain a known adhesive. As the adhesive, there may be cited a laminating adhesive composed of an organic titanium resin, a polyethyleneimine resin, a carbamate resin, an epoxy resin, an acrylic resin, a polyester resin, a resin containing an oxazoline group, a modified silicone resin and an alkyl titanate, a polyester polybutadiene, or a one-component type, a two-component type polyol and a polyisocyanate, an aqueous carbamate, an ion cross-linked polymer, etc. Alternatively, an aqueous adhesive having an acrylic resin, a vinyl acetate resin, a carbamate resin, a polyester resin, etc. as the main raw material may be used.
[0411] In addition, other additives such as a curing agent and a silane coupling agent may be added to the adhesive depending on the application of the gas barrier laminate 8. When the gas barrier laminate is used for hot water treatment such as boiling, from the viewpoint of heat resistance and water resistance, a dry lamination adhesive represented by a polyurethane adhesive is preferred, and a solvent-based two-component curing polyurethane adhesive is more preferred.
[0412] The gas barrier layered product 8 according to the first embodiment has excellent gas barrier properties after retorting and can be suitably used as packaging materials, particularly packaging materials for food containing contents requiring high gas barrier properties, and various packaging materials for medical, industrial, and daily groceries purposes.
[0413] The gas barrier layered product 8 of the first embodiment can be suitably used as, for example, a vacuum heat insulating film requiring high barrier performance, a sealing film for sealing an electroluminescent element, a solar cell, or the like, and the like.
[0414] <Second Embodiment>
[0415] Figure 5 It is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product according to the second embodiment.
[0416] The gas barrier laminate 100 includes a base layer 101 , a gas barrier layer 103 provided on at least one surface of the base layer 101 , and an inorganic layer 102 provided between the base layer 101 and the gas barrier layer 103 .
[0417] When the gas barrier layer 103 was subjected to time-of-flight secondary ion mass spectrometry (TOF-SIMS), PO2 - The mass peak intensity is set as I(PO2 - ), PO3 - The mass peak intensity is set as I(PO3 - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - ), {I(PO2 - )+I(PO3 - )} / I(C3H3O2 - ) is 0.02 to 5, preferably 0.05 to 3.
[0418] In addition, the gas barrier layer 103 contains one or more metal elements selected from the group consisting of Zn, Ca, Mg, Ba and Al, and the composition ratio of the above metal elements in the gas barrier layer 103 obtained by performing X-ray photoelectron spectroscopy analysis on the gas barrier layer 103 is 1 to 15 atomic %, preferably 1.5 to 12 atomic %.
[0419] {I(PO2 - )+I(PO3 - )} / I(C3H3O2 - ) is 0.02 to 5 and the composition ratio of the metal element in the gas barrier layer 103 is 1 to 15 atomic % can be defined as follows.
[0420] PO2 was detected from the gas barrier layer 103 by mass spectrometry. - PO3 - This means that the gas barrier layer 103 contains a phosphorus compound represented by phosphoric acid. - )+I(PO3 - ) is a value related to the amount (concentration) of the phosphorus compound in the gas barrier layer 103.
[0421] In addition, C3H3O2 was detected from the gas barrier layer 103 by mass spectrometry. - This means that the gas barrier layer 103 contains polycarboxylic acid of polyacrylic acid or its derivative / similar compound (polyacrylic acid, etc.). - ) is a value related to the amount (concentration) of the carboxyl groups of the polycarboxylic acid contained in the gas barrier layer 103 .
[0422] According to the knowledge and research of the inventors of the present application, phosphorus compounds represented by phosphoric acid interact with polyvalent metals such as Zn, Ca, Mg, Ba, and Al to form phosphoric acid-polyvalent metal bonds in the gas barrier layer 103. Although the details are unknown, it is believed that the phosphoric acid-polyvalent metal bond is a bond that is not easily cut by hydration and is therefore resistant to retorting treatment and the like, and that the presence of the phosphoric acid-polyvalent metal bond allows good gas barrier properties to be obtained even after retorting treatment.
[0423] {I(PO2 - )+I(PO3 - )} / I(C3H3O2 - ) being 0.02 to 5 means that the gas barrier layer 103 contains a relatively sufficient amount of phosphorus compound based on the polycarboxylic acid or the like.
[0424] The fact that the composition ratio of the metal element in the gas barrier layer 103 is 1 to 15 atomic % means that the gas barrier layer 103 contains an appropriate amount of a polyvalent metal that cross-links with phosphoric acid or the like.
[0425] That is, the gas barrier layer 103 has {I(PO2 - )+I(PO3 - )} / I(C3H3O2 - ) is 0.02 to 5 and the composition ratio of the above-mentioned metal elements in the gas barrier layer 103 is 1 to 15 atomic %, which corresponds to the presence of a sufficient amount of phosphoric acid-polyvalent metal bonds (resistant to boiling treatment, etc.) in the gas barrier layer 103.
[0426] In addition, according to the knowledge of the inventors of the present application, it is believed that by making the gas barrier layer 103 contain any one or more metal elements of Zn, Ca, Mg, Ba and Al, a cross-linked structure such as -COO...M...OOC- that can be formed between the carboxyl group possessed by polyacrylic acid and the metal element can be introduced into the gas barrier layer 103. It is believed that by making the barrier layer 103 contain such a cross-linked structure, the barrier property is further improved.
[0427] For the sake of caution, it is explained that the “composition ratio of Zn, Ca, Mg, Ba, and Al in the gas barrier layer 103 ” means the total ratio of these metal elements when the gas barrier layer 103 contains a plurality of metal elements.
[0428] The analysis of the gas barrier layer 103 by TOF-SIMS is supplemented in advance.
[0429] In order to analyze the inside of the gas barrier layer 103, it is preferred that, before analysis, the surface layer of the gas barrier layer 103 is sputter-etched using an Ar-gas cluster ion beam (Ar-GC IB) attached to a TOF-SIMS analysis device to expose the inside of the gas barrier layer 103. The use of Ar-GC IB reduces damage to the gas barrier layer 103 caused by etching.
[0430] An example of specific conditions of Ar-GCIB etching is shown below.
[0431] GCIB output: 5kV, 5μA
[0432] GCIB processing time: the time point when the spectral pattern of TOF-SIMS no longer changes
[0433] In addition, an example of specific conditions of TOF-SIMS analysis is shown.
[0434] Analytical device: PHI NaNo TOF II manufactured by ULVAC-PHI
[0435] Primary ion: Bi3 ++
[0436] Primary ion source output: 30kV, 0.5μA
[0437] Analysis area: 300×300μm (as the scanning area of the primary ion beam)
[0438] During analysis, charge neutralization is performed by irradiation with low-energy electron beams and low-energy Ar ions attached to the device.
[0439] The analysis method of data obtained by TOF-SIMS is described in advance.
[0440] In order to perform detailed mass spectrometry analysis, it is preferred that the mass number m is obtained by an analysis device for each of the positive and negative secondary ions. i and the corresponding count c i As a pair of raw data columns and total ion counts (C T ). Here, i = 0, 1, ..., N. The original data column is for m i And in ascending order. C T is the total count of secondary ions detected by the detector.
[0441] The mass number range around the mass spectrum peak of interest is set to i=N1, N1+1, ..., N2. i The data c of the count of this range obtained by analysis i Specifically, by using the background level b 0 and K triangular functions Y j (m i ) to fit the curve of c i Make an approximation.
[0442] [Formula 4]
[0443]
[0444] In the above mathematical formula, b 0 is a constant. j (m i )yes Figure 7 As shown in the mass number x 0 j When the peak value Y 0 j The function (triangular function) is expressed by the following formula.
[0445] [Mathematical formula 5]
[0446]
[0447] Triangular function Y j (m i The half-peak width of (B - j +B + j ) / 2.
[0448] b 0 、x 0 j , Y 0 j , B - j , B + j becomes the fitting parameter. Regarding j, j=1, ..., K.
[0449] For example, the background in the spectrum is not a constant value but varies relative to m i In the case of linear changes, b 0 With the triangular function Y j (m i ) combination to approximate the background.
[0450] When the mass spectrum peak of interest is a single peak, the background is removed and approximation is performed using one triangular function. When the mass spectrum peak of interest is close to other mass peaks, the other mass peaks are also included and approximation is performed using multiple triangular functions.
[0451] When the mass spectrum peak of interest to be approximated is set as the j=kth peak in the K triangular functions, the peak intensity I is calculated by setting i=N1, ..., N2 to Y k (m i The total ion count (C T ) is expressed as a normalized value and is obtained by the following formula.
[0452] [Mathematical formula 6]
[0453]
[0454] If there is a tail in the mass spectrum peak, it becomes difficult to define the range of mass numbers corresponding to the count. Therefore, in the above text, in order to avoid this, the mass spectrum peak is approximated using a triangular function. Thus, the count of the tail of the mass spectrum peak is ignored. The curve fitting is performed in a manner that the central part of the mass spectrum peak is consistent with the triangular function.
[0455] The mass numbers of the fragments concerned in the second embodiment are calculated in advance and shown below. The atomic masses of isotopes are referenced from https: / / physics.nist.gov / .
[0456] [Table 3]
[0457]
[0458] The calculation of the mass peak intensity of the fragment concerned in the second embodiment is supplemented in advance.
[0459] (PO2 - Calculation of mass peak intensity)
[0460] Focusing on the range of mass number of negative secondary ion spectrum = 62.5 to 63.3, according to the equivalent 31 P 16 O2 - The triangular function and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as PO2 - The mass peak intensity I(PO2 - ).
[0461] An example of curve fitting is shown in Figure 8 The calculation results of the parameters and the total counts used at this time are shown in the following table. - The triangular function and m i The total number of counts obtained from the data is 436. The total ion count of negative secondary ions (C T )=6838528, therefore, PO2 - The mass peak intensity I(PO2 - ) are described below.
[0462] I(PO2 - ) = 436 / 6838528 = 5.48 × 10 -5
[0463] [Table 4]
[0464]
[0465] In advance, an example of curve fitting is shown. Figure 8 To supplement.
[0466] (i) To obtain measurement data c near the target peak position i The approximation curve y i , need "background b0 ” and the curves of “the triangular function approximation of other components”, and “the triangular function Y j (m i )” curve.
[0467] (ii) Figure 8 In the example of i The "approximation curve y i ”, using the “background b 0 ”, “Triangular function Y as the target j (m i )" (in Table 2, j=1), and the curve of "triangular function approximation of other components" (in Table 2, j=0).
[0468] (iii) The large peak near m / z 63 to 63.05 was not approximated by the triangular function because it did not overlap significantly with the target peak component.
[0469] (PO3 - Calculation of mass peak intensity)
[0470] Focusing on the range of mass number of negative secondary ion spectrum = 78.5 to 79.3, according to the equivalent 31 P 16 O3 - The triangular function and m obtained by approximating the mass peak near 78.959 i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as PO3 - The mass peak intensity I(PO3 - ).
[0471] (C3H3O2 - Calculation of mass peak intensity)
[0472] Focusing on the range of mass number of negative secondary ion spectrum = 70.7 to 71.4, according to the curve fitting, the equivalent 12 C3 1 H3 16 O2 - The triangular function Y is obtained by approximating the mass peak near 71.013 k (m i ) and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as C3H3O2 - The mass peak intensity I(C3H3O2- ).
[0473] (CN - Calculation of mass peak intensity)
[0474] Focusing on the range of mass number of negative secondary ion spectrum = 70.7 to 71.4, according to the curve fitting, the equivalent 12 C 14 N - The triangular function Y is obtained by approximating the mass peak near 26.003 k (m i ) and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as CN - The mass peak intensity I(CN - ).
[0475] The analysis of the gas barrier layer 103 by X-ray photoelectron spectroscopy is supplemented in advance.
[0476] An example of specific analysis conditions is shown below.
[0477] Analyzer: AXIS-NOVA manufactured by KRATOS
[0478] X-ray source: monochromatized Al-Kα
[0479] X-ray source output: 15kV, 10mA
[0480] Analysis area: 300×700μm
[0481] Use a neutralizing electron gun for charge correction during analysis
[0482] In order to analyze the inside of the gas barrier layer 103, it is desirable to sputter-etch the surface layer of the gas barrier layer before analysis. However, in order to reduce damage to the gas barrier layer caused by etching, etching using an Ar-gas cluster ion beam source is desirable.
[0483] The detected elements are determined by wide energy spectrum scanning, and the spectrum is obtained by narrow scanning for each element. Then, the background obtained by the Shirley method is removed from the obtained spectrum, and the atomic composition ratio (atomic %) of the detected element is calculated based on the obtained peak area using the relative sensitivity coefficient method.
[0484] In addition, the detection sensitivity of the atomic composition ratio in ordinary XPS analysis is considered to be about 0.1 atomic %. For example, when a trace amount of a phosphorus compound is added to the gas barrier layer, the content of P may not be detected by XPS analysis.
[0485] As another viewpoint, the gas barrier layer 103 preferably contains a relatively large amount of carboxylate structures (and, as a result, the amount of free carboxyl groups is small). This means that the gas barrier layer 103 contains, for example, a metal-carboxyl crosslinked structure to a certain extent. By making the gas barrier layer 103 contain a relatively large amount of carboxylate structures, the gas barrier properties can be further improved.
[0486] Specifically, in the absorption spectrum obtained by measuring the infrared spectrum of the gas barrier layer 103 by total reflection measurement, at 1493 cm -1 Above 1780cm -1 The total peak area within the following absorption band range is defined as A and the peak area at 1493 cm -1 Above 1598cm -1 When the total peak area in the following absorption band range is defined as D, the area ratio D / A is preferably 0.5 or more, more preferably 0.58 or more, and more preferably 0.6 or more. The upper limit of D / A is, for example, 0.8 or less.
[0487] According to the conventional knowledge of infrared spectroscopy and the knowledge of the inventors of the present application, the absorption of νC=O by free carboxylic acid is 1700 cm -1 Nearby, the absorption of ν(C=O) based on carboxylate is 1540-1560 cm -1 Therefore, D / A can be used as an indicator of the amount of carboxylate structures contained in the gas barrier layer 103. In addition, as described later, when the gas barrier layer 103 contains polyamine, the carbonyl group may be present in the range of 1630 to 1685 cm -1 Absorption based on ν(C═O) of an amide bond was observed nearby.
[0488] Specifically, infrared spectrum measurement can be performed as follows using total reflection measurement.
[0489] First, a measurement sample of 1 cm×3 cm is cut out from the gas barrier layer 103 .
[0490] Next, an infrared absorption spectrum of the surface of the gas barrier layer 103 is obtained by infrared total reflection measurement (ATR method).
[0491] In the infrared absorption spectrum obtained, 1493 cm -1 The measuring point at 1780cm -1 The measurement points at the positions are connected by a straight line (baseline: N), and the difference spectrum between the obtained infrared absorption spectrum and N is obtained, which is defined as the spectrum (S BN). However, when the thickness of the gas barrier layer 103 is about 0.5 μm or less, the measured infrared absorption spectrum includes the influence of the layer below the gas barrier layer.
[0492] In this case, a substrate having no gas barrier layer and consisting only of the lower layer is also prepared as a measurement sample, and an ATR-IR spectrum of the substrate surface is obtained in the same manner, and a difference spectrum from the baseline N is obtained and set as the spectrum (S SN ). At 1493cm -1 Up to 1780cm -1 When a clear absorption peak is shown in the wave number range of , a difference spectrum analysis is performed according to the following formula to obtain a spectrum (S BN ').
[0493] < Spectrum (S BN ')>=<Spectrum(S BN )>-α*< Spectrum (S SN )>
[0494] Here, α is a coefficient for eliminating the influence of the base material, and 0≤α<1.
[0495] In the obtained difference spectrum (S BN '), 1493cm -1 Up to 1780cm -1 The total peak area A is taken as the area of the spectrum in the wavenumber range of 1493 cm -1 Up to 1598cm -1 The area of the spectrum in the wavenumber range is taken as the total peak area D.
[0496] Here, as a specific example, a method for determining the coefficient α for eliminating the influence of the substrate composed of the substrate layer, the inorganic layer, etc. is supplemented for the case where the substrate layer is a polyethylene terephthalate (PET) film.
[0497] PET at 1700cm -1 There is a large absorption peak near 1493cm -1 Up to 1780cm -1 The calculation of the peak area within the wave number range of 1493 cm is affected. In order to eliminate this influence, the conventional differential spectrum analysis method is used. For example, -1 Up to 1780cm -1 The sharp absorption peak of PET that is adjacent to the wave number range of 1340 cm and does not overlap with the absorption peak of the gas barrier layer is selected. -1 The absorption peak near the reference peak is taken as the reference peak. BN '), with 1340cm -1The coefficient α is adjusted in such a way that the reference peak near 1700 cm disappears, thereby obtaining -1 The influence of the nearby PET absorption peak was eliminated from the spectrum (S BN ').
[0498] In addition, the coefficient α can also be obtained as the area ratio of the infrared absorption spectrum as described below.
[0499] The infrared absorption spectrum measured from the surface of the gas barrier layer and the infrared absorption spectrum of the substrate having no gas barrier layer and consisting only of the lower layer were analyzed by dividing the infrared absorption spectrum at 1325 cm -1 The measuring point at 1355cm -1 The measurement points at 1325 cm are connected by a straight line (baseline: M). -1 ~1355cm -1 In the wave number range, the difference spectrum between the infrared absorption spectrum obtained and the baseline M is obtained, which are set as the spectrum (S BM ), spectrum (S SM ). For the spectrum (S BM ) and spectrum (S SM ), if 1325cm -1 Above 1355cm -1 The following peak areas are respectively designated as area (A BM ), area (A SM ), the coefficient α can be calculated by the following formula.
[0500] α=A BM / A SM
[0501] For the measurement of infrared absorption spectrum (infrared total reflection measurement: ATR method), for example, an IRT-5200 device manufactured by JASCO Corporation can be used, with a PKM-GE-S (germanium) crystal installed, at an incident angle of 45 degrees, room temperature, and a resolution of 4 cm -1 , the cumulative number of times is 100 times.
[0502] Figure 6 It is a cross-sectional view schematically showing another configuration example of the gas barrier layered product.
[0503] Figure 6 The basic structure of the gas barrier laminate 110 is Figure 5 The gas barrier laminate 100 is similar to the gas barrier laminate 100 of FIG. 1 , but is different in that the base layer 101 and the inorganic layer 102 are not directly in contact with each other and further includes a primer layer 104 provided between the base layer 101 and the inorganic layer 102 .
[0504] The gas barrier layer 110 can also achieve the same effects as those of the gas barrier layer 100. In addition, in the gas barrier layer 110, by providing the primer layer 104 between the base layer 101 and the inorganic layer 102, the adhesion between the base layer 101 and the inorganic layer 102 can be further improved.
[0505] The gas barrier laminate of the second embodiment can be manufactured by using appropriate raw materials in appropriate amounts and selecting appropriate manufacturing methods and manufacturing conditions. The details will be described later, but from the perspective of the formation of a cross-linked structure, it is preferred that in addition to the type and amount of raw materials, the manufacturing conditions (temperature and time of the heating treatment described later) when forming the gas barrier layer 103 are appropriately set.
[0506] Hereinafter, the layers that may be included in the gas barrier layered product will be described in detail.
[0507] (Gas barrier layer)
[0508] The gas barrier layer 103 is composed of a cured product of a mixture containing, for example, a polycarboxylic acid such as polyacrylic acid, a polyamine compound, and a polyvalent metal compound. More specifically, the gas barrier layer 103 is a film (gas barrier film 10) composed of the cured product.
[0509] More specifically, the gas barrier layer 103 can be obtained, for example, as follows: after coating the pre-cured mixture (gas barrier coating material) on a layer such as the inorganic layer 102 arranged immediately below the gas barrier layer 103, drying and heat treating it to cure the gas barrier coating material.
[0510] The components that may be contained in the mixture before curing (gas barrier coating material) are described below. The gas barrier layered product of the second embodiment can be produced by appropriately selecting the types and amounts of these components and providing the gas barrier layer 103 .
[0511] Polycarboxylic acid
[0512] Polycarboxylic acid is a compound having two or more carboxyl groups in the molecule. Specifically, homopolymers of α,β-unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, 3-hexenedioic acid, or copolymers thereof may be cited. In addition, copolymers of the above-mentioned α,β-unsaturated carboxylic acids with esters such as ethyl esters, olefins such as ethylene, etc. may also be mentioned.
[0513] Among them, preferred are homopolymers of acrylic acid, methacrylic acid, itaconic acid, fumaric acid, crotonic acid, and cinnamic acid, or copolymers thereof; more preferred are one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid; further preferred are at least one polymer selected from polyacrylic acid and polymethacrylic acid; and even more preferred are at least one polymer selected from homopolymers of acrylic acid and homopolymers of methacrylic acid.
[0514] Here, in the second embodiment, the so-called polyacrylic acid includes both homopolymers of acrylic acid and copolymers of acrylic acid and other monomers. In the case of a copolymer of acrylic acid and other monomers, the polyacrylic acid contains generally 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from acrylic acid in 100% by mass of the polymer.
[0515] In the second embodiment, the polymethacrylic acid includes both homopolymers of methacrylic acid and copolymers of methacrylic acid and other monomers. In the case of copolymers of methacrylic acid and other monomers, the polymethacrylic acid contains structural units derived from methacrylic acid in an amount of usually 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more, based on 100% by mass of the polymer.
[0516] The polycarboxylic acid is a polymer obtained by polymerizing carboxylic acid monomers. The molecular weight of the polycarboxylic acid is preferably 500 to 2,500,000, more preferably 5,000 to 2,000,000, more preferably 10,000 to 1,500,000, and even more preferably 100,000 to 1,200,000, from the viewpoint of excellent balance between gas barrier properties and handling properties.
[0517] Here, in the second embodiment, the molecular weight of the polycarboxylic acid is a weight average molecular weight calculated as polyethylene oxide, and can be measured using gel permeation chromatography (GPC).
[0518] At least a portion of the polycarboxylic acid can be neutralized with a volatile base. By neutralizing the polycarboxylic acid with a volatile base, the occurrence of gelation can be suppressed when a polyvalent metal compound, a polyamine compound and the polycarboxylic acid are mixed. Therefore, in the polycarboxylic acid, from the viewpoint of preventing gelation, it is preferred to prepare a partially neutralized or completely neutralized product of the carboxyl group with a volatile base. The neutralized product can be obtained by partially or completely neutralizing the carboxyl group of the polycarboxylic acid with a volatile base, that is, preparing the carboxyl group of the polycarboxylic acid partially or completely into a carboxylate. Thus, gelation can be prevented when a polyamine compound or a polyvalent metal compound is added.
[0519] The partially neutralized product is prepared by adding a volatile base to an aqueous solution of a polycarboxylic acid polymer, and the desired neutralization degree can be obtained by adjusting the amount ratio of the polycarboxylic acid to the volatile base. In the second embodiment, from the viewpoint of fully suppressing gelation caused by the neutralization reaction with the amino group of the polyamine compound, the neutralization degree of the polycarboxylic acid obtained by the volatile base is preferably 70 to 300 equivalents, more preferably 90 to 250 equivalents, and further preferably 100 to 200 equivalents.
[0520] As the volatile base, any water-soluble base can be used.
[0521] Examples of the volatile base include ammonia, morpholine, alkylamines, tertiary amines such as 2-dimethylaminoethanol, N-methylmorpholine, ethylenediamine, and triethylamine, or aqueous solutions thereof, or mixtures thereof. From the viewpoint of obtaining good gas barrier properties, aqueous ammonia solutions are preferred.
[0522] Polyamine compounds
[0523] The mixture before curing preferably contains a polyamine compound. The polyamine compound can react with a polycarboxylic acid to form a crosslinked structure (amide bond), thereby further improving the gas barrier properties.
[0524] The polyamine compound is a compound having two or more amino groups in the main chain, side chain or terminal, and is preferably a polymer. Specifically, aliphatic polyamines such as polyallylamine, polyvinylamine, polyethyleneimine, poly(propyleneimine) and the like; polyamides having amino groups in the side chains such as polylysine and polyarginine; and the like can be cited. In addition, a polyamine obtained by modifying a part of the amino groups may also be used.
[0525] From the viewpoint of obtaining good gas barrier properties, the polyamine compound preferably contains polyethyleneimine, and more preferably polyethyleneimine.
[0526] From the viewpoint of excellent balance between gas barrier properties and handleability, the number average molecular weight of the polyamine compound is preferably 50 to 2,000,000, more preferably 100 to 1,000,000, further preferably 1,500 to 500,000, further more preferably 1,500 to 100,000, further more preferably 1,500 to 50,000, further more preferably 3,500 to 20,000, further more preferably 5,000 to 15,000, further more preferably 7,000 to 12,000.
[0527] The molecular weight of the polyamine compound can be measured by a boiling point elevation method or a viscosity method.
[0528] From the viewpoint of further improving the gas barrier performance after the retort treatment, (the number of moles of amino groups contained in the polyamine compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.20 or more, more preferably 0.25 or more, further preferably 0.30 or more, further more preferably 0.35 or more, and further preferably 0.40 or more.
[0529] From the same point of view, (the number of moles of amino groups contained in the polyamine compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.90 or less, more preferably 0.85 or less, further preferably 0.80 or less, further more preferably 0.75 or less, and further preferably 0.70 or less.
[0530] Although the detailed reason is unclear, it is believed that by forming a dense structure with good balance between amide crosslinking (which is formed by amino groups constituting polyamine compounds) and metal crosslinking (which is formed by polyvalent metals constituting salts of polycarboxylic acids and polyvalent metals), a gas barrier layer 103 with excellent gas barrier performance after steaming treatment and a gas barrier laminate having the same can be obtained.
[0531] Regarding the polyamine compound, when the gas barrier layer 103 was subjected to time-of-flight secondary ion mass spectrometry, CN - The peak intensity is set as I(CN - ) and C3H3O2 - The peak intensity is set as I(C3H3O2 - ), I(CN - ) / I(C3H3O2 - ) is 2 or less, preferably 1.8 or less, and more preferably 1.5 or less. - ) / I(C3H3O2 - The lower limit of the value of ) is, for example, 0, preferably 0.2, and more preferably 0.4. The details of the time-of-flight secondary ion mass spectrometry are as described above.
[0532] It is believed that CN detected by mass spectrometry - From polyamines. Therefore, it is believed that I(CN - ) / I(C3H3O2 - ) is an appropriate numerical value, which corresponds to the above-mentioned "amide crosslinking (which is formed by the amino group constituting the polyamine compound) and the metal crosslinking (which is formed by the polyvalent metal constituting the salt of the polycarboxylic acid and the polyvalent metal) form a dense structure with good balance."
[0533] ·Metal
[0534] As described above, the gas barrier layer 103 preferably contains one or more metal elements selected from the group consisting of Zn, Ca, Mg, Ba and Al. Therefore, the mixture before curing preferably contains compounds of these metals. Among them, in view of the application in the packaging of steamed food, compounds containing Mg and compounds containing Zn are preferred, and compounds containing Zn are more preferred.
[0535] Examples of the metal compound include oxides, hydroxides, halides, carbonates, phosphates, phosphites, hypophosphites, sulfates, and sulfites of the above-mentioned metals. From the viewpoint of water resistance, impurities, and the like, metal oxides or metal hydroxides are preferred.
[0536] The metal compound that can be preferably used is one or more compounds selected from the group consisting of oxides such as magnesium oxide, calcium oxide, barium oxide, zinc oxide, and magnesium hydroxide, and hydroxides such as calcium hydroxide, barium hydroxide, and zinc hydroxide. It is more preferably at least one of zinc oxide and zinc hydroxide, and even more preferably zinc oxide.
[0537] In the second embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the metal compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.1 or more, more preferably 0.13 or more, further preferably 0.15 or more, and further more preferably 0.18 or more.
[0538] From the same point of view, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.80 or less, more preferably 0.70 or less, further preferably 0.60 or less, further more preferably 0.55 or less, and further preferably 0.50 or less.
[0539] In the second embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the metal compound in the mixture) / (the number of moles of the amino group derived from the polyamine compound in the mixture) is preferably 0.25 or more, more preferably 0.35 or more, and even more preferably 0.40 or more.
[0540] From the same viewpoint, (the number of moles of the metal compound in the mixture) / (the number of moles of the amino groups derived from the polyamine compound in the mixture) is preferably 0.75 or less, more preferably 0.60 or less, and even more preferably 0.55 or less.
[0541] Phosphorus compounds or their salts
[0542] As described above, when the barrier layer 103 is subjected to mass spectrometry analysis, PO2- and / or PO3 - In order to provide such a barrier layer 103, the mixture before curing preferably contains a phosphorus compound or a salt thereof.
[0543] The phosphorus compound or the phosphorus compound in the salt thereof contains one or more -P-OH groups in the molecular structure. The phosphorus compound may be added to the mixture in the form of a salt.
[0544] From the viewpoint of further improving the water vapor barrier property after retorting, the phosphorus compound preferably contains 2 or more -P-OH groups, and more preferably contains 3 or more -P-OH groups. In addition, from the viewpoint of productivity, the number of -P-OH groups in the phosphorus compound may be, for example, 10 or less.
[0545] Specific examples of the phosphorus compound include phosphoric acid, phosphorous acid, phosphonic acid, hypophosphorous acid, polyphosphoric acid, and derivatives thereof.
[0546] Specifically, the polyphosphoric acid has a condensed structure of two or more phosphoric acids in its molecular structure, and examples thereof include diphosphoric acid (pyrophosphoric acid), triphosphoric acid, and polyphosphoric acid in which four or more phosphoric acids are condensed.
[0547] Specific examples of derivatives include esters of the above-mentioned phosphorus compounds such as phosphorylated starch and phosphoric acid cross-linked starch; halides such as chlorides; acid anhydrides such as tetraphosphorus decoxide; and compounds having a structure in which the hydrogen atoms bonded to the phosphorus atoms are replaced by alkyl groups, such as nitrilotris(methylenephosphonic acid) and N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid).
[0548] From the viewpoint of further improving the balance between barrier properties and productivity, the phosphorus compound is one or more selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, polyphosphoric acid, phosphonic acid and salts thereof, and more preferably at least one selected from the group consisting of phosphoric acid, phosphorous acid, phosphonic acid and salts thereof.
[0549] Specific examples of the salt in the salt of the phosphorus compound include salts of monovalent metals such as sodium and potassium; and ammonium salts. From the viewpoint of barrier properties, the salt of the phosphorus compound is preferably an ammonium salt.
[0550] In the second embodiment, from the viewpoint of improving barrier properties, (the number of moles of P atoms of the phosphorus compound or the phosphorus compound derived from its salt in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is preferably 0.0005 or more, more preferably 0.001 or more, further preferably 0.003 or more, and further more preferably 0.005 or more. In a phosphorus compound containing one P atom in the chemical formula such as phosphoric acid, the number of moles of P atoms and the number of moles of the phosphorus compound have the same meaning.
[0551] In addition, from the viewpoint of barrier properties and productivity (stability of the coating solution, uniformity / appearance of the coating film), (the number of moles of the phosphorus compound or the phosphorus compound derived from its salt in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is preferably 0.3 or less, more preferably 0.1 or less, further preferably 0.08 or less, and further more preferably 0.05 or less.
[0552] Other ingredients
[0553] The mixture before curing may contain components other than the above components.
[0554] For example, the mixture preferably further comprises carbonate ammonium salt. Carbonate ammonium salt is a substance added to make the polyvalent metal compound into a state of carbonate polyvalent metal ammonium complex, thereby improving the solubility of the polyvalent metal compound and preparing a uniform solution containing the polyvalent metal compound. By making the mixture before solidification contain carbonate ammonium salt, the dissolution amount of the polyvalent metal compound can be increased, and as a result, the mixture with the polyvalent metal compound can be made more uniform.
[0555] Examples of the carbonate-based ammonium salt include ammonium carbonate and ammonium hydrogen carbonate. Ammonium carbonate is preferred because it is easily volatilized and is unlikely to remain in the obtained gas barrier layer.
[0556] From the viewpoint of further improving the solubility of the polyvalent metal compound, (the number of moles of the carbonate-based ammonium salt in the mixture) / (the number of moles of the metal compound in the mixture) is preferably greater than 0.05, more preferably greater than 0.10, further preferably greater than 0.25, further more preferably greater than 0.50, and particularly preferably greater than 0.75.
[0557] In addition, from the viewpoint of further improving the coating properties of the gas barrier coating material, (the number of moles of the carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of the metal compound in the gas barrier coating material) is preferably 10.0 or less, more preferably 5.0 or less, further preferably 2.0 or less, and further more preferably 1.5 or less.
[0558] Furthermore, from the viewpoint of suppressing the generation of depressions when the mixture is applied as a gas barrier coating material, the mixture before curing preferably further contains a surfactant.
[0559] When the solid content of the mixture as a whole is 100% by mass, the amount of the surfactant added is preferably 0.01 to 3% by mass, and more preferably 0.01 to 1% by mass.
[0560] Examples of the surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. From the viewpoint of obtaining good coating properties, nonionic surfactants are preferred, and polyoxyethylene alkyl ethers are more preferred.
[0561] Examples of the nonionic surfactant include polyoxyalkylene alkyl aryl ethers, polyoxyalkylene alkyl ethers, polyoxyalkylene fatty acid esters, sorbitan fatty acid esters, silicone-based surfactants, acetylene alcohol-based surfactants, and fluorine-containing surfactants.
[0562] Examples of the polyoxyalkylene alkyl aryl ethers include polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene dodecylphenyl ether, and the like.
[0563] Examples of the polyoxyalkylene alkyl ethers include polyoxyethylene alkyl ethers such as polyoxyethylene oleyl ether and polyoxyethylene lauryl ether.
[0564] Examples of the polyoxyalkylene fatty acid esters include polyoxyethylene oleate, polyoxyethylene laurate, polyoxyethylene distearate, and the like.
[0565] Examples of the sorbitan fatty acid esters include sorbitan laurate, sorbitan monostearate, sorbitan monooleate, sorbitan sesquioleate, polyoxyethylene monooleate, and polyoxyethylene stearate.
[0566] Examples of the silicone-based surfactant include dimethylpolysiloxane and the like.
[0567] Examples of the acetylene alcohol surfactant include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,6-dimethyl-4-octyne-3,6-diol, and 3,5-dimethyl-1-hexyne-3-ol.
[0568] Examples of the fluorine-containing surfactant include fluoroalkyl esters and the like.
[0569] The mixture before curing may contain additives other than the above-mentioned components, for example, various additives such as lubricants, slip agents, anti-caking agents, antistatic agents, anti-fogging agents, pigments, dyes, inorganic or organic fillers, etc.
[0570] In order to improve coating properties when the mixture is applied as a gas barrier coating material, the solid content concentration of the mixture before curing is preferably 0.5 to 15% by mass, more preferably 1 to 10% by mass.
[0571] ·Method for producing gas barrier layer
[0572] Specifically, the gas barrier layer 103 can be produced by applying a pre-cured mixture (gas barrier coating material) and curing the mixture.
[0573] The mixture can be obtained as follows.
[0574] First, a volatile base is appropriately added to a polycarboxylic acid to completely or partially neutralize the carboxyl groups of the polycarboxylic acid. A polyvalent metal salt compound and an appropriate carbonate-based ammonium salt are further mixed to form a metal salt in all or part of the carboxyl groups of the polycarboxylic acid neutralized with the volatile base and in the carboxyl groups of the polycarboxylic acid not neutralized with the volatile base.
[0575] Then, a polyamine compound is further added, and finally a phosphorus compound or a salt thereof is added to obtain a mixture before curing. Thus, a salt is formed between the phosphorus compound and the amino group of the polyvalent metal compound or the polyamine.
[0576] Since the polycarboxylic acid, the polyvalent metal salt compound, the phosphorus compound or its salt, the appropriate carbonate-based ammonium salt and the polyamine compound are mixed in such a step, the formation of agglomerates can be suppressed and a more uniform mixture can be obtained. Thus, the dehydration condensation reaction between the -COO- group contained in the polycarboxylic acid and the amino group contained in the polyamine compound can be carried out more effectively.
[0577] The details are as follows: Hereinafter, the case where a volatile base and a carbonate-based ammonium salt are added to the mixture will be described as an example.
[0578] First, a completely or partially neutralized solution of the carboxyl groups constituting the polycarboxylic acid is prepared.
[0579] A volatile base is added to the polycarboxylic acid to completely or partially neutralize the carboxyl groups of the polycarboxylic acid. By neutralizing the carboxyl groups of the polycarboxylic acid, gelation caused by the reaction of the carboxyl groups constituting the polycarboxylic acid with the amino groups constituting the polyvalent metal compound and the polyamine compound when a polyvalent metal compound or a polyamine compound is added can be effectively prevented, thereby obtaining a more uniform mixture.
[0580] Next, a polyvalent metal salt compound and a carbonate ammonium salt are added and dissolved, and the generated polyvalent metal ions form a polyvalent metal salt with the -COO- group constituting the polycarboxylic acid. At this time, the -COO- group that forms a salt with the polyvalent metal ion refers to both the carboxyl group that has not been neutralized with the base and the -COO- group that has been neutralized with the base. In the case of the -COO- group that has been neutralized with the base, the polyvalent metal ions from the above-mentioned polyvalent metal compound are replaced and coordinated to form a polyvalent metal salt of the -COO- group.
[0581] Then, after the polyvalent metal salt is formed, a polyamine compound and a phosphorus compound or a salt thereof are further added to obtain a mixture. At this time, the polyvalent metal salt coordinated to the -COO- group also coordinates with the -PO- group in the phosphorus compound to form a -COO-polyvalent metal-OP- structure. In addition, an ionic bond is formed between the -NH2 group in the polyamine and the -PO- group in the phosphorus compound.
[0582] The mixture thus produced is applied as a gas barrier coating material to the inorganic layer 102 or to an intervening layer formed on the inorganic layer 102 and between the gas barrier layer 103 and the inorganic layer 102, and dried and cured to form the gas barrier layer 103. At this time, the polyvalent metal of the polyvalent metal salt constituting the -COO- group of the polycarboxylic acid forms a metal crosslink, the amino group constituting the polyamine forms an amide crosslink, and the -PO- group in the phosphorus compound and the amino group in the polyvalent metal or the polyamine form an ionic crosslink, so that the gas barrier layer 103 having excellent gas barrier properties can be obtained. A more detailed method for producing the gas barrier layer 103 will be described later.
[0583] From the viewpoint of improving the barrier properties, the thickness of the gas barrier layer 103 after drying and curing is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more.
[0584] From the viewpoint of reducing the thickness of the entire gas barrier laminate, the thickness of the gas barrier layer 103 after drying and curing is preferably 15 μm or less, more preferably 5 μm or less, and even more preferably 1 μm or less.
[0585] (Base material layer)
[0586] The substrate layer 101 may be a single layer or may be two or more layers. The shape of the substrate layer 101 is not limited, and examples thereof include a sheet or film shape, a tray, a cup, a hollow body, and the like.
[0587] As the material of the substrate layer 101, any material can be used without limitation as long as it can stably form the inorganic layer 102 on the substrate layer 101 and can coat the solution of the gas barrier coating material on the upper part of the inorganic layer 102. As the material of the substrate layer 101, for example, resins such as thermosetting resins and thermoplastic resins, organic materials such as paper; inorganic materials such as glass, pottery, ceramics, silicon oxide, silicon oxynitride, silicon nitride, concrete, aluminum, aluminum oxide, iron, copper, stainless steel and other metals; a substrate layer of a multilayer structure formed by a combination of organic materials or a combination of organic materials and inorganic materials, etc. Among them, for example, in the case of various film applications such as packaging materials and panels, it is preferred to use a plastic film of at least one selected from the group consisting of thermosetting resins and thermoplastic resins, or an organic material such as paper.
[0588] As the thermosetting resin, a known thermosetting resin can be used, for example, epoxy resin, unsaturated polyester resin, phenol resin, urea-melamine resin, polyurethane resin, silicone resin, polyimide, etc. can be mentioned.
[0589] As the thermoplastic resin, known thermoplastic resins can be used, for example, polyolefins (polyethylene, polypropylene, poly(4-methyl-1-pentene), poly(1-butene), etc.), polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyamides (nylon-6, nylon-66, poly(m-xylylene adipamide), etc.), polyvinyl chloride, polyimide, ethylene-vinyl acetate copolymer or its saponified product, polyvinyl alcohol, polyacrylonitrile, polycarbonate, polystyrene, ionomer, fluororesin, or mixtures thereof.
[0590] Among them, from the viewpoint of improving transparency, one or more resins selected from the group consisting of polypropylene, polyethylene terephthalate (PET), polyethylene naphthalate, polyamide, polyimide, and polybutylene terephthalate are preferred.
[0591] In addition, from the viewpoint of excellent pinhole resistance, breakage resistance, heat resistance, etc., one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate are preferred. From the same viewpoint, the base layer 101 is preferably a layer containing one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate, and more preferably a layer containing one or more resins therein.
[0592] In addition, when a hygroscopic material such as polyamide is used in the substrate layer 101, in the gas barrier layer stack, the substrate layer 101 absorbs moisture and swells, and the gas barrier performance under high humidity, the gas barrier performance after boiling treatment, and the gas barrier performance when filled with acidic contents are easily reduced. However, in the second embodiment, even when a hygroscopic material is used as the substrate layer 101, the reduction in the gas barrier performance of the gas barrier layer stack under high humidity and the gas barrier performance after boiling treatment can be appropriately suppressed.
[0593] Alternatively, the base layer 101 may be formed by stretching a film made of a thermosetting resin or a thermoplastic resin in at least one direction, preferably in two directions.
[0594] From the viewpoint of excellent transparency, rigidity and heat resistance, the substrate layer 101 is preferably a biaxially stretched film formed from one or more thermoplastic resins selected from the group consisting of polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide and polybutylene terephthalate, and is more preferably a biaxially stretched film formed from one or more thermoplastic resins selected from the group consisting of polyamide, polyethylene terephthalate and polybutylene terephthalate.
[0595] In addition, the surface of the base layer 101 may be coated with polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, acrylic resin, urethane resin, or the like.
[0596] In addition, the substrate layer 101 may be a substrate layer subjected to surface treatment in order to improve adhesion with the gas barrier layer 103. Specifically, the surface of the substrate layer 101 facing the gas barrier layer 103 may be subjected to surface activation treatment such as corona treatment, flame treatment, plasma treatment, or primer coating treatment.
[0597] From the viewpoint of obtaining good film properties, the thickness of the substrate layer 101 is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and is preferably 1000 μm or less, more preferably 500 μm or less, further preferably 300 μm or less.
[0598] (Base coating)
[0599] like Figure 6 As described in , a primer layer 104 may be provided between the substrate layer 101 and the inorganic layer 102. By providing the primer layer 104, the adhesion between them can be further improved, and the barrier property after the retort treatment can be further improved.
[0600] From the viewpoint of improving adhesion between the base layer 101 and the inorganic layer 102 , examples of the material of the primer layer 104 include one or more selected from the group consisting of polyurethane resins, polyester resins, oxazoline resins, and (meth)acrylic resins.
[0601] As polyurethane resins, various polyurethane resins, polyurethane polyurea resins and prepolymers thereof can be exemplified. As specific examples of such urethane resins, reaction products of diisocyanate components such as toluene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate and diol components such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexanedimethanol, bisphenol, polyester diol, polyether diol, polycarbonate diol, polyethylene glycol and the like; reaction products of urethane prepolymers having an isocyanate group at the end and amino compounds, aminosulfonates, polyhydroxycarboxylic acids, acidic sulfurous acids and the like can be cited; and the like.
[0602] In addition, from the viewpoint of improving the barrier properties after the retorting treatment and the adhesion between the substrate layer 101 and the inorganic layer 102, it is also preferred that the polyurethane resin in the primer layer 104 is composed of a polyurethane resin having an aromatic ring structure in the main chain. The polyurethane resin having an aromatic ring structure in the main chain can be obtained as a water-dispersible polyurethane resin by, for example, reacting a polyol, an organic polyisocyanate, and a chain extender. In this way, an aromatic ring structure can be introduced into the main chain of the polyurethane resin.
[0603] As the polyurethane resin having an aromatic ring structure in the main chain, more specifically, the polyurethane resin described in JP-A-2018-171827 can be used.
[0604] For polyurethane resins such as water-dispersible polyurethane resins, a crosslinking agent may be used in combination for the purpose of improving heat resistance, water resistance, hydrolysis resistance, etc. The crosslinking agent may be an external crosslinking agent that is a different component from the polyurethane resin, or an internal crosslinking agent that preliminarily introduces reaction points that can form a crosslinked structure into the molecular structure of the polyurethane resin.
[0605] As a crosslinking agent, a compound having an isocyanate group, an oxazoline group, a carbodiimide group, an epoxy group, a melamine resin, and a silanol group can be suitably used, and a compound having a carbodiimide group is more suitable. In addition, when a compound having a carbodiimide group is used as a crosslinking agent, the amount of the compound having a carbodiimide group added is preferably 0.1 to 3.0 mol, more preferably 0.2 to 2.0 mol, and particularly preferably 0.3 to 1.0 mol for carboxyl groups in the polyurethane resin.
[0606] Various polyester resins and their modified products can be exemplified as the polyester resin used in the primer layer 104. Specific examples of such polyester resins include reaction products of polycarboxylic acid components such as terephthalic acid, phthalic acid, isophthalic acid, trimellitic acid, pyromellitic acid, 2-sulfoisophthalic acid, 5-sulfoisophthalic acid, adipic acid, sebacic acid, succinic acid, and dodecanedioic acid with diol components such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexanedimethanol, and bisphenol, as well as modified products based on acrylic resins, epoxy resins, and the like.
[0607] When an oxazoline resin is used for the primer layer 104 , the primer layer 104 is preferably composed of an oxazoline-based resin composition containing an aqueous polymer having an oxazoline group, an aqueous (meth)acrylic resin, and an aqueous polyester resin.
[0608] The oxazoline resin composition comprises, for example, an aqueous polymer containing an oxazoline group having an oxazoline group content of 6.0 to 9.0 mmol / g, an aqueous (meth)acrylic resin having a carboxyl group content of 0.5 to 3.5 mmol / g, and an aqueous polyester resin having a carboxyl group content of 0.5 to 2.0 mmol / g.
[0609] In addition, taking the total amount of the aqueous polymer containing an oxazoline group, the aqueous (meth) acrylic resin and the aqueous polyester resin as 100 mass%, the oxazoline-based resin composition contains, for example, 10 to 55 mass% of an aqueous polymer containing an oxazoline group, 10 to 80 mass% of an aqueous (meth) acrylic resin, and 10 to 80 mass% of an aqueous polyester resin.
[0610] In the oxazoline resin composition, for example, the ratio of the number of moles of oxazoline groups to the number of moles of carboxyl groups [expressed by the ratio of the number of moles of oxazoline groups (xmmol) to the number of moles of carboxyl groups (ymmol) (x / y)×100 [mol%]] is 150 to 420 mol%.
[0611] As the oxazoline resin used in the primer layer 104 , more specifically, the oxazoline resin described in International Publication No. 2016 / 186074 can be used.
[0612] From the viewpoint of obtaining good adhesion, the thickness of the primer layer 104 is preferably 0.001 μm or more, more preferably 0.005 μm or more, further preferably 0.01 μm or more, further more preferably 0.05 μm or more, further preferably 0.1 μm or more, and further preferably 0.2 μm or more.
[0613] From an economical point of view, the thickness of the primer layer 104 is preferably 1.0 μm or less, more preferably 0.6 μm or less, further preferably 0.5 μm or less, further more preferably 0.1 μm, and further preferably 0.05 μm or less.
[0614] (Inorganic layer)
[0615] Examples of the inorganic material constituting the inorganic material layer 102 include metals, metal oxides, metal nitrides, metal fluorides, and metal oxynitrides that can form a thin film having barrier properties.
[0616] As the inorganic material constituting the inorganic layer 102, for example, one or more of the simple substances, oxides, nitrides, fluorides, or oxynitrides of periodic table 6A elements such as selenium and tellurium, etc., can be cited as inorganic materials, for example, beryllium, magnesium, calcium, strontium, barium and other periodic table 2A elements; titanium, zirconium, ruthenium, hafnium, tantalum and other periodic table transition elements; zinc and other periodic table 2B elements; aluminum, gallium, indium, thallium and other periodic table 3A elements; silicon, germanium, tin and other periodic table 4A elements; selenium, tellurium and other periodic table 6A elements, etc., etc. (the group names of the periodic table are expressed in the old CAS form).
[0617] Among the above-mentioned inorganic substances, one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum are preferred, and aluminum oxide is more preferred, from the viewpoint of excellent balance between barrier properties and cost.
[0618] It should be noted that silicon oxide may contain silicon monoxide and silicon monoxide in addition to silicon dioxide.
[0619] The inorganic layer 102 is formed of the above-mentioned inorganic substance. From the viewpoint of excellent balance between barrier properties and cost, the inorganic layer 102 preferably includes an aluminum oxide layer composed of aluminum oxide.
[0620] The inorganic layer 102 may be composed of a single inorganic layer or a plurality of inorganic layers. In addition, when the inorganic layer 102 is composed of a plurality of inorganic layers, they may be composed of the same type or different types of inorganic layers.
[0621] From the viewpoint of a balance between improved barrier properties and improved handleability, the thickness of the inorganic layer 102 is usually 1 nm or more, preferably 4 nm or more, and is usually 1000 nm or less, preferably 500 nm or less.
[0622] Here, the thickness of the inorganic substance layer 102 can be determined, for example, from an observation image obtained by a transmission electron microscope or a scanning electron microscope.
[0623] The method for forming the inorganic layer 102 is not limited. For example, the inorganic layer 102 can be formed on one or both sides of the substrate layer 101 by vacuum evaporation, ion plating, sputtering, chemical vapor deposition, physical vapor deposition, chemical vapor deposition (CVD), plasma CVD, sol-gel, etc. Among them, film formation under reduced pressure by sputtering, ion plating, chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma CVD, etc. is ideal. Therefore, it is predicted that chemically active molecular species containing silicon such as silicon nitride and silicon oxynitride react quickly, thereby improving the smoothness of the surface of the inorganic layer 102 and reducing pores. In order to quickly carry out these bonding reactions, it is ideal that the inorganic atoms and compounds are chemically active molecular species or atomic species.
[0624] Furthermore, from the viewpoint of improving the balance between the barrier properties and productivity of the gas barrier laminate, the inorganic substance layer 102 is preferably a vapor-deposited film.
[0625] From the perspective of improving the balance between the barrier properties and productivity of the gas barrier laminate, the inorganic layer 102 is a vapor-deposited film arranged on the substrate layer 101, or is a vapor-deposited film arranged on the intermediate layer when there is an intermediate layer between the substrate layer 101 and the inorganic layer 102, and is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum.
[0626] (Sealing agent layer)
[0627] From a practical viewpoint such as production of retort foods, it is preferred that a sealant layer be provided on the surface of the gas barrier layer 103 opposite to the inorganic substance layer 102 .
[0628] The sealant layer is in contact with the gas barrier layer 103, or the gas barrier layer 103 and the sealant layer are bonded to each other via an adhesive layer. The adhesive layer will be described later.
[0629] Examples of the sealant layer include: a layer formed from a resin composition containing one or more polyolefins selected from homopolymers or copolymers of α-olefins such as ethylene, propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc., polyethylene such as high-density polyethylene, medium-density polyethylene, linear low-density polyethylene, low-density polyethylene, homopolypropylene, random copolymers of propylene and α-olefins having 2 or more carbon atoms and 4 to 10, low-crystalline or amorphous ethylene·propylene random copolymers, etc.; a layer formed from a resin composition containing ethylene·vinyl acetate copolymer (EVA); a layer formed from a resin composition containing EVA and a polyolefin; and the like.
[0630] Among them, from the viewpoint of heat sealability, it is preferred to contain one or more thermoplastic resins selected from low-density polyethylene, linear low-density polyethylene, homopolypropylene, and random copolymers of propylene and an α-olefin having 2 or 4 to 10 carbon atoms.
[0631] The form of the thermoplastic resin is preferably unstretched or stretched low-density polyethylene, linear low-density polyethylene (stretched LLDPE), a random copolymer of propylene and an α-olefin having 2 or 4 to 10 carbon atoms, or the like.
[0632] From the viewpoint of application in the production of retort foods, the sealant layer preferably contains an unstretched polypropylene polymer. Examples of the polypropylene polymer include homopolymers of propylene and random copolymers of propylene and an α-olefin having 2 or 4 to 10 carbon atoms.
[0633] The sealant layer may contain components other than the thermoplastic resin, for example, additives such as anti-fogging agents and anti-blocking agents, and adhesive resins such as urethane resins, urea resins, melamine resins, epoxy resins, and alkyd resins.
[0634] The sealant layer may be provided as an adhesive, and may be provided by drying and curing an adhesive containing an adhesive resin such as an acrylic resin, a urethane resin, a urea resin, a melamine resin, an epoxy resin, or an alkyd resin.
[0635] The thickness of the sealant layer is preferably 10 to 100 μm, more preferably 15 to 80 μm, and even more preferably 20 to 60 μm. By setting the thickness to this range, sufficient heat sealing properties can be obtained and the handling properties of the film can be improved.
[0636] (Adhesive layer)
[0637] The gas barrier layered product may further include an adhesive layer. Specifically, the gas barrier layer 103 and the above-mentioned sealant layer may be bonded together via the adhesive layer.
[0638] The adhesive layer may contain a known adhesive. As the adhesive, there may be mentioned a laminated adhesive composed of an organic titanium resin, a polyethyleneimine resin, a carbamate resin, an epoxy resin, an acrylic resin, a polyester resin, a resin containing an oxazoline group, a modified silicone resin, an alkyl titanate, a polyester polybutadiene, or a one-component or two-component polyol and polyisocyanate, an aqueous carbamate, an ionomer, etc. Alternatively, an aqueous adhesive having an acrylic resin, a vinyl acetate resin, a carbamate resin, a polyester resin, etc. as the main raw material may be used.
[0639] In addition, other additives such as a curing agent and a silane coupling agent may be added to the adhesive depending on the application of the gas barrier laminate. When the gas barrier laminate is used for hot water treatment such as boiling, from the viewpoint of heat resistance and water resistance, a dry lamination adhesive represented by a polyurethane adhesive is preferred, and a solvent-based two-component curing polyurethane adhesive is more preferred.
[0640] (Polyamide-containing layer)
[0641] A layer containing polyamide (e.g., a nylon layer) may or may not be provided between the gas barrier layer 103 and the sealant layer. By providing a layer containing polyamide, the strength of the film itself can be increased. For example, the bag is less likely to break when the package falls.
[0642] The layer containing polyamide may contain, for example, one or more of nylon-6, nylon-66, poly(meta-xylylene adipamide), and the like.
[0643] When a layer containing polyamide is provided, the thickness thereof is preferably 8 to 100 μm, more preferably 10 to 50 μm, and particularly preferably 13 to 30 μm.
[0644] (Method for producing gas barrier laminate)
[0645] In the second embodiment, the manufacturing method of the gas barrier stack 100 may include the following steps: a step of preparing a substrate layer 101; a step of forming an inorganic layer 102 on the substrate layer 101; and a step of forming a gas barrier layer 103 on the upper part of the substrate layer 101 on which the inorganic layer 102 is formed.
[0646] After the step of forming the inorganic layer 102 and before the step of forming the gas barrier layer 103 , a step of forming the primer layer 104 on the inorganic layer 102 may be further included.
[0647] The step of forming the inorganic layer 102 on the base layer 101 is the same as described above as the method for forming the inorganic layer 102 .
[0648] The process of forming the gas barrier layer 103 includes, for example, the following steps: applying the pre-cured mixture as a gas barrier coating material to the inorganic layer 102, followed by drying, thereby obtaining a coating layer; and heating the above-mentioned coating layer to allow the carboxyl groups contained in the polycarboxylic acid and the amino groups contained in the polyamine compound to undergo a dehydration condensation reaction, thereby forming a gas barrier layer 103 having an amide bond.
[0649] The method for applying the gas barrier coating material to the inorganic layer 102 is not limited, and a known method can be used. For example, a method of applying the gas barrier coating material using a Meyer rod coater, an air knife coater, a direct gravure coater, a gravure offset printer, a curved gravure coater, a reverse gravure printer, and a gravure coater such as a jet nozzle method, a reverse roll coater such as a top feed reverse coater, a bottom feed reverse coater, and a nozzle feed reverse coater, a five-roll coater, a lip coater, a rod coater, a rod reverse coater, a die coater, and the like can be cited.
[0650] From the viewpoint of improving the barrier performance of the obtained gas barrier layered product, the coating amount (wet thickness) is preferably 0.05 μm, more preferably 1 μm or more.
[0651] In addition, from the viewpoint of suppressing warping of the obtained gas barrier layered product and more effectively carrying out the dehydration condensation reaction between the -COO- group contained in the polycarboxylic acid and the amino group contained in the polyamine compound, the wet thickness is preferably 300 μm or less, more preferably 200 μm or less, and further preferably 100 μm or less.
[0652] As for drying and heat treatment, heat treatment may be performed after drying, or drying and heat treatment may be performed simultaneously.
[0653] As for the method of drying and heating treatment, there is no limitation as long as the effect of the present invention can be obtained, and any method that can cure the gas barrier coating material or heat the cured gas barrier coating material can be used. For example, there can be cited methods based on convection heat transfer such as ovens and dryers; methods based on conduction heat transfer such as heating rollers; methods based on radiation heat transfer using electromagnetic waves such as infrared, far-infrared and near-infrared heaters; and methods based on internal heating such as microwaves. As a device for drying and heating treatment, from the viewpoint of manufacturing efficiency, it is preferred to use a device that can perform both drying and heating treatment. Specifically, from the viewpoint of being able to be used for various purposes such as drying, heating, and annealing, it is preferred to use a hot air oven, and from the viewpoint of excellent heat conduction efficiency to the film, it is preferred to use a heating roller. In addition, the methods for drying and heating treatment can also be appropriately combined. Specifically, a hot air oven and a heating roller can be used together. For example, when the gas barrier coating material is dried by a hot air oven and then heated by a heating roller, the time of the heating treatment process is shortened, which is preferred from the viewpoint of manufacturing efficiency. In addition, it is preferred to perform the drying and heating treatment only using a hot air oven.
[0654] Regarding the heating treatment conditions, for example, the heating treatment temperature is 80 to 250° C., and the heating treatment time is 1 second to 10 minutes; preferably, the heating treatment temperature is 120 to 240° C., and the heating treatment time is 1 second to 1 minute; more preferably, the heating treatment temperature is 170 to 230° C., and the heating treatment time is 1 second to 30 seconds; and further preferably, the heating treatment temperature is 200 to 220° C., and the heating treatment time is 1 second to 10 seconds. Furthermore, by using a heating roller in combination as described above, the heating treatment can be performed in a short time.
[0655] It should be noted that, from the viewpoint of effectively forming a cross-linked structure (for example, the formation of an amide bond between a -COO- group contained in a polycarboxylic acid and an amino group contained in a polyamine compound), it is important to adjust the heat treatment temperature and the heat treatment time according to the wet thickness of the gas barrier coating material. By selecting an appropriate heat treatment temperature and heat treatment time, an appropriate cross-linked structure can be formed.
[0656] By drying and heat treating the gas barrier coating material, the carboxyl groups of the polycarboxylic acid react with the polyamine and the polyvalent metal compound to form covalent bonds and / or ion crosslinks, thereby forming a gas barrier layer 103 having good gas barrier properties even after steaming treatment.
[0657] (Specific example of layer structure)
[0658] In the second embodiment, a specific example of a laminate structure including a gas barrier layered product is shown below.
[0659] (Laminate Structure Example 1) Base material layer 101 (PET base material) / inorganic material layer 102 (aluminum oxide vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyolefin layer
[0660] (Laminate Structure Example 2) Base material layer 101 (PET base material) / primer layer 104 / inorganic material layer 102 (aluminum oxide vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyolefin layer
[0661] (Laminate structure example 3) Base material layer 101 (PET base material) / inorganic material layer 102 (alumina vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyamide layer / adhesive layer / polyolefin layer
[0662] (Laminate structure example 4) Base material layer 101 (PET base material) / primer layer 104 / inorganic material layer 102 (aluminum oxide vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyamide layer / adhesive layer / polyolefin layer
[0663] Here, by including a polyolefin layer composed of polyolefins such as polyethylene, polypropylene, poly(4-methyl-1-pentene), and poly(1-butene) in the laminate structure, the pinhole resistance, breakage resistance, and heat resistance of the gas barrier laminate can be improved, and the reduction in gas barrier performance under high humidity and after boiling treatment can be further suppressed.
[0664] (use)
[0665] The gas barrier layered product of the second embodiment has excellent gas barrier properties and can be suitably used as various packaging materials such as packaging materials, especially food packaging materials for contents requiring high gas barrier properties, for medical purposes, industrial purposes, and daily groceries. The gas barrier layered product of the second embodiment is particularly preferably used for food packaging purposes, and more preferably used for the production of retorted foods.
[0666] The gas barrier layered product according to the second embodiment can also be suitably used as a vacuum heat insulating film requiring high barrier performance, a sealing film for sealing an electroluminescent element, a solar cell, or the like, and the like.
[0667] (Packaging bag composed of gas barrier layered product, and food packaged using gas barrier layered product)
[0668] The gas barrier layered product described above can be used to form a packaging bag. The packaging bag is preferably used, for example, in the production of retort foods. That is, food (retort foods) packaged with the gas barrier layered product can be produced.
[0669] In the gas barrier layered product constituting the packaging bag, the side where the base layer is present is usually the outer surface side, and the side where the gas barrier layer is present is usually the inner surface side. If a sealant layer is present, the side where the sealant layer is present is usually the inner surface side.
[0670] The method for producing steamed food can adopt the common method in this field. The food that has been heat-sealed in the packaging bag can be sterilized by moist heat with pressurized hot water or steam at 100°C or above (for example, at 130°C for about 30 minutes), thereby producing food that can be stored at room temperature for a long time.
[0671] <Third Embodiment>
[0672] The gas barrier layered product according to the third embodiment is the following gas barrier layered product:
[0673] The invention comprises a substrate layer, a gas barrier layer provided on at least one surface of the substrate layer, and an inorganic layer provided between the substrate layer and the gas barrier layer.
[0674] The composition ratio of Zn measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is 1 to 10 atomic %.
[0675] In the case where the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, 64 ZnPO4H - The mass peak intensity is set as I( 64 ZnPO4H - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - )hour,
[0676] I( 64 ZnPO4H - ) / I(C3H3O2 - ) is 7×10 -4 Above 5×10 -2 the following.
[0677] The fact that the composition ratio of Zn measured by X-ray photoelectron spectroscopy is 1 to 10 atomic % means that Zn is contained in the gas barrier layer at a certain concentration.
[0678] In addition, C3H3O2 was detected from the gas barrier layer by mass spectrometry. - This means that the gas barrier layer contains polyacrylic acid or its derivatives / similar compounds (polyacrylic acid, etc.). - ) is a value related to the amount (concentration) of the carboxyl group of the polycarboxylic acid contained in the gas barrier layer.
[0679] Since the gas barrier layer contains Zn at a certain concentration and there is a polycarboxylic acid having a carboxyl group in the gas barrier layer, it is believed that the polycarboxylic acid in the gas barrier layer forms a crosslinked body with Zn, and the gas barrier layer forming the Zn crosslinked body together with the inorganic layer arranged between the substrate layer and the gas barrier layer is responsible for the gas barrier property of the gas barrier laminate.
[0680] In addition, the gas barrier layer was detected by mass spectrometry. 64 ZnPO4H - This means that there is a bond between a phosphorus compound represented by phosphoric acid and Zn in the gas barrier layer, and it is believed that I( 64 ZnPO4H - ) is a value related to the amount (concentration) of the bond between the phosphorus compound and Zn. It is also inferred that Zn is not only bonded to the carboxyl group of the polyvalent carboxylic acid, but also part of Zn is chemically bonded to each other via the polyvalent phosphorus compound.
[0681] In addition, it is believed that I( 64 ZnPO4H - ) / I(C3H3O2 - ) is a value related to the amount (concentration) of the bond between phosphoric acid and Zn relative to the carboxyl group of the polycarboxylic acid.
[0682] However, zinc phosphate is known as a water-insoluble compound, and the bond between the phosphorus compound and Zn is not easily cut by water (which is one of the reasons for the reduction of barrier properties after retorting). Therefore, it is believed that the presence of the bond between the phosphorus compound and Zn in the gas barrier layer suppresses the excessive swelling and shrinkage of the gas barrier layer due to retorting, etc., which damages the adjacent inorganic layer and thus greatly reduces the gas barrier properties.
[0683] That is, since the composition ratio of Zn is 1 to 10 atomic %, I( 64 ZnPO4H-) / I(C3H3O2 - ) is 7×10 -4 Above 5×10 -2 Therefore, the barrier properties after retorting can be well maintained.
[0684] Fig. 9 , a schematic cross-sectional view of an example of a double-layer laminated structure barrier film including a gas barrier laminate according to the third embodiment is shown. The double-layer laminated structure barrier film 1 includes a gas barrier laminate 8. The gas barrier laminate 8 includes a substrate layer 2, a gas barrier layer 5 located on at least one surface of the substrate layer 2, and an inorganic layer 4 located between the substrate layer 2 and the gas barrier layer 5. In addition, a primer layer (UC layer) 3 may be provided below the inorganic layer 4, that is, above the substrate layer 2. With respect to the double-layer laminated structure barrier film 1, for example, the gas barrier laminate 8 may be bonded to the unstretched polypropylene (CPP) 7 via an adhesive layer 6.
[0685] in addition, Fig.10 2 is a schematic cross-sectional view of an example of a three-layer laminated structure barrier film including a gas barrier laminate according to the third embodiment. In the three-layer laminated structure barrier film 10, for example, a nylon film 9 may be bonded to the first adhesive layer 61 of the barrier laminate 8 provided with the first adhesive layer 61, and the nylon film 9 and the unstretched polypropylene 7 may be bonded via the second adhesive layer 62.
[0686] The gas barrier layer 5 of the gas barrier laminate 8 according to the third embodiment is a layer in which at least zinc (Zn) is detected by X-ray photoelectron spectroscopy (XPS) analysis. In addition, by time-of-flight secondary ion mass spectrometry (TOF-SIMS) analysis, at least zinc (Zn) is detected. 64 Peaks of ZnPO4H-, C3H3O2- The peak.
[0687] In the gas barrier layer of the gas barrier layered product according to the third embodiment, a high water resistance 64 The peak of ZnPO4H- is thus obtained, and the barrier performance after retorting is excellent regardless of the laminate structure.
[0688] [XPS analysis]
[0689] The composition of Zn contained in the gas barrier layer is 1 atom% or more, preferably 2 atom% or more, and more preferably 3 atom% or more in XPS analysis. In addition, the composition of Zn contained in the gas barrier layer is 10 atom% or less, preferably 9.5 atom% or less, and more preferably 9 atom% or less. This corresponds to the peak intensity of Zn relative to the peak intensity of carbon, that is, Zn / C is 0.01 or more and 0.2 or less (atom / atom%).
[0690] As described above, the presence of a certain amount of Zn in the gas barrier layer improves the barrier properties after retorting.
[0691] An example of specific conditions applicable to the XPS analysis of the third embodiment is shown below.
[0692] Analyzer: AXIS-NOVA manufactured by KRATOS
[0693] X-ray source: monochromatized Al-Kα
[0694] X-ray source output: 15kV, 10mA
[0695] Analysis area: 300×700μm
[0696] During analysis: Use a neutralizing gun for charge calibration
[0697] In XPS analysis, a 1×1 cm measurement sample cut from the gas barrier layer can be used. In addition, in order to analyze the interior of the gas barrier layer, it is preferred to sputter-etch the surface of the gas barrier layer before analysis. In order to reduce damage to the gas barrier layer, it is desirable to use an Ar-gas cluster ion beam (Ar-GCIB) source for sputter etching. Ar-gas cluster ion beam etching is known as a method that can etch in a manner that does not damage the chemical structure of the sample to be tested.
[0698] In XPS analysis, the detected elements are determined by scanning the wide energy spectrum, and the spectrum is obtained for each element by narrow scanning. Then, the background is calculated based on the obtained spectrum using the Shirley method and the background is removed from the spectrum. For each element measured, the spectrum without background is obtained, and the atomic composition ratio (atomic %) of the detected element is calculated based on the obtained peak area using the relative sensitivity coefficient method.
[0699] It should be noted that the detection sensitivity of the atomic composition ratio in ordinary XPS analysis is considered to be about 0.1 atomic %. For example, when a trace amount of a phosphorus compound is added to the gas barrier layer, the content of P may not be detected by XPS analysis.
[0700] [TOF-SIMS analysis]
[0701] In the TOF-SIMS analysis of the gas barrier layer, the fragments detected 64 The peak intensity of ZnPO4H- is set as I( 64 ZnPO4H-) and C3H3O2 - The peak intensity of the fragment is set as I(C3H3O2 - )hour,
[0702] I( 64 ZnPO4H - ) / I(C3H3O2 - ) is 7×10 -4 Above, preferably 1×10 -3 More preferably, 2×10 -3 In addition, 5×10 -2 Below, preferably 3×10 -2 Below, more preferably 2×10 -2 the following.
[0703] As described above, when the fragments from the bonds with high water resistance are detected, 64 ZnPO4H - The mass peak of 64 ZnPO4H - ) / I(C3H3O2 - ) is within the above range, a gas barrier laminate having good barrier properties after steaming is obtained regardless of the laminate structure. 64 ZnPO4H-) / I(C3H3O2 - ) is too large, zinc phosphate bonded particles grow in the gas barrier layer, causing non-uniformity in the gas barrier layer and tending to deteriorate the gas barrier performance.
[0704] An example of specific conditions applicable to the TOF-SIMS analysis of the third embodiment is shown below.
[0705] In order to analyze the inside of the gas barrier layer, it is preferred to sputter-etch the surface of the gas barrier layer using Ar-gas cluster ion beam (Ar-GCIB) attached to the TOF-SIMS analyzer before TOF-SIMS analysis. The use of Ar-GCIB can reduce damage to the gas barrier layer.
[0706] An example of specific conditions applicable to Ar-GCIB of the third embodiment is shown.
[0707] GCIB: 5kV, 5μA
[0708] GCIB processing time: the time point when the spectral pattern of TOF-SIMS no longer changes
[0709] TOF-SIMS analysis can be performed, for example, as follows.
[0710] Analyzer: PHI nano-TOFII manufactured by ULVAC-PHI
[0711] Primary ion: Bi3 2+
[0712] Primary ion source output: 30kV, 0.5μA
[0713] Analysis area: 300×300μm (scanning area of primary ion beam)
[0714] During the analysis, charge neutralization can be performed by irradiation with low-energy electron beams or low-energy Ar ions provided with the device. In addition, in the TOF-SIMS analysis, a 1×1 cm measurement sample cut out from the gas barrier layer can be used, similarly to the XPS analysis.
[0715] At this time, the PO2 observed by TOF-SIMS analysis of the gas barrier layer - The mass peak intensity is set as I(PO2 - ) and PO3 - The mass peak intensity is set as I(PO3 - )hour,
[0716] I(PO2 - )+I(PO3 - ) / I(C3H3O2 - ) is preferably 0.02 or more, more preferably 0.07 or more, and still more preferably 0.1 or more. - )+I(PO3 -) / I(C3H3O2 - ) is preferably 5 or less, more preferably 4 or less, and further preferably 3 or less.
[0717] PO2 detected - PO3 - The mass peak of means that the gas barrier layer contains a phosphorus compound containing one or more P-OH groups, represented by phosphoric acid. - )+I(PO3 - ) / I(C3H3O2 - ) is a value related to the amount (concentration) of the phosphorus compound relative to the carboxyl group of the polycarboxylic acid in the gas barrier layer.
[0718] At this time, the above I(PO2 - ) and I(PO3 - ) intensity ratio, that is, I(PO2 - ) / I(PO3 - ) is preferably 0.05 or more, more preferably 0.08 or more, and still more preferably 0.1. - ) / I(PO3 - ) is 1 or less, preferably 0.9 or less, and more preferably 0.8 or less.
[0719] In TOF-SIMS analysis, PO2 was detected - and PO3 - The mass peak of this point refers to the inclusion of phosphorus compounds such as phosphoric acid (H3PO4), and its ratio, that is, I(PO2 - ) / I(PO3 - ) becomes a value reflecting the type of phosphorus compound containing a P-OH group.
[0720] I( 64 ZnPO4H - ) / I(C3H3O2 - ) affects the type of phosphorus compound. That is, it is also related to I(PO2 - ) / I(PO3 - ) value. The above I(PO2 - ) / I(PO3 - ) is 0.05 or more and 1 or less, which can make I( 64 ZnPO4H - ) / I(C3H3O2 - ) is within an appropriate range, and the barrier performance of the gas barrier layered product after retorting of the third embodiment can be well maintained.
[0721] The analysis method of the data obtained by TOF-SIMS analysis can be performed as follows.
[0722] In order to perform detailed spectrum analysis, in the third embodiment, the mass number m is obtained by using an analysis device for each of the positive and negative secondary ions. i and the corresponding count c i As a pair of raw data columns and total ion counts (C T ). Here, i = 0, 1, 2, ..., N, and the original data sequence is for m i It should be noted that C T is the total count of secondary ions detected by the detector.
[0723] The mass number range around the mass spectrum peak of interest is set to i=n1, n1+1, ..., n2. i The data c of the count of this range obtained by analysis i Specifically, by using the background level b 0 and K triangular functions Y j (m i ) to fit the curve of c i Here, b 0 is a constant.
[0724] [Formula 7]
[0725]
[0726] Y j (m i )yes Fig.11 As shown in the mass number x 0 j When the peak value Y 0 j The function is expressed by the following formula.
[0727] [Mathematical formula 8]
[0728]
[0729] Here, b 0 、x 0 j , Y 0 j , B - j , B + j becomes the fitting parameter. In addition, regarding j, j=1, ..., K. For example, the background of the spectrum is not a constant value but varies with respect to m iIn the case of linear changes, b 0 With the triangular function Y j (m i ) combination to approximate the background. When the mass spectrum peak of interest is a single peak, the background is removed and approximation is performed using one triangular function. When the mass spectrum peak of interest is close to other mass peaks, the other mass peaks are also included and approximated using multiple triangular functions. When the mass spectrum peak of interest that has been approximated is set to the j=kth peak among the K triangular functions, the peak intensity I is calculated by setting i=n1, ..., n2 to Y k (m i The total ion count (C T ) is expressed as a normalized value and is obtained by the following formula.
[0730] [Mathematical formula 9]
[0731]
[0732] If there is a tail in the mass spectrum peak, it becomes difficult to define the range of the mass number corresponding to the count. In the third embodiment, in order to avoid this, the mass spectrum peak is approximated by a triangular function. Thus, the count of the tail of the mass spectrum peak is ignored. Curve fitting is performed in a manner that the central part of the mass spectrum peak is consistent with the triangular function.
[0733] In addition, other components overlapping with the target peak component may be observed (for example, other types of mass peaks with the same mass number). In such cases, the target peak component is obtained by approximating the other components overlapping with the target peak component using a triangular function.
[0734] The mass numbers of the fragments concerned in the third embodiment are calculated in advance and shown below. The atomic mass numbers of isotopes are referred to http: / / physics.nist.gov / .
[0735] [Table 5]
[0736]
[0737] [ 64 ZnPO4H - Calculation of mass peak intensity]
[0738] It is known that Zn has five isotopes. In TOF-SIMS analysis, the main isotopes detected are 64 Zn, 66 Zn, 68 In the third embodiment, the fragments with the highest abundance ratio are focused on. 64 Zn. In the expression 64In the fragments of the bond between Zn and phosphorus compounds containing P-OH, 64 ZnPO4H - , 64 ZnP2O6H - , 64 ZnP2O7H - , 64 ZnP3O9H - etc., but focus on the mass peak with greater intensity 64 ZnPO4H - .
[0739] Focusing on the range of mass number of negative secondary ion spectrum = 159.5 to 160.3, according to the equivalent 64 Zn 31 P 16 O4 1 H - The triangular function and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as 64 ZnPO4H - The mass peak intensity I( 64 ZnPO4H - ).
[0740] An example of curve fitting is shown in Fig.12 The calculation results of the parameters used at this time and the total count are shown in Table 6. Fig.12 In the example shown, according to the target 64 ZnPO4H - The triangular function and m obtained by approximating the mass peak i The total number of counts obtained from the data is 1514. The total ion count of negative secondary ions (C T ) = 8571746, so 64 ZnPO4H - The peak intensity I( 64 ZnPO4H - )for:
[0741] I( 64 ZnPO4H - ) = 1514 / 8571746 = 1.77 × 10 -4 .
[0742] [Table 6]
[0743]
[0744] For an example showing curve fitting Fig.12 To supplement.
[0745] (i) To obtain measurement data c near the target peak position i The approximation curve y i , need "background b 0 ” and the curves of “the triangular function approximation of other components”, and “the triangular function Y j (m i )” curve.
[0746] (ii) Fig.12 In the example of i The "approximation curve y i ”, using the “background b 0 ”, “Triangular function Y as the target j (m i )" (in Table 2, j=2), and two curves of "triangular function approximation of other components" (in Table 6, j=0, 1).
[0747] [C3H3O2 - Calculation of mass peak intensity]
[0748] Focusing on the range of mass number of negative secondary ion spectrum = 70.7 to 71.4, according to the curve fitting, the equivalent 12 C3 1 H3 16 O2 - The triangular function Y is obtained by approximating the mass peak near 71.013 k (m i ) and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as C3H3O2 - The mass peak intensity I(C3H3O2 - ).
[0749] [PO2 - Calculation of mass peak intensity]
[0750] Focusing on the range of mass number of negative secondary ion spectrum = 62.5 to 63.3, according to the equivalent 31 P 16 O2 - The triangular function and m i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as PO2- The mass peak intensity I(PO2 - ).
[0751] [PO3 - Calculation of mass peak intensity]
[0752] Focusing on the range of mass number of negative secondary ion spectrum = 78.5 to 79.3, according to the equivalent 31 P 16 O3 - The triangular function and m obtained by approximating the mass peak near 78.959 i The data is used to calculate the sum of the counts, using C T Normalize and use the resulting value as PO3 - The mass peak intensity I(PO3 - ).
[0753] The gas barrier layer is preferably formed of a cured product of a mixture containing a polycarboxylic acid, Zn, and a phosphorus compound containing one or more P-OH groups, such as phosphoric acid (H 3 PO 4 ), or a salt thereof.
[0754] If the gas barrier layer is formed of a cured product of a mixture containing these components, the carboxyl groups from the polycarboxylic acid form metal ion crosslinks via Zn, and Zn also reacts with the phosphorus compound containing a P-OH group to form a bond having water resistance. Although the detailed mechanism is unclear, it is believed that since these metal ion crosslinks formed via Zn and the bonds between Zn and the phosphorus compound are uniformly and appropriately present in the gas barrier layer, a dense gas barrier layer is formed, and excessive swelling and shrinkage of the gas barrier layer due to steaming treatment, etc. is suppressed.
[0755] The composition ratio of Zn in the gas barrier layer according to the third embodiment and the I( 64 ZnPO4H - ) / I(C3H3O2 - ) value, I(PO2 - )+I(PO3 - ) / I(C3H3O2 - ) value, I(PO2 - ) / I(PO3 - ) can be controlled by appropriately adjusting the manufacturing conditions of the gas barrier layer.
[0756] In the third embodiment, for example, the concentration of phosphoric acid relative to the polycarboxylic acid can be cited as a factor for controlling the Zn composition ratio and I ( 64 ZnPO4H - ) / I(C3H3O2 -)’s value.
[0757] The polycarboxylic acid, zinc or its compound, phosphorus compound, and other components that can be added that can be applied to the third embodiment will be described in detail below.
[0758] (Polycarboxylic Acid)
[0759] Polycarboxylic acid is a compound having two or more carboxyl groups in the molecule. Specifically, homopolymers of α,β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, 3-hexenedioic acid, or copolymers thereof may be cited. In addition, copolymers of the above-mentioned α,β-unsaturated carboxylic acids with esters such as ethyl esters, olefins such as ethylene, etc. may also be mentioned.
[0760] Among them, homopolymers of acrylic acid and methacrylic acid or copolymers thereof are preferred, one or more polymers selected from polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid are more preferred, at least one polymer selected from polyacrylic acid and polymethacrylic acid is further preferred, and at least one polymer selected from homopolymers of acrylic acid and homopolymers of methacrylic acid is particularly preferred.
[0761] Here, in the third embodiment, the so-called polyacrylic acid includes both homopolymers of acrylic acid and copolymers of acrylic acid and other monomers. In the case of copolymers of acrylic acid and other monomers, the polyacrylic acid contains generally 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from acrylic acid in 100% by mass of the polymer.
[0762] In the third embodiment, the polymethacrylic acid includes both homopolymers of methacrylic acid and copolymers of methacrylic acid and other monomers. In the case of copolymers of methacrylic acid and other monomers, the polymethacrylic acid contains structural units derived from methacrylic acid in an amount of usually 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more, based on 100% by mass of the polymer.
[0763] The polycarboxylic acid is a polymer obtained by polymerizing carboxylic acid monomers. The molecular weight of the polycarboxylic acid is preferably 500 to 2,500,000, more preferably 5,000 to 2,000,000, more preferably 10,000 to 1,500,000, and even more preferably 100,000 to 1,200,000 from the viewpoint of excellent balance between gas barrier properties and handling properties.
[0764] Here, the molecular weight of the polycarboxylic acid is a weight average molecular weight calculated as polyethylene oxide, and can be measured using gel permeation chromatography (GPC).
[0765] By neutralizing the polycarboxylic acid with a volatile base, the occurrence of gelation can be suppressed when zinc described later is mixed with the polycarboxylic acid. Therefore, in the polycarboxylic acid, from the viewpoint of preventing gelation, it is preferred to prepare a partially neutralized or completely neutralized product of the carboxyl group with a volatile base. The neutralized product can be obtained by partially or completely neutralizing the carboxyl group of the polycarboxylic acid with a volatile base (that is, preparing a carboxyl group of the polycarboxylic acid partially or completely into a carboxylate). Thus, gelation can be prevented when zinc is added.
[0766] The partially neutralized product is prepared by adding a volatile base to an aqueous solution of a polycarboxylic acid polymer, and the desired degree of neutralization can be obtained by adjusting the ratio of the amount of the polycarboxylic acid to the volatile base. In the third embodiment, the degree of neutralization of the polycarboxylic acid obtained by the volatile base is preferably 30 to 100 equivalent %, more preferably 50 to 100 equivalent %.
[0767] As the volatile base, any water-soluble base can be used.
[0768] Examples of the volatile base include ammonia, morpholine, alkylamines, tertiary amines such as 2-dimethylaminoethanol, N-methylmorpholine, ethylenediamine, and triethylamine, or aqueous solutions thereof, or mixtures thereof. From the viewpoint of obtaining good gas barrier properties, aqueous ammonia solutions are preferred.
[0769] The mixture constituting the gas barrier layered product according to the third embodiment preferably further contains an ammonium carbonate salt. The ammonium carbonate salt is a substance added to make zinc described later in the form of a zinc ammonium carbonate complex to improve the solubility of zinc and to prepare a uniform solution containing zinc.
[0770] Examples of the carbonate-based ammonium salt include ammonium carbonate and ammonium hydrogen carbonate. Ammonium carbonate is preferred because it is easily volatilized and is unlikely to remain in the obtained gas barrier layer.
[0771] (Zinc)
[0772] Zinc (Zn) can form water-resistant Zn phosphate bonds with phosphorus compounds, which can be detected by TOF-SIMS analysis 64 ZnPO4H - In the case where the gas barrier layer contains a polycarboxylic acid, a salt is formed with the polycarboxylic acid. Zn is zinc or a zinc compound that can be added to the mixture forming the gas barrier layer. For example, metallic zinc, zinc oxide (ZnO), a zinc compound, etc. can be used. The amount of zinc added can be set to 0.1 mol or more and 0.5 mol or less relative to 1 mol of the carboxyl group of the polycarboxylic acid.
[0773] (Phosphorus compounds)
[0774] As described above, when the gas barrier layer is subjected to mass spectrometry analysis, it is preferred to detect PO2 - and / or PO3 - In order to provide such a gas barrier layer, the mixture before curing preferably contains a phosphorus compound or a salt thereof.
[0775] The phosphorus compound or the phosphorus compound in the salt thereof contains one or more -P-OH groups in the molecular structure. The phosphorus compound may be added to the mixture in the form of a salt.
[0776] From the viewpoint of further improving the water vapor barrier property after retorting, the phosphorus compound preferably contains 2 or more -P-OH groups, and more preferably contains 3 or more -P-OH groups. In addition, from the viewpoint of productivity, the number of -P-OH groups in the phosphorus compound may be, for example, 10 or less.
[0777] Specific examples of the phosphorus compound include phosphoric acid, phosphorous acid, phosphonic acid, hypophosphorous acid, polyphosphoric acid, and derivatives thereof.
[0778] Specifically, the polyphosphoric acid has a condensed structure of two or more phosphoric acids in its molecular structure, and examples thereof include diphosphoric acid (pyrophosphoric acid), triphosphoric acid, and polyphosphoric acid in which four or more phosphoric acids are condensed.
[0779] Specific examples of derivatives include esters of the above-mentioned phosphorus compounds such as phosphorylated starch and phosphoric acid cross-linked starch; halides such as chlorides; acid anhydrides such as tetraphosphorus decoxide; and compounds having a structure in which the hydrogen atoms bonded to the phosphorus atoms are replaced by alkyl groups, such as nitrilotris(methylenephosphonic acid) and N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid).
[0780] From the viewpoint of further improving the balance between barrier properties and productivity, the phosphorus compound is one or more selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, polyphosphoric acid, phosphonic acid and salts thereof, and more preferably at least one selected from the group consisting of phosphoric acid, phosphorous acid, phosphonic acid and salts thereof.
[0781] Specific examples of the salt in the salt of the phosphorus compound include salts of monovalent metals such as sodium and potassium; and ammonium salts. From the viewpoint of barrier properties, the salt of the phosphorus compound is preferably an ammonium salt.
[0782] The concentration of P atoms in the phosphorus compound is typically 5×10 -4 mol or more, preferably 1×10 -3 mol or more, more preferably 5×10 -3In the case of a phosphorus compound containing one P atom in the chemical formula such as phosphoric acid, the number of moles of the P atom has the same meaning as the number of moles of the phosphorus compound.
[0783] It is believed that if the phosphorus compound or the phosphorus compound derived from the salt thereof has such a concentration, a Zn bond can be reliably formed with the water-resistant phosphorus compound, thereby suppressing the excessive swelling and shrinkage of the gas barrier layer due to the retorting treatment, etc., thereby further improving the gas barrier property of the gas barrier layered product after the retorting treatment. The existence of the bond between the phosphorus compound and Zn is obtained by the aforementioned TOF-SIMS analysis. 64 ZnPO4H - The mass peak reflects.
[0784] (Other ingredients)
[0785] The mixture constituting the gas barrier layer according to the third embodiment may or may not contain polyamine as other components, for example. When polyamine is contained, the barrier properties of the obtained gas barrier layered product can be improved, and the interlayer adhesion of the obtained gas barrier layered product can be improved, and the delamination resistance can be improved.
[0786] It should be noted that the fragments detected in the TOF-SIMS analysis can be detected independently, so the I( 64 ZnPO4H - ) / I(C3H3O2 - )、(I(PO2 - )+I(PO3 - )) / I(C3H3O2 - )、I(PO2 - ) / I(PO3 - ) is not affected by the presence or absence of polyamines.
[0787] Polyamines are polymers having two or more amino groups in the main chain, side chain or terminal. Specifically, aliphatic polyamines such as polyallylamine, polyvinylamine, polyethyleneimine, poly(propyleneimine) and the like; polyamides having amino groups in the side chains such as polylysine and polyarginine; and the like. In addition, polyamines obtained by modifying a part of the amino groups may also be used. The amount of polyamine added may be set to an amount that makes the active hydrogen in the polyamine be 0 mol or more and 0.9 mol or less relative to 1 mol of the carboxyl group contained in the above-mentioned polycarboxylic acid.
[0788] From the viewpoint of excellent balance between gas barrier properties and handling properties, the weight average molecular weight of the polyamine is preferably 50 to 2,000,000, more preferably 100 to 1,000,000, further preferably 1,500 to 500,000, further more preferably 1,500 to 100,000, further more preferably 1,500 to 50,000, further more preferably 3,500 to 20,000, further more preferably 5,000 to 15,000, particularly preferably 7,000 to 12,000.
[0789] Here, in the third embodiment, the molecular weight of the polyamine can be measured using a boiling point elevation method or a viscosity method.
[0790] (Method for producing gas barrier layer)
[0791] The gas barrier layer according to the third embodiment can be produced, for example, as follows.
[0792] First, a completely or partially neutralized solution of the carboxyl groups constituting the polycarboxylic acid is prepared.
[0793] A volatile base is added to the polycarboxylic acid to completely or partially neutralize the carboxyl groups of the polycarboxylic acid. By neutralizing the carboxyl groups of the polycarboxylic acid, gelation due to reaction with the carboxyl groups constituting the polycarboxylic acid when zinc is added in the subsequent process can be effectively prevented, thereby obtaining a uniform gas barrier coating material intermediate.
[0794] Next, a zinc salt compound and a carbonate-based ammonium salt are added to the above intermediate and dissolved, and the generated zinc ions form a zinc salt with the -COO- group constituting the polycarboxylic acid. At this time, the -COO- group that forms a salt with the zinc ion refers to both the carboxyl group that has not been neutralized with the base and the -COO- group that has been neutralized with the base. In the case of the -COO- group that has been neutralized with the base, the zinc ion from the above zinc is replaced and coordinated to form a zinc salt of the -COO- group. Then, phosphoric acid is added after the zinc salt is formed, thereby obtaining a gas barrier coating material (mixture).
[0795] The gas barrier coating material (mixture) thus manufactured is applied to the inorganic layer described later, dried and solidified, thereby forming a gas barrier layer. The method for applying the gas barrier coating material to the substrate layer is not particularly limited, and the usual method can be used. For example, various known coating machines such as Meyer rod coater, air knife coater, direct gravure coater, gravure offset press, arc gravure coater, reverse gravure press and jet nozzle method, top feed reverse coater, bottom feed reverse coater and nozzle feed reverse coater, five-roll coater, lip coater, rod coater, rod reverse coater, die coater, etc. can be cited for coating.
[0796] The coating amount (wet thickness) of the gas barrier coating material (mixture) is preferably 0.05 μm or more, more preferably 1 μm or more, and preferably 300 μm or less, more preferably 200 μm or less, and further preferably 100 μm or less.
[0797] In addition, the average thickness of the gas barrier layer after drying and curing is preferably 0.05 μm to 10 μm, more preferably 0.08 μm to 5 μm, and further preferably 0.1 μm to 1 μm. If it is below the above upper limit, the warping of the obtained gas barrier laminate and gas barrier film can be suppressed. In addition, if it is above the above lower limit, the barrier performance of the obtained gas barrier laminate and gas barrier film can be made better.
[0798] As for drying and heat treatment, heat treatment may be performed after drying, or drying and heat treatment may be performed simultaneously.
[0799] As for the method of drying and heating treatment, there is no particular limitation as long as the purpose of the present invention can be achieved, and it can be a method that can cure the gas barrier coating material or a method that can heat the cured gas barrier coating material. For example, there can be cited methods based on convection heat transfer such as ovens and dryers; methods based on conduction heat transfer such as heating rollers; methods based on radiation heat transfer using electromagnetic waves such as infrared, far-infrared and near-infrared heaters; and methods based on internal heating such as microwaves. As a device for drying and heating treatment, from the viewpoint of manufacturing efficiency, it is preferably a device that can perform both drying and heating treatment. Specifically, from the viewpoint of being able to be used for various purposes such as drying, heating, and annealing, it is preferred to use a hot air oven, and from the viewpoint of excellent heat conduction efficiency to the film, it is preferred to use a heating roller. In addition, the methods for drying and heating treatment can also be appropriately combined. A hot air oven and a heating roller can be used together. For example, when the gas barrier coating material is dried by a hot air oven and then heated by a heating roller, the time of the heating treatment process is shortened, which is preferred from the viewpoint of manufacturing efficiency. In addition, it is preferred to perform the drying and heating treatment only using a hot air oven.
[0800] For example, it is desirable to perform the heat treatment under the following conditions: the heat treatment temperature is 80 to 250°C and the heat treatment time is 1 second to 10 minutes; preferably the heat treatment temperature is 120 to 240°C and the heat treatment time is 1 second to 1 minute; more preferably the heat treatment temperature is 170 to 230°C and the heat treatment time is 1 second to 30 seconds. Furthermore, by using a heating roller as described above, the heat treatment can be performed in a short time. It is important to adjust the heat treatment temperature and the heat treatment time according to the wet thickness of the gas barrier coating material.
[0801] In the gas barrier coating material (mixture), the zinc salt of the -COO- group constituting the polycarboxylic acid forms a metal crosslink and a water-resistant Zn phosphate bond (as reflected in the above-mentioned TOF-SIMS analysis). 64 ZnPO4H - A gas barrier layer having excellent gas barrier properties can be obtained by drying and heat treatment.
[0802] (Inorganic layer)
[0803] Examples of the inorganic substance constituting the inorganic substance layer 4 include metals, metal oxides, metal nitrides, metal fluorides, metal oxynitrides, and the like that can form a thin film having barrier properties.
[0804] As the inorganic material constituting the inorganic layer 4, for example, one or more of the simple substances, oxides, nitrides, fluorides, or oxynitrides of periodic table 6A elements such as selenium and tellurium, etc., can be cited as inorganic materials constituting the inorganic material layer 4, for example, beryllium, magnesium, calcium, strontium, barium and other periodic table 2A group elements; titanium, zirconium, ruthenium, hafnium, tantalum and other periodic table transition elements; zinc and other periodic table 2B group elements; aluminum, gallium, indium, thallium and other periodic table 3A group elements; silicon, germanium, tin and other periodic table 4A group elements; selenium, tellurium and other periodic table 6A group elements, etc.
[0805] It should be noted that, in the third embodiment, the group names of the periodic table are expressed in the old CAS format.
[0806] Among the above-mentioned inorganic substances, one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide, and aluminum are preferred, and aluminum oxide is more preferred, from the viewpoint of excellent balance between barrier properties and cost.
[0807] It should be noted that silicon oxide may contain silicon monoxide and silicon monoxide in addition to silicon dioxide.
[0808] The inorganic layer is formed by the above-mentioned inorganic substance. The inorganic layer 4 can be composed of a single inorganic layer or a plurality of inorganic layers. In addition, when the inorganic layer 4 is composed of a plurality of inorganic layers, it can be composed of the same type of inorganic layers or different types of inorganic layers.
[0809] From the viewpoint of the balance among barrier properties, adhesion, handleability, etc., the thickness of the inorganic layer 4 is usually 1 nm to 1000 nm, preferably 1 nm to 500 nm.
[0810] In the third embodiment, the thickness of the inorganic substance layer can be determined from an observation image obtained by a transmission electron microscope or a scanning electron microscope.
[0811] The method for forming the inorganic layer is not particularly limited. For example, the inorganic layer 4 can be formed on one or both sides of the substrate layer 2 by vacuum evaporation, ion plating, sputtering, chemical vapor deposition, physical vapor deposition, chemical vapor deposition (CVD), plasma CVD, sol-gel, etc. Among them, sputtering, ion plating, chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma CVD, etc., film formation under reduced pressure is ideal. Therefore, it is predicted that chemically active molecular species containing silicon such as silicon nitride and silicon oxynitride react quickly, thereby improving the smoothness of the surface of the inorganic layer 4 and reducing pores.
[0812] In order to rapidly carry out these bonding reactions, it is desirable that the inorganic atom, compound be a chemically active molecular species or atomic species.
[0813] (Base material layer)
[0814] The substrate layer 2 can be used without particular limitation as long as it is a substrate layer on which a solution of a gas barrier coating material can be applied. For example, organic materials such as thermosetting resins, thermoplastic resins, or paper, inorganic materials such as glass, pottery, ceramics, silicon oxide, silicon oxynitride, silicon nitride, concrete, aluminum, aluminum oxide, iron, copper, stainless steel, etc., and a substrate layer of a multilayer structure formed by a combination of organic materials or a combination of organic materials and inorganic materials can be cited. Among them, for example, in the case of various film uses such as packaging materials and panels, plastic films using thermosetting resins, thermoplastic resins, or organic materials such as paper are preferably used.
[0815] As the thermosetting resin, a known thermosetting resin can be used, for example, epoxy resin, unsaturated polyester resin, phenol resin, urea-melamine resin, polyurethane resin, silicone resin, polyimide, etc. can be mentioned.
[0816] As the thermoplastic resin, known thermoplastic resins can be used, for example, polyolefins (polyethylene, polypropylene, poly(4-methyl-1-pentene), poly(1-butene), etc.), polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyamides (nylon-6, nylon-66, poly(m-xylylene adipamide), etc.), polyvinyl chloride, polyimide, ethylene-vinyl acetate copolymer or its saponified product, polyvinyl alcohol, polyacrylonitrile, polycarbonate, polystyrene, ionomer, fluororesin, or mixtures thereof.
[0817] Among them, from the viewpoint of achieving good transparency, one or more resins selected from the group consisting of polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide and polybutylene terephthalate are preferred, and from the viewpoint of excellent pinhole resistance, breakage resistance and heat resistance, one or more resins selected from the group consisting of polyamide, polyethylene terephthalate and polybutylene terephthalate are preferred.
[0818] In addition, depending on the application of the gas barrier layered product 8, the base layer 2 formed of a thermoplastic resin may be a single layer or may be two or more layers.
[0819] Alternatively, the base layer may be prepared by stretching a film made of the above-mentioned thermosetting resin or thermoplastic resin in at least one direction, preferably in two directions.
[0820] As the substrate layer 2 involved in the third embodiment, from the viewpoint of excellent transparency, rigidity and heat resistance, it is preferably a biaxially stretched film formed from one or more thermoplastic resins selected from polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide and polybutylene terephthalate, and more preferably a biaxially stretched film formed from one or more thermoplastic resins selected from polyamide, polyethylene terephthalate and polybutylene terephthalate.
[0821] The surface of the base material layer 2 may be coated with polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, acrylic resin, urethane resin or the like.
[0822] Furthermore, the base material layer 2 may be subjected to a surface treatment to improve adhesion, and specifically, may be subjected to a surface activation treatment such as a corona treatment, a flame treatment, a plasma treatment, or a primer coating treatment.
[0823] From the viewpoint of obtaining good film properties, the thickness of the base material layer 2 is preferably 1 to 1000 μm, more preferably 1 to 500 μm, and even more preferably 1 to 300 μm.
[0824] The shape of the base material layer 2 is not particularly limited, and examples thereof include a sheet or film shape, a tray, a cup, a hollow body, and the like.
[0825] (Base coating)
[0826] In the gas barrier laminate 8, a primer layer 3 may be formed on the surface of the substrate layer 2 from the viewpoint of improving the adhesion between the substrate layer 2 and the inorganic layer 4. The primer layer is preferably a layer formed of an epoxy (meth)acrylate compound or a urethane (meth)acrylate compound.
[0827] The primer layer 3 is preferably a layer formed by curing at least one selected from epoxy (meth)acrylate compounds and urethane (meth)acrylate compounds.
[0828] Examples of epoxy (meth) acrylate compounds include compounds obtained by reacting epoxy compounds such as bisphenol A epoxy compounds, bisphenol F epoxy compounds, bisphenol S epoxy compounds, phenol Novolac epoxy compounds, cresol Novolac epoxy compounds, and aliphatic epoxy compounds with acrylic acid or methacrylic acid, and acid-modified epoxy (meth) acrylates obtained by reacting the above epoxy compounds with carboxylic acids or their anhydrides. These epoxy (meth) acrylate compounds are applied to the surface of the substrate layer together with a diluent containing a photopolymerization initiator and, if necessary, other photopolymerization initiators or a thermoreactive monomer, and then irradiated with ultraviolet rays to form a primer layer through a crosslinking reaction.
[0829] Examples of the urethane (meth)acrylate compound include compounds obtained by subjecting an oligomer composed of a polyol compound and a polyisocyanate compound (hereinafter also referred to as a polyurethane oligomer) to acrylate.
[0830] Polyurethane oligomers can be obtained from condensation products of polyisocyanate compounds and polyol compounds. As specific polyisocyanate compounds, examples include methylene bis (p-phenylene diisocyanate), adducts of hexamethylene diisocyanate hexanetriol, hexamethylene diisocyanate, toluene diisocyanate, adducts of toluene diisocyanate trimethylolpropane, 1,5-naphthalene diisocyanate, thiopropyl diisocyanate, ethylbenzene-2,4-diisocyanate, 2,4-toluene diisocyanate dimer, hydrogenated xylylene diisocyanate, tris (4-phenylisocyanate) thiophosphate, etc., and as specific polyol compounds, there are polyether polyols such as polyoxytetramethylene glycol, polyester polyols such as polyadipate polyols and polycarbonate polyols, copolymers of acrylates and hydroxyethyl methacrylate, etc. Examples of the monomer constituting the acrylic acid ester include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and phenyl (meth)acrylate.
[0831] These epoxy (meth)acrylate compounds and urethane (meth)acrylate compounds can be used together as needed. In addition, various known methods can be mentioned as methods for polymerizing them, and specifically, methods such as irradiation with energy rays containing ionizing rays or heating can be mentioned.
[0832] When the primer layer is formed by ultraviolet curing, it is preferred to use acetophenones, benzophenones, Michler's benzoyl benzoate, α-amyl oxime ester or thioxanthones as photopolymerization initiators, and n-butylamine, triethylamine, tri-n-butylphosphine as photosensitizers. In addition, in the third embodiment, epoxy (meth) acrylate compounds and carbamate (meth) acrylate compounds can also be used in combination.
[0833] In addition, these epoxy (meth)acrylate compounds and urethane (meth)acrylate compounds can be diluted with (meth)acrylic monomers. Examples of such (meth)acrylic monomers include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, phenyl (meth)acrylate, trimethylolpropane tri(meth)acrylate as a multifunctional monomer, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate.
[0834] Among them, when a urethane (meth)acrylate compound is used as the primer layer, the oxygen barrier property of the obtained gas barrier layered product 8 can be further improved.
[0835] The thickness of the primer layer in the third embodiment is usually 0.01 to 100 g / m 2 In the range of 0.05 to 50 g / m 2 within the range.
[0836] (Adhesive layer)
[0837] In addition, an adhesive layer 6 may be provided on the gas barrier layer 5. The adhesive layer 6 may contain a known adhesive. As the adhesive, there may be cited a laminating adhesive composed of an organic titanium resin, a polyethyleneimine resin, a carbamate resin, an epoxy resin, an acrylic resin, a polyester resin, a resin containing an oxazoline group, a modified silicone resin and an alkyl titanate, a polyester polybutadiene, or a one-component type, a two-component type polyol and a polyisocyanate, an aqueous carbamate, an ion cross-linked polymer, etc. Alternatively, an aqueous adhesive having an acrylic resin, a vinyl acetate resin, a carbamate resin, a polyester resin, etc. as the main raw material may be used.
[0838] In addition, other additives such as a curing agent and a silane coupling agent may be added to the adhesive depending on the application of the gas barrier laminate 8. When the gas barrier laminate is used for hot water treatment such as boiling, from the viewpoint of heat resistance and water resistance, a dry lamination adhesive represented by a polyurethane adhesive is preferred, and a solvent-based two-component curing polyurethane adhesive is more preferred.
[0839] The gas barrier layered product 8 according to the third embodiment has excellent gas barrier properties after retorting regardless of the lamination structure. Therefore, it is preferably used as a packaging material, especially a food packaging material for contents requiring high gas barrier properties. In addition, it can also be suitably used as a variety of packaging materials for medical purposes, industrial purposes, daily sundries, etc.
[0840] The gas barrier layered product 8 of the third embodiment can be suitably used as, for example, a vacuum heat insulating film requiring high barrier performance, a sealing film for sealing an electroluminescent element, a solar cell, or the like, and the like.
[0841] <Fourth Implementation Method>
[0842] Fig.13 It is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the fourth embodiment. Fig.13 The gas barrier laminate 100 shown includes a substrate layer 101, a gas barrier layer 103 provided on at least one surface of the substrate layer 101, and an inorganic layer 102 provided between the substrate layer 101 and the gas barrier layer 103. The gas barrier layer 103 is composed of a cured product of a mixture containing a polycarboxylic acid, a polyamine compound, a polyvalent metal compound, and a phosphorus compound containing one or more -P-OH groups or a salt thereof.
[0843] The specific structure of each layer will be described later.
[0844] In the gas barrier laminate 100, the substrate layer 101, the inorganic layer 102 and the gas barrier layer 103 are stacked in sequence, and the gas barrier layer 103 is composed of a solidified product of the above-mentioned mixture. Therefore, the balance between barrier properties and productivity is excellent, and ideal barrier properties can be exerted in various layer structures.
[0845] More specifically, the gas barrier laminate 100 has excellent barrier properties such as oxygen barrier property and water vapor barrier property after the steaming treatment. In addition, in the gas barrier laminate 100, the gas barrier layer 103 is composed of a cured product of the above-mentioned mixture, so even if the curing time (specifically, the heating treatment time) when obtaining the gas barrier layer 103 is short, for example, a gas barrier laminate 100 with excellent barrier properties can be obtained.
[0846] In addition, the gas barrier layer 103 is composed of a cured product of a mixture of a polycarboxylic acid, a polyamine compound, a polyvalent metal compound, and a phosphorus compound containing one or more -P-OH groups or their salts. Therefore, for example, a gas barrier laminate 100 with excellent barrier properties and water resistance can also be obtained.
[0847] Fig.14 It is a cross-sectional view schematically showing another configuration example of the gas barrier layered product. Fig.14 The basic structure of the gas barrier laminate 110 shown in FIG. Fig.13 The gas barrier laminate 100 described above is similar, but is different in that it further includes a primer layer 104 provided between the base layer 101 and the inorganic substance layer 102 .
[0848] The gas barrier layer 110 can also achieve the same effects as those of the gas barrier layer 100. In addition, in the gas barrier layer 110, by providing the primer layer 104 between the base layer 101 and the inorganic layer 102, the adhesion between the base layer 101 and the inorganic layer 102 can be further improved.
[0849] Hereinafter, the configuration of the layers included in the gas barrier layered product will be described in more detail. First, the gas barrier layer 103 will be described.
[0850] (Gas barrier layer)
[0851] The gas barrier layer 103 is composed of a cured product of a mixture containing a polycarboxylic acid, a polyamine compound, and a polyvalent metal compound. More specifically, the gas barrier layer 103 is a film (gas barrier film 10) composed of the cured product.
[0852] More specifically, the gas barrier layer 103 can be obtained, for example, as follows: after coating the pre-cured mixture, i.e., the gas barrier coating material, on a layer such as the inorganic layer 102 arranged immediately below the gas barrier layer 103, drying and heat treating the mixture to cure the gas barrier coating material, the gas barrier coating material is obtained.
[0853] In the infrared absorption spectrum of the gas barrier layer 103, at 1300 cm -1 Above 1490cm -1 The maximum peak height of the absorbance in the following range is defined as α and 1690 cm -1 Above 1780cm -1When the maximum peak height of the absorbance in the following range is set to γ, from the viewpoint of liquid stability of the gas barrier coating material before coating, the ratio of free carboxyl groups to the NH3 complex represented by γ / α is preferably 0.00 or more, more preferably 0.01 or more, and further preferably 0.02 or more.
[0854] In addition, from the perspective of improving the barrier properties of the gas barrier layer 103 obtained after coating, the above-mentioned γ / α is preferably less than 1.00, more preferably less than 0.80, further preferably less than 0.60, further more preferably less than 0.40, further preferably less than 0.20, and further preferably less than 0.10.
[0855] In the infrared absorption spectrum of the gas barrier layer 103, the wavelength at 1493 cm -1 Above 1780cm -1 The total peak area within the following absorption band range is defined as A, and the peak area at 1598 cm -1 Above 1690cm -1 The total peak area within the following absorption band range is defined as B, and the peak area at 1690 cm -1 Above 1780cm -1 The total peak area within the following absorption band range is defined as C, and the peak area at 1493 cm -1 Above 1598cm -1 When the total peak area in the following absorption band range is defined as D, preferred examples of the area ratio are shown below.
[0856] In the infrared absorption spectrum of the gas barrier layer 103, from the viewpoint of further improving the gas barrier performance after retorting, the area ratio of the amide bonds represented by B / A is preferably 0.200 or more, more preferably 0.220 or more, and even more preferably 0.250 or more.
[0857] From the viewpoint of further improving the balance between barrier properties and productivity, the area ratio of the amide bonds represented by B / A is preferably 0.370 or less, more preferably 0.350 or less, and even more preferably 0.300 or less.
[0858] In the infrared absorption spectrum of the gas barrier layer 103, from the viewpoint of further improving the gas barrier performance after the steaming treatment, the area ratio of carboxylic acid represented by C / A is preferably 0.150 or less, more preferably 0.100 or less, further preferably 0.080 or less, and further more preferably 0.060 or less.
[0859] The lower limit of the area ratio of the carboxylic acid represented by C / A is not limited, and may be, for example, 0.000 or more, or, for example, 0.0001 or more.
[0860] In the infrared absorption spectrum of the gas barrier layer 103 , from the viewpoint of further improving the balance between barrier properties and productivity, the area ratio of the carboxylate represented by D / A is preferably 0.580 or more, more preferably 0.600 or more.
[0861] From the viewpoint of further improving the gas barrier performance after retorting, the D / A is preferably 0.800 or less, more preferably 0.780 or less, further preferably 0.760 or less, and still further preferably 0.740 or less.
[0862] In addition, from the viewpoint of achieving a more ideal balance between the productivity and barrier properties of the gas barrier layered product, it is also preferred that the area ratio of the amide bond represented by B / A is greater than 0.200 and less than 0.370, the area ratio of the carboxylic acid represented by C / A is less than 0.150, and the area ratio of the carboxylate represented by D / A is greater than 0.580 and less than 0.800.
[0863] In the infrared absorption spectrum of the gas barrier layer 103, from the viewpoint of improving the barrier properties, the area ratio of the carboxylate represented by D / A relative to the area ratio of the amide bond represented by B / A is preferably 1.2 or more, more preferably 1.5 or more, and more preferably 2.0 or more.
[0864] From the viewpoint of improving barrier properties after retorting, the area ratio of the carboxylate represented by D / A to the area ratio of the amide bond represented by B / A is preferably 4.0 or less, more preferably 3.5 or less, and even more preferably 3.0 or less.
[0865] Here, in the gas barrier layer 103, at 1700 cm -1 The absorption of νC=O based on unreacted carboxylic acid in the near visible infrared absorption spectrum is at 1630-1685 cm -1 Nearby, absorption based on νC=O of the amide bond as a cross-linked structure can be seen at 1540~1560cm -1 The absorption of νC=O based on carboxylate can be seen nearby, at 1300~1490cm -1 Absorption of δN-H based on ammonia forming a complex is observed nearby.
[0866] It is believed that 1300cm in the infrared absorption spectrum -1 Above 1490cm -1 The maximum peak height α of the absorbance in the following range is an indicator of the amount of ammonia present in the complex formed, 1690 cm -1 Above 1780cm -1The maximum peak height γ in the following range represents an indicator of the amount of free, ie, unreacted, carboxylic acid present.
[0867] In the fourth embodiment, specifically, the maximum peak heights α and γ can be measured by the following steps. That is, a 1 cm × 3 cm measurement sample is cut out from the gas barrier layer 103. Then, an infrared absorption spectrum of the surface of the gas barrier layer 103 is obtained by infrared total reflection measurement (ATR method). In the obtained infrared absorption spectrum, a straight line is connected between 900 cm -1 The absorbance at 1900 cm -1 The line formed by the absorbance is used as the baseline, and the maximum peak height within the range of each absorbance is calculated.
[0868] In addition, it is believed that the 1493 cm -1 Above 1780cm -1 The total peak area A in the following absorption band range is an indicator of the total amount of carboxylic acid, amide bond and carboxylate: 1598 cm -1 Above 1690cm -1 The total peak area B within the following absorption band range is an indicator of the amount of amide bonds present. -1 Above 1780cm -1 The total peak area C in the following absorption band range is an indicator of the amount of unreacted carboxylic acid present: 1493 cm -1 Above 1598cm -1 The total peak area D within the following absorption band range is an indicator of the amount of carboxylate present.
[0869] In the fourth embodiment, specifically, the total peak areas A to D can be measured by the following procedure.
[0870] First, a 1 cm×3 cm measurement sample is cut out from the gas barrier layer 103. Next, an infrared absorption spectrum of the surface of the gas barrier layer 103 is obtained by infrared total reflection measurement (ATR method). Based on the obtained infrared absorption spectrum, the total peak areas A to D are calculated by the following steps (1) to (4).
[0871] (1) 1780cm -1 With 1493cm -1 The absorbance of 1493cm -1 Above 1780cm -1 The area surrounded by N in the absorption spectrum within the following absorption band is taken as the total peak area A.
[0872] (2) From 1690cm -1Draw a straight line (O) vertically from the absorbance (Q) of N and O, and take the intersection of N and O as P. -1 Draw a straight line (S) vertically from the absorbance (R) of N, and take the intersection of N and S as T. -1 Above 1690cm -1 The area enclosed by the absorption spectrum within the following absorption band and the straight line S, point T, straight line N, point P, straight line O, absorbance Q, and absorbance R is taken as the total peak area B.
[0873] (3) will be 1690cm -1 Above 1780cm -1 The absorption spectrum within the following absorption band range and the area surrounded by absorbance Q, straight line O, point P, and straight line N are taken as the total peak area C.
[0874] (4) will be 1493cm -1 Above 1598cm -1 The absorption spectrum within the following absorption band range and the area surrounded by absorbance R, straight line S, point T, and straight line N are taken as the total peak area D.
[0875] Next, the area ratios B / A, C / A, and D / A are obtained from the areas obtained by the above method.
[0876] It should be noted that, in the fourth embodiment, for the measurement of infrared absorption spectrum (infrared total reflection measurement: ATR method), for example, an IRT-5200 device manufactured by JASCO Corporation can be used, with a PKM-GE-S (germanium) crystal installed, at an incident angle of 45 degrees, room temperature, and a resolution of 4 cm -1 , the cumulative number of times is 100 times.
[0877] The maximum peak heights α and γ of the gas barrier layer 103, and the area ratio of the amide bonds represented by B / A, the area ratio of the carboxylic acids represented by C / A, and the area ratio of the carboxylate represented by D / A can be controlled by appropriately adjusting the production conditions of the gas barrier layer 103. Specifically, as factors for controlling the maximum peak heights α and γ of the gas barrier layer 103, and the area ratio of the amide bonds represented by B / A, the area ratio of the carboxylic acids represented by C / A, and the area ratio of the carboxylate represented by D / A, the mixing ratio of the polycarboxylic acid, the polyamine compound, the polyvalent metal compound, and the phosphorus compound, the method for preparing the mixture before curing, the method, temperature, and time of heating the mixture, etc. can be cited.
[0878] Next, components contained in the mixture (gas barrier coating material) before curing will be described.
[0879] (Polycarboxylic Acid)
[0880] Polycarboxylic acid is a compound having two or more carboxyl groups in the molecule. Specifically, homopolymers of α,β-unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, 3-hexenedioic acid, or copolymers thereof may be cited. In addition, copolymers of the above-mentioned α,β-unsaturated carboxylic acids with esters such as ethyl esters, olefins such as ethylene, etc. may also be mentioned.
[0881] Among them, preferred are homopolymers of acrylic acid, methacrylic acid, itaconic acid, fumaric acid, crotonic acid, and cinnamic acid, or copolymers thereof; more preferred are one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid; further preferred are at least one polymer selected from polyacrylic acid and polymethacrylic acid; and still more preferred are at least one polymer selected from homopolymers of acrylic acid and homopolymers of methacrylic acid.
[0882] Here, in the fourth embodiment, the so-called polyacrylic acid includes both homopolymers of acrylic acid and copolymers of acrylic acid and other monomers. In the case of a copolymer of acrylic acid and other monomers, the polyacrylic acid contains generally 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from acrylic acid in 100% by mass of the polymer.
[0883] In the fourth embodiment, the polymethacrylic acid includes both homopolymers of methacrylic acid and copolymers of methacrylic acid and other monomers. In the case of copolymers of methacrylic acid and other monomers, the polymethacrylic acid contains structural units derived from methacrylic acid in an amount of usually 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more, based on 100% by mass of the polymer.
[0884] The polycarboxylic acid is a polymer obtained by polymerizing carboxylic acid monomers. The molecular weight of the polycarboxylic acid is preferably 500 to 2,500,000, more preferably 5,000 to 2,000,000, more preferably 10,000 to 1,500,000, and even more preferably 100,000 to 1,200,000, from the viewpoint of excellent balance between gas barrier properties and handling properties.
[0885] Here, in the fourth embodiment, the molecular weight of the polycarboxylic acid is a weight average molecular weight calculated as polyethylene oxide, and can be measured using gel permeation chromatography (GPC).
[0886] At least a portion of the polycarboxylic acid can be neutralized with a volatile base. By neutralizing the polycarboxylic acid with a volatile base, the occurrence of gelation can be suppressed when a polyvalent metal compound, a polyamine compound and the polycarboxylic acid are mixed. Therefore, in the polycarboxylic acid, from the viewpoint of preventing gelation, it is preferred to prepare a partially neutralized or completely neutralized product of the carboxyl group with a volatile base. The neutralized product can be obtained by partially or completely neutralizing the carboxyl group of the polycarboxylic acid with a volatile base, that is, preparing the carboxyl group of the polycarboxylic acid partially or completely into a carboxylate. Thus, gelation can be prevented when a polyamine compound or a polyvalent metal compound is added.
[0887] The partially neutralized product can be prepared by adding a volatile base to an aqueous solution of a polycarboxylic acid polymer, and the desired neutralization degree can be obtained by adjusting the amount ratio of the polycarboxylic acid to the volatile base. In the fourth embodiment, from the viewpoint of fully suppressing gelation caused by the neutralization reaction with the amino group of the polyamine compound, the neutralization degree of the polycarboxylic acid obtained by the volatile base is preferably 70 to 300 equivalents, more preferably 90 to 250 equivalents, and further preferably 100 to 200 equivalents.
[0888] As the volatile base, any water-soluble base can be used.
[0889] Examples of the volatile base include ammonia, morpholine, alkylamines, tertiary amines such as 2-dimethylaminoethanol, N-methylmorpholine, ethylenediamine, and triethylamine, or aqueous solutions thereof, or mixtures thereof. From the viewpoint of obtaining good gas barrier properties, aqueous ammonia solutions are preferred.
[0890] (Polyamine compounds)
[0891] The mixture before curing contains a polyamine compound. By containing a polyamine compound, the barrier properties of the obtained gas barrier material can be improved.
[0892] The polyamine compound is a compound having two or more amino groups in the main chain, side chain or terminal, and is preferably a polymer. Specifically, aliphatic polyamines such as polyallylamine, polyvinylamine, polyethyleneimine, poly(propyleneimine) and the like; polyamides having amino groups in the side chains such as polylysine and polyarginine; and the like can be cited. In addition, a polyamine obtained by modifying a part of the amino groups may also be used.
[0893] From the viewpoint of obtaining good gas barrier properties, the polyamine compound preferably contains polyethyleneimine, and more preferably polyethyleneimine.
[0894] From the viewpoint of excellent balance between gas barrier properties and handleability, the number average molecular weight of the polyamine compound is preferably 50 to 2,000,000, more preferably 100 to 1,000,000, further preferably 1,500 to 500,000, further more preferably 1,500 to 100,000, further more preferably 1,500 to 50,000, further more preferably 3,500 to 20,000, further more preferably 5,000 to 15,000, further more preferably 7,000 to 12,000.
[0895] Here, in the fourth embodiment, the molecular weight of the polyamine compound can be measured using a boiling point elevation method or a viscosity method.
[0896] From the viewpoint of further improving the gas barrier performance after the retort treatment, (the number of moles of amino groups contained in the polyamine compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.20 or more, more preferably 0.25 or more, further preferably 0.30 or more, further more preferably 0.35 or more, and further preferably 0.40 or more.
[0897] From the same point of view, (the number of moles of amino groups contained in the polyamine compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.90 or less, more preferably 0.85 or less, further preferably 0.80 or less, further more preferably 0.75 or less, and further preferably 0.70 or less.
[0898] Although the detailed reason is unclear, it is believed that by forming a dense structure with good balance between amide crosslinking (which is formed by amino groups constituting polyamine compounds) and metal crosslinking (which is formed by polyvalent metals constituting salts of polycarboxylic acids and polyvalent metals), a gas barrier layer 103 with excellent gas barrier performance after steaming treatment and a gas barrier laminate having the same can be obtained.
[0899] (Polyvalent Metal Compounds)
[0900] The polyvalent metal compound specifically refers to metals and metal compounds belonging to Groups 2 to 13 of the periodic table, and more specifically, bivalent or higher metals such as magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), and aluminum (Al), and oxides, hydroxides, halides, carbonates, phosphates, phosphites, hypophosphites, sulfates, or sulfites of these metals. From the viewpoints of water resistance, impurities, etc., metal oxides or metal hydroxides are preferred.
[0901] From the viewpoint of further improving the gas barrier performance after retorting, the divalent or higher metal in the polyvalent metal compound is preferably one or more metals selected from the group consisting of Zn, Ca, Mg, Ba and Al, and more preferably Zn.
[0902] From the same viewpoint, the polyvalent metal compound is preferably a compound of one or more divalent or higher metals selected from the group consisting of Zn, Ca, Mg, Ba and Al, and more preferably a Zn compound.
[0903] From the same viewpoint, the polyvalent metal compound is preferably one or more compounds selected from the group consisting of oxides such as magnesium oxide, calcium oxide, barium oxide, zinc oxide, and magnesium hydroxide, and hydroxides such as calcium hydroxide, barium hydroxide, and zinc hydroxide, more preferably at least one of zinc oxide and zinc hydroxide, and further preferably zinc oxide.
[0904] In the fourth embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.10 or more, more preferably 0.13 or more, further preferably 0.15 or more, and further more preferably 0.18 or more.
[0905] From the same point of view, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.80 or less, more preferably 0.70 or less, further preferably 0.60 or less, further more preferably 0.55 or less, and further preferably 0.50 or less.
[0906] In the fourth embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of the amino group derived from the polyamine compound in the mixture) is preferably 0.25 or more, more preferably 0.35 or more, and even more preferably 0.40 or more.
[0907] From the same viewpoint, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of the amino groups derived from the polyamine compound in the mixture) is preferably 0.65 or less, more preferably 0.60 or less, and even more preferably 0.55 or less.
[0908] (Phosphorus compound or its salt)
[0909] The phosphorus compound or the phosphorus compound in the salt thereof contains one or more -P-OH groups in the molecular structure. The phosphorus compound may be added to the mixture in the form of a salt.
[0910] From the viewpoint of further improving the water vapor barrier property after retorting, the phosphorus compound preferably contains two or more -P-OH groups, and more preferably contains three or more -P-OH groups. In addition, from the viewpoint of improving the liquid stability of the gas barrier coating material, the number of -P-OH groups in the phosphorus compound may be, for example, two or less.
[0911] Specific examples of the phosphorus compound include phosphoric acid, phosphorous acid, phosphonic acid, hypophosphorous acid, polyphosphoric acid, and derivatives thereof.
[0912] Specifically, the polyphosphoric acid has a condensed structure of two or more phosphoric acids in its molecular structure, and examples thereof include diphosphoric acid (pyrophosphoric acid), triphosphoric acid, and polyphosphoric acid in which four or more phosphoric acids are condensed.
[0913] Specific examples of derivatives include:
[0914] Esters of the above-mentioned phosphorus compounds such as phosphorylated starch and phosphorylated cross-linked starch;
[0915] Halides such as chlorides;
[0916] Anhydrides such as tetraphosphorus decoxide; and
[0917] A compound having a structure in which a hydrogen atom bonded to a phosphorus atom is substituted with an alkyl group, such as nitrilotris(methylenephosphonic acid) and N,N,N',N'-ethylenediaminetetra(methylenephosphonic acid).
[0918] From the viewpoint of further improving the balance between barrier properties and productivity, the phosphorus compound is one or more selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, polyphosphoric acid, phosphonic acid and salts thereof, and more preferably at least one selected from the group consisting of phosphoric acid and phosphorous acid.
[0919] Specific examples of the salt in the salt of the phosphorus compound include salts of monovalent metals such as sodium and potassium; and ammonium salts. From the viewpoint of improving barrier properties, the salt of the phosphorus compound is preferably an ammonium salt.
[0920] In the fourth embodiment, from the viewpoint of improving barrier properties, (the number of moles of P atoms derived from the phosphorus compound or its salt in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) may be, for example, 0.0001 or more, preferably 0.001 or more, more preferably 0.003 or more, and further preferably 0.005 or more. In a phosphorus compound containing one P atom in the chemical formula such as phosphoric acid, the number of moles of P atoms and the number of moles of the phosphorus compound have the same meaning.
[0921] In addition, from the viewpoint of improving the liquid stability of the barrier coating material (mixture), (the number of moles of P atoms derived from the phosphorus compound or its salt in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is preferably 0.3 or less, more preferably 0.1 or less, further preferably 0.08 or less, and further more preferably 0.005 or less.
[0922] The mixture before curing may contain components other than the above components.
[0923] For example, the mixture preferably further comprises carbonate ammonium salt. Carbonate ammonium salt is a substance added to make the polyvalent metal compound into a state of carbonate polyvalent metal ammonium complex, thereby improving the solubility of the polyvalent metal compound and preparing a uniform solution containing the polyvalent metal compound. By making the mixture before solidification contain carbonate ammonium salt, the dissolution amount of the polyvalent metal compound can be increased, and as a result, the mixture with the polyvalent metal compound can be made more uniform.
[0924] Examples of the carbonate-based ammonium salt include ammonium carbonate and ammonium hydrogen carbonate. Ammonium carbonate is preferred because it is easily volatilized and is unlikely to remain in the obtained gas barrier layer.
[0925] From the viewpoint of further improving the solubility of the polyvalent metal compound, (the number of moles of the carbonate-based ammonium salt in the mixture) / (the number of moles of the polyvalent metal compound in the mixture) is preferably greater than 0.05, more preferably greater than 0.10, further preferably greater than 0.25, further more preferably greater than 0.50, and further preferably greater than 0.75.
[0926] In addition, from the viewpoint of further improving the coating properties of the gas barrier coating material, (the number of moles of carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of polyvalent metal compound in the gas barrier coating material) is preferably 10.0 or less, more preferably 5.0 or less, further preferably 2.0 or less, and further more preferably 1.5 or less.
[0927] Furthermore, from the viewpoint of suppressing the generation of depressions when the mixture is applied as a gas barrier coating material, the mixture before curing preferably further contains a surfactant.
[0928] When the solid content of the mixture as a whole is 100% by mass, the amount of the surfactant added is preferably 0.01 to 3% by mass, and more preferably 0.01 to 1% by mass.
[0929] Examples of the surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. From the viewpoint of obtaining good coating properties, nonionic surfactants are preferred, polyoxyalkylene alkyl ethers are more preferred, and polyoxyethylene alkyl ethers are still more preferred.
[0930] Examples of the nonionic surfactant include polyoxyalkylene alkyl aryl ethers, polyoxyalkylene alkyl ethers, polyoxyalkylene fatty acid esters, sorbitan fatty acid esters, silicone-based surfactants, acetylene alcohol-based surfactants, and fluorine-containing surfactants.
[0931] Examples of the polyoxyalkylene alkyl aryl ethers include polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene dodecylphenyl ether, and the like.
[0932] Examples of the polyoxyalkylene alkyl ethers include polyoxyethylene alkyl ethers such as polyoxyethylene oleyl ether and polyoxyethylene lauryl ether.
[0933] Examples of the polyoxyalkylene fatty acid esters include polyoxyethylene oleate, polyoxyethylene laurate, polyoxyethylene distearate, and the like.
[0934] Examples of the sorbitan fatty acid esters include sorbitan laurate, sorbitan monostearate, sorbitan monooleate, sorbitan sesquioleate, polyoxyethylene monooleate, and polyoxyethylene stearate.
[0935] Examples of the silicone-based surfactant include dimethylpolysiloxane and the like.
[0936] Examples of the acetylene alcohol surfactant include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,6-dimethyl-4-octyne-3,6-diol, and 3,5-dimethyl-1-hexyne-3-ol.
[0937] Examples of the fluorine-containing surfactant include fluoroalkyl esters and the like.
[0938] The mixture before curing may contain additives other than the above-mentioned components, for example, various additives such as lubricants, slip agents, anti-caking agents, antistatic agents, anti-fogging agents, pigments, dyes, inorganic or organic fillers, etc. may be added.
[0939] In order to improve coating properties when the mixture is applied as a gas barrier coating material, the solid content concentration of the mixture before curing is preferably 0.5 to 15% by mass, more preferably 1 to 10% by mass.
[0940] (Method for producing gas barrier layer)
[0941] Specifically, the gas barrier layer 103 can be produced by applying a pre-cured mixture (gas barrier coating material) and curing the mixture.
[0942] The mixture can be obtained as follows.
[0943] First, a volatile base is appropriately added to a polycarboxylic acid to completely or partially neutralize the carboxyl groups of the polycarboxylic acid. A polyvalent metal salt compound and an appropriate carbonate-based ammonium salt are further mixed to form a metal salt in all or part of the carboxyl groups of the polycarboxylic acid neutralized with the volatile base and in the carboxyl groups of the polycarboxylic acid not neutralized with the volatile base.
[0944] Then, a polyamine compound is further added, and finally a phosphorus compound or a salt thereof is added to obtain a mixture before curing. Thus, a salt is formed between the phosphorus compound and the amino group of the polyvalent metal compound or the polyamine.
[0945] Since the polycarboxylic acid, the polyvalent metal salt compound, the phosphorus compound or its salt, the appropriate carbonate-based ammonium salt and the polyamine compound are mixed in such a step, the formation of agglomerates can be suppressed and a more uniform mixture can be obtained. Thus, the dehydration condensation reaction between the -COO- group contained in the polycarboxylic acid and the amino group contained in the polyamine compound can be carried out more effectively.
[0946] The details are as follows: Hereinafter, the case where a volatile base and a carbonate-based ammonium salt are added to the mixture will be described as an example.
[0947] First, a completely or partially neutralized solution of the carboxyl groups constituting the polycarboxylic acid is prepared.
[0948] A volatile base is added to the polycarboxylic acid to completely or partially neutralize the carboxyl groups of the polycarboxylic acid. By neutralizing the carboxyl groups of the polycarboxylic acid, gelation caused by the reaction of the carboxyl groups constituting the polycarboxylic acid with the amino groups constituting the polyvalent metal compound and the polyamine compound when a polyvalent metal compound or a polyamine compound is added can be effectively prevented, thereby obtaining a more uniform mixture.
[0949] Next, a polyvalent metal salt compound and a carbonate ammonium salt are added and dissolved, and the generated polyvalent metal ions form a polyvalent metal salt with the -COO- group constituting the polycarboxylic acid. At this time, the -COO- group that forms a salt with the polyvalent metal ion refers to both the carboxyl group that has not been neutralized with the base and the -COO- group that has been neutralized with the base. In the case of the -COO- group that has been neutralized with the base, the polyvalent metal ions from the above-mentioned polyvalent metal compound are replaced and coordinated to form a polyvalent metal salt of the -COO- group.
[0950] Then, after the polyvalent metal salt is formed, a polyamine compound and a phosphorus compound or a salt thereof are further added to obtain a mixture. At this time, the polyvalent metal salt coordinated to the -COO- group also coordinates with the -PO- group in the phosphorus compound to form a -COO-polyvalent metal-OP- structure. In addition, an ionic bond is formed between the -NH2 group in the polyamine and the -PO- group in the phosphorus compound.
[0951] The mixture thus produced is applied as a gas barrier coating material to the inorganic layer 102 or to an intervening layer formed on the inorganic layer 102 and between the gas barrier layer 103 and the inorganic layer 102, and dried and cured to form the gas barrier layer 103. At this time, the polyvalent metal of the polyvalent metal salt constituting the -COO- group of the polycarboxylic acid forms a metal crosslink, the amino group constituting the polyamine forms an amide crosslink, and the -PO- group in the phosphorus compound and the amino group in the polyvalent metal or the polyamine form an ionic crosslink, so that the gas barrier layer 103 having excellent gas barrier properties can be obtained. A more detailed method for producing the gas barrier layer 103 will be described later.
[0952] From the viewpoint of improving the barrier properties, the thickness of the gas barrier layer 103 after drying and curing is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more.
[0953] From the viewpoint of reducing the thickness of the entire gas barrier laminate, the thickness of the gas barrier layer 103 after drying and curing is preferably 15 μm or less, more preferably 5 μm or less, and even more preferably 1 μm or less.
[0954] (Base material layer)
[0955] The substrate layer 101 may be a single layer or may be two or more layers. The shape of the substrate layer 101 is not limited, and examples thereof include a sheet or film shape, a tray, a cup, a hollow body, and the like.
[0956] As the material of the substrate layer 101, any material can be used without limitation as long as it can stably form the inorganic layer 102 on the substrate layer 101 and can coat the solution of the gas barrier coating material on the upper part of the inorganic layer 102. As the material of the substrate layer 101, for example, resins such as thermosetting resins and thermoplastic resins, organic materials such as paper; inorganic materials such as glass, pottery, ceramics, silicon oxide, silicon oxynitride, silicon nitride, concrete, aluminum, aluminum oxide, iron, copper, stainless steel and other metals; a substrate layer of a multilayer structure formed by a combination of organic materials or a combination of organic materials and inorganic materials, etc. Among them, for example, in the case of various film applications such as packaging materials and panels, it is preferred to use a plastic film of at least one selected from the group consisting of thermosetting resins and thermoplastic resins, or an organic material such as paper.
[0957] As the thermosetting resin, a known thermosetting resin can be used, for example, epoxy resin, unsaturated polyester resin, phenol resin, urea-melamine resin, polyurethane resin, silicone resin, polyimide, etc. can be mentioned.
[0958] As the thermoplastic resin, known thermoplastic resins can be used, for example, polyolefins (polyethylene, polypropylene, poly(4-methyl-1-pentene), poly(1-butene), etc.), polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyamides (nylon-6, nylon-66, poly(m-xylylene adipamide), etc.), polyvinyl chloride, polyimide, ethylene-vinyl acetate copolymer or its saponified product, polyvinyl alcohol, polyacrylonitrile, polycarbonate, polystyrene, ionomer, fluororesin, or mixtures thereof.
[0959] Among them, from the viewpoint of improving transparency, one or more resins selected from the group consisting of polypropylene, polyethylene terephthalate (PET), polyethylene naphthalate, polyamide, polyimide, and polybutylene terephthalate are preferred.
[0960] In addition, from the viewpoint of excellent pinhole resistance, breakage resistance, heat resistance, etc., one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate are preferred. From the same viewpoint, the base layer 101 is preferably a layer containing one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate, and more preferably a layer containing one or more resins therein.
[0961] In addition, when a hygroscopic material such as polyamide is used in the substrate layer 101, in the gas barrier layer stack, the substrate layer 101 absorbs moisture and swells, and the gas barrier performance under high humidity, the gas barrier performance after boiling treatment, and the gas barrier performance when filled with acidic contents are easily reduced. However, in the fourth embodiment, even when a hygroscopic material is used as the substrate layer 101, the reduction in the gas barrier performance of the gas barrier layer stack under high humidity and the gas barrier performance after boiling treatment can be appropriately suppressed.
[0962] Alternatively, the base layer 101 may be formed by stretching a film made of a thermosetting resin or a thermoplastic resin in at least one direction, preferably in two directions.
[0963] From the viewpoint of excellent transparency, rigidity and heat resistance, the substrate layer 101 is preferably a biaxially stretched film formed from one or more thermoplastic resins selected from the group consisting of polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide and polybutylene terephthalate, and is more preferably a biaxially stretched film formed from one or more thermoplastic resins selected from the group consisting of polyamide, polyethylene terephthalate and polybutylene terephthalate.
[0964] In addition, the surface of the base layer 101 may be coated with polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, acrylic resin, urethane resin, or the like.
[0965] In addition, the substrate layer 101 may be a substrate layer subjected to surface treatment in order to improve adhesion with the gas barrier layer 103. Specifically, the surface of the substrate layer 101 facing the gas barrier layer 103 may be subjected to surface activation treatment such as corona treatment, flame treatment, plasma treatment, or primer coating treatment.
[0966] From the viewpoint of obtaining good film properties, the thickness of the substrate layer 101 is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and is preferably 1000 μm or less, more preferably 500 μm or less, further preferably 300 μm or less.
[0967] (Inorganic layer)
[0968] Examples of the inorganic material constituting the inorganic material layer 102 include metals, metal oxides, metal nitrides, metal fluorides, and metal oxynitrides that can form a thin film having barrier properties.
[0969] As inorganic substances constituting the inorganic layer 102, for example, one or more of the single substances, oxides, nitrides, fluorides, or oxynitrides of periodic table 6A elements such as selenium and tellurium, etc., can be cited, for example. 2A group elements of the periodic table such as beryllium, magnesium, calcium, strontium, and barium; transition elements of the periodic table such as titanium, zirconium, ruthenium, hafnium, and tantalum; 2B group elements of the periodic table such as zinc; 3A group elements of the periodic table such as aluminum, gallium, indium, and thallium; 4A group elements of the periodic table such as silicon, germanium, and tin; and 6A group elements of the periodic table such as selenium and tellurium, etc.
[0970] It should be noted that in the fourth embodiment, the group name of the periodic table of elements concerning the inorganic substance layer 102 is expressed in the old CAS format.
[0971] Among the above-mentioned inorganic substances, one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum are preferred, and aluminum oxide is more preferred, from the viewpoint of excellent balance between barrier properties and cost.
[0972] It should be noted that silicon oxide may contain silicon monoxide and silicon monoxide in addition to silicon dioxide.
[0973] The inorganic layer 102 is formed of the above-mentioned inorganic substance. From the viewpoint of excellent balance between barrier properties and cost, the inorganic layer 102 preferably includes an aluminum oxide layer composed of aluminum oxide.
[0974] The inorganic layer 102 may be composed of a single inorganic layer or a plurality of inorganic layers. In addition, when the inorganic layer 102 is composed of a plurality of inorganic layers, they may be composed of the same type or different types of inorganic layers.
[0975] From the viewpoint of a balance between improved barrier properties and improved handleability, the thickness of the inorganic layer 102 is usually 1 nm or more, preferably 4 nm or more, and is usually 1000 nm or less, preferably 500 nm or less.
[0976] Here, the thickness of the inorganic substance layer 102 can be determined, for example, from an observation image obtained by a transmission electron microscope or a scanning electron microscope.
[0977] The method for forming the inorganic layer 102 is not limited. For example, the inorganic layer 102 can be formed on one or both sides of the substrate layer 101 by vacuum evaporation, ion plating, sputtering, chemical vapor deposition, physical vapor deposition, chemical vapor deposition (CVD), plasma CVD, sol-gel, etc. Among them, film formation under reduced pressure by sputtering, ion plating, chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma CVD, etc. is ideal. Therefore, it is predicted that chemically active molecular species containing silicon such as silicon nitride and silicon oxynitride react quickly, thereby improving the smoothness of the surface of the inorganic layer 102 and reducing pores. In order to quickly carry out these bonding reactions, it is ideal that the inorganic atoms and compounds are chemically active molecular species or atomic species.
[0978] Furthermore, from the viewpoint of improving the balance between the barrier properties and productivity of the gas barrier laminate, the inorganic substance layer 102 is preferably a vapor-deposited film.
[0979] From the perspective of improving the balance between the barrier properties and productivity of the gas barrier laminate, the inorganic layer 102 is a vapor-deposited film arranged on the substrate layer 101, or is a vapor-deposited film arranged on the intermediate layer when there is an intermediate layer between the substrate layer 101 and the inorganic layer 102, and is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum.
[0980] (Base coating)
[0981] A primer layer 104 ( Fig.14 ), by providing a primer layer 104, their adhesion can be further improved, and the barrier properties after steaming treatment can be further improved.
[0982] From the viewpoint of improving adhesion between the base layer 101 and the inorganic layer 102 , examples of the material of the primer layer 104 include one or more selected from the group consisting of polyurethane resins, polyester resins, oxazoline resins, and (meth)acrylic resins.
[0983] As polyurethane resins, various polyurethane resins, polyurethane polyurea resins and prepolymers thereof can be exemplified. As specific examples of such urethane resins, reaction products of diisocyanate components such as toluene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate and diol components such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexanedimethanol, bisphenol, polyester diol, polyether diol, polycarbonate diol, polyethylene glycol and the like; reaction products of urethane prepolymers having an isocyanate group at the end and amino compounds, aminosulfonates, polyhydroxycarboxylic acids, acidic sulfurous acids and the like can be cited; and the like.
[0984] In addition, from the viewpoint of improving the barrier properties after the retorting treatment and the adhesion between the substrate layer 101 and the inorganic layer 102, it is also preferred that the polyurethane resin in the primer layer 104 is composed of a polyurethane resin having an aromatic ring structure in the main chain. The polyurethane resin having an aromatic ring structure in the main chain can be obtained as a water-dispersible polyurethane resin by, for example, reacting a polyol, an organic polyisocyanate, and a chain extender. In this way, an aromatic ring structure can be introduced into the main chain of the polyurethane resin.
[0985] As the polyurethane resin having an aromatic ring structure in the main chain, more specifically, the polyurethane resin described in JP-A-2018-171827 can be used.
[0986] In addition, in the above-mentioned water-dispersible polyurethane resin, a cross-linking agent may be used in combination from the viewpoint of improving heat resistance, water resistance, hydrolysis resistance, etc. The cross-linking agent may be an external cross-linking agent added as a third component to the water-dispersible polyurethane resin, or an internal cross-linking agent that preliminarily introduces reaction points capable of forming a cross-linked structure into the molecular structure of the water-dispersible polyurethane resin.
[0987] As a crosslinking agent, a compound having an isocyanate group, an oxazoline group, a carbodiimide group, an epoxy group, a melamine resin, and a silanol group can be suitably used, and a compound having a carbodiimide group is more suitable. In addition, when a compound having a carbodiimide group is used as a crosslinking agent, the amount of the compound having a carbodiimide group added is preferably 0.1 to 3.0 mol, more preferably 0.2 to 2.0 mol, and even more preferably 0.3 to 1.0 mol relative to 1.0 mol of the carboxyl group in the polyurethane resin.
[0988] Various polyester resins and their modified products can be exemplified as the polyester resin used in the primer layer 104. Specific examples of such polyester resins include reaction products of polycarboxylic acid components such as terephthalic acid, phthalic acid, isophthalic acid, trimellitic acid, pyromellitic acid, 2-sulfoisophthalic acid, 5-sulfoisophthalic acid, adipic acid, sebacic acid, succinic acid, and dodecanedioic acid with diol components such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexanedimethanol, and bisphenol, as well as modified products based on acrylic resins, epoxy resins, and the like.
[0989] When an oxazoline resin is used for the primer layer 104 , the primer layer 104 is preferably composed of an oxazoline-based resin composition containing an aqueous polymer having an oxazoline group, an aqueous (meth)acrylic resin, and an aqueous polyester resin.
[0990] The oxazoline resin composition comprises, for example, an aqueous polymer containing an oxazoline group having an oxazoline group content of 6.0 to 9.0 mmol / g, an aqueous (meth)acrylic resin having a carboxyl group content of 0.5 to 3.5 mmol / g, and an aqueous polyester resin having a carboxyl group content of 0.5 to 2.0 mmol / g.
[0991] In addition, taking the total amount of the aqueous polymer containing an oxazoline group, the aqueous (meth) acrylic resin and the aqueous polyester resin as 100 mass%, the oxazoline-based resin composition contains, for example, 10 to 55 mass% of an aqueous polymer containing an oxazoline group, 10 to 80 mass% of an aqueous (meth) acrylic resin, and 10 to 80 mass% of an aqueous polyester resin.
[0992] In the oxazoline resin composition, for example, the ratio of the number of moles of oxazoline groups to the number of moles of carboxyl groups [expressed by the ratio of the number of moles of oxazoline groups (xmmol) to the number of moles of carboxyl groups (ymmol) (x / y)×100 [mol%]] is 150 to 420 mol%.
[0993] As the oxazoline resin used in the primer layer 104 , more specifically, the oxazoline resin described in International Publication No. 2016 / 186074 can be used.
[0994] From the viewpoint of obtaining good adhesion, the thickness of the primer layer 104 is preferably 0.001 μm or more, more preferably 0.005 μm or more, further preferably 0.01 μm or more, further more preferably 0.05 μm or more, further preferably 0.1 μm or more, and further preferably 0.2 μm or more.
[0995] From an economical point of view, the thickness of the primer layer 104 is preferably 1.0 μm or less, more preferably 0.6 μm or less, further preferably 0.5 μm or less, and may be, for example, 0.1 μm or less or 0.05 μm or less.
[0996] (Adhesive layer)
[0997] The gas barrier layered product may further include an adhesive layer. In addition, the primer layer 104 is excluded from the adhesive layer.
[0998] The adhesive layer is provided, for example, between the gas barrier layer 103 and the upper layer of the gas barrier layer 103. In addition, when the upper layer is formed by a plurality of layers, an adhesive layer may be provided between the plurality of layers. Here, the upper layer of the gas barrier layer 103 refers to a layer stacked on the surface of the gas barrier layer 103 opposite to the surface facing the inorganic layer 102.
[0999] The adhesive layer may contain a known adhesive. As the adhesive, there may be mentioned a laminated adhesive composed of an organic titanium resin, a polyethyleneimine resin, a carbamate resin, an epoxy resin, an acrylic resin, a polyester resin, a resin containing an oxazoline group, a modified silicone resin, an alkyl titanate, a polyester polybutadiene, or a one-component or two-component polyol and polyisocyanate, an aqueous carbamate, an ionomer, etc. Alternatively, an aqueous adhesive having an acrylic resin, a vinyl acetate resin, a carbamate resin, a polyester resin, etc. as the main raw material may be used.
[1000] In addition, other additives such as a curing agent and a silane coupling agent may be added to the adhesive depending on the application of the gas barrier layered product 100. When the gas barrier layered product is used for hot water treatment such as retorting, from the viewpoint of heat resistance and water resistance, a dry lamination adhesive represented by a polyurethane adhesive is preferred, and a solvent-based two-component curing polyurethane adhesive is more preferred.
[1001] (Method for producing gas barrier laminate)
[1002] In the fourth embodiment, the method for manufacturing the gas barrier laminate 100 includes, for example, the following steps: a step of preparing a substrate layer 101; a step of forming an inorganic layer 102 on the substrate layer 101; and a step of forming a gas barrier layer 103 on the upper portion of the substrate layer 101 on which the inorganic layer 102 is formed. In addition, after the step of forming the inorganic layer 102 and before the step of forming the gas barrier layer 103, a step of forming a primer layer 104 on the inorganic layer 102 may be further included.
[1003] In the step of forming the inorganic layer 102 on the base layer 101 , for example, the above-described method for forming the inorganic layer 102 can be used.
[1004] The process of forming the gas barrier layer 103 includes, for example, the following steps: applying the pre-cured mixture as a gas barrier coating material to the inorganic layer 102, followed by drying, thereby obtaining a coating layer; and heating the above-mentioned coating layer to allow the carboxyl groups contained in the polycarboxylic acid and the amino groups contained in the polyamine compound to undergo a dehydration condensation reaction, thereby forming a gas barrier layer 103 having an amide bond.
[1005] The method for applying the gas barrier coating material to the inorganic layer 102 is not limited, and a common method can be used. For example, a method of coating using a known coating machine such as a Meyer rod coater, an air knife coater, a direct gravure coater, a gravure offset printer, a curved gravure coater, a reverse gravure printer, and a jet nozzle type gravure coater, a top feed reverse coater, a bottom feed reverse coater, and a nozzle feed reverse coater, a reverse roll coater, a five-roll coater, a lip coater, a rod coater, a rod reverse coater, a die coater, etc.
[1006] From the viewpoint of improving the barrier performance of the obtained gas barrier layered product, the coating amount (wet thickness) is preferably 0.05 μm, more preferably 1 μm or more.
[1007] In addition, from the viewpoint of suppressing warping of the obtained gas barrier layered product and more effectively carrying out the dehydration condensation reaction between the -COO- group contained in the polycarboxylic acid and the amino group contained in the polyamine compound, the wet thickness is preferably 300 μm or less, more preferably 200 μm or less, and further preferably 100 μm or less.
[1008] As for drying and heat treatment, heat treatment may be performed after drying, or drying and heat treatment may be performed simultaneously.
[1009] As for the method of drying and heating treatment, there is no limitation as long as the effect of the present invention can be obtained, and any method that can cure the gas barrier coating material or heat the cured gas barrier coating material can be used. For example, there can be cited methods based on convection heat transfer such as ovens and dryers; methods based on conduction heat transfer such as heating rollers; methods based on radiation heat transfer using electromagnetic waves such as infrared, far-infrared and near-infrared heaters; and methods based on internal heating such as microwaves. As a device for drying and heating treatment, from the viewpoint of manufacturing efficiency, it is preferred to use a device that can perform both drying and heating treatment. Specifically, from the viewpoint of being able to be used for various purposes such as drying, heating, and annealing, it is preferred to use a hot air oven, and from the viewpoint of excellent heat conduction efficiency to the film, it is preferred to use a heating roller. In addition, the methods for drying and heating treatment can also be appropriately combined. Specifically, a hot air oven and a heating roller can be used together. For example, when the gas barrier coating material is dried by a hot air oven and then heated by a heating roller, the time of the heating treatment process is shortened, which is preferred from the viewpoint of manufacturing efficiency. In addition, it is preferred to perform the drying and heating treatment only using a hot air oven.
[1010] Regarding the heating treatment conditions, for example, the heating treatment temperature is 80 to 250° C., and the heating treatment time is 1 second to 10 minutes; preferably, the heating treatment temperature is 120 to 240° C., and the heating treatment time is 1 second to 1 minute; more preferably, the heating treatment temperature is 170 to 230° C., and the heating treatment time is 1 second to 30 seconds; and further preferably, the heating treatment temperature is 200 to 220° C., and the heating treatment time is 1 second to 10 seconds. Furthermore, by using a heating roller in combination as described above, the heating treatment can be performed in a short time.
[1011] It should be noted that, from the viewpoint of effectively carrying out the dehydration condensation reaction between the -COO- group contained in the polycarboxylic acid and the amino group contained in the polyamine compound, it is important to adjust the heat treatment temperature and the heat treatment time according to the wet thickness of the gas barrier coating material. By selecting an appropriate heat treatment temperature and heat treatment time, an appropriate crosslinking structure can be formed.
[1012] By drying and heat treating the gas barrier coating material, the carboxyl groups of the polycarboxylic acid react with the polyamine and the polyvalent metal compound to form covalent bonds and ion crosslinks, thereby forming a gas barrier layer 103 having good gas barrier properties even after retorting.
[1013] In the fourth embodiment, the gas barrier layered product has excellent gas barrier properties and can be suitably used as packaging materials, particularly packaging materials for food that requires high gas barrier properties, and various packaging materials for medical, industrial, and daily groceries purposes.
[1014] The gas barrier laminate according to the fourth embodiment can be suitably used as, for example, a vacuum heat insulating film requiring high barrier performance, a sealing film for sealing an electroluminescent element, a solar cell, or the like, and the like.
[1015] In the fourth embodiment, a specific example of a laminate structure including a gas barrier layered product is shown below.
[1016] (Laminate Structure Example 1) Base material layer 101 (PET base material) / inorganic material layer 102 (aluminum oxide vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyolefin layer
[1017] (Laminate Structure Example 2) Base material layer 101 (PET base material) / primer layer 104 / inorganic material layer 102 (aluminum oxide vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyolefin layer
[1018] (Laminate structure example 3) Base material layer 101 (PET base material) / inorganic material layer 102 (alumina vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyamide layer / adhesive layer / polyolefin layer
[1019] (Laminate structure example 4) Base material layer 101 (PET base material) / primer layer 104 / inorganic material layer 102 (aluminum oxide vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyamide layer / adhesive layer / polyolefin layer
[1020] Here, by including a polyolefin layer composed of polyolefins such as polyethylene, polypropylene, poly(4-methyl-1-pentene), and poly(1-butene) in the laminate structure, the pinhole resistance, breakage resistance, and heat resistance of the gas barrier laminate can be improved, and the reduction in gas barrier performance under high humidity and after boiling treatment can be further suppressed.
[1021] <Fifth Implementation Method>
[1022] Fig.15 It is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the fifth embodiment. Fig.15 The gas barrier laminate 100 shown includes a substrate layer 101, a gas barrier layer 103 provided on at least one surface of the substrate layer 101, and an inorganic layer 102 provided between the substrate layer 101 and the gas barrier layer 103. The gas barrier layer 103 is composed of a cured product of a mixture containing a polycarboxylic acid, a polyamine compound, and a polyvalent metal compound.
[1023] The specific structure of each layer will be described later.
[1024] In the gas barrier laminate 100 , the base layer 101 , the inorganic layer 102 , and the gas barrier layer 103 are laminated in this order, and the gas barrier layer 103 is composed of a cured product of the above mixture. Therefore, the gas barrier laminate 100 has an excellent balance between barrier properties and productivity.
[1025] More specifically, the gas barrier laminate 100 has excellent barrier properties such as oxygen barrier property and water vapor barrier property after the steaming treatment. In addition, in the gas barrier laminate 100, the gas barrier layer 103 is composed of a cured product of the above-mentioned mixture, so even if the curing time (specifically, the heating treatment time) when obtaining the gas barrier layer 103 is short, for example, a gas barrier laminate 100 with excellent barrier properties can be obtained.
[1026] Fig.16 It is a cross-sectional view schematically showing another configuration example of the gas barrier layered product. Fig.16 The basic structure of the gas barrier laminate 110 shown in FIG. Fig.15 The gas barrier laminate 100 described above is similar, but is different in that it further includes a primer layer 104 provided between the base layer 101 and the inorganic substance layer 102 .
[1027] The gas barrier layer 110 can also achieve the same effects as those of the gas barrier layer 100. In addition, in the gas barrier layer 110, by providing the primer layer 104 between the base layer 101 and the inorganic layer 102, the adhesion between the base layer 101 and the inorganic layer 102 can be further improved.
[1028] Hereinafter, the configuration of the layers included in the gas barrier layered product will be described in more detail. First, the gas barrier layer 103 will be described.
[1029] (Gas barrier layer)
[1030] The gas barrier layer 103 is composed of a cured product of a mixture containing a polycarboxylic acid, a polyamine compound, and a polyvalent metal compound. More specifically, the gas barrier layer 103 is a film (gas barrier film 10) composed of the cured product.
[1031] More specifically, the gas barrier layer 103 can be obtained, for example, as follows: after coating the pre-cured mixture, i.e., the gas barrier coating material, on a layer such as the inorganic layer 102 arranged immediately below the gas barrier layer 103, drying and heat treating the mixture to cure the gas barrier coating material, the gas barrier coating material is obtained.
[1032] In the infrared absorption spectrum of the gas barrier layer 103, at 1300 cm -1 Above 1490cm -1The maximum peak height of the absorbance in the following range is defined as α and 1690 cm -1 Above 1780cm -1 When the maximum peak height of the absorbance in the following range is set to γ, from the viewpoint of liquid stability of the gas barrier coating material before coating, the ratio of free carboxyl groups to the NH3 complex represented by γ / α is preferably 0.00 or more, more preferably 0.01 or more, and further preferably 0.02 or more.
[1033] In addition, from the perspective of improving the barrier properties of the gas barrier layer 103 obtained after coating, the above-mentioned γ / α is preferably less than 1.00, more preferably less than 0.80, further preferably less than 0.60, further more preferably less than 0.40, further preferably less than 0.20, and further preferably less than 0.10.
[1034] In the infrared absorption spectrum of the gas barrier layer 103, the wavelength at 1493 cm -1 Above 1780cm -1 The total peak area within the following absorption band range is defined as A, and the peak area at 1598 cm -1 Above 1690cm -1 The total peak area within the following absorption band range is defined as B, and the peak area at 1690 cm -1 Above 1780cm -1 The total peak area within the following absorption band range is defined as C, and the peak area at 1493 cm -1 Above 1598cm -1 When the total peak area in the following absorption band range is defined as D, preferred examples of the area ratio are shown below.
[1035] In the infrared absorption spectrum of the gas barrier layer 103, from the viewpoint of further improving the gas barrier performance after the steaming treatment, the area ratio of the amide bond represented by B / A is preferably 0.200 or more, more preferably 0.250 or more, further preferably 0.270 or more, further more preferably 0.290 or more, and further preferably 0.310 or more.
[1036] From the viewpoint of further improving the balance between barrier properties and productivity, the area ratio of the amide bonds represented by B / A is preferably 0.370 or less, more preferably 0.360 or less, and even more preferably 0.350 or less.
[1037] In the infrared absorption spectrum of the gas barrier layer 103, from the viewpoint of further improving the gas barrier performance after the steaming treatment, the area ratio of carboxylic acid represented by C / A is preferably 0.150 or less, more preferably 0.100 or less, further preferably 0.080 or less, and further more preferably 0.060 or less.
[1038] The lower limit of the area ratio of the carboxylic acid represented by C / A is not limited, and may be, for example, 0.000 or more, or, for example, 0.0001 or more.
[1039] In the infrared absorption spectrum of the gas barrier layer 103 , from the viewpoint of further improving the balance between barrier properties and productivity, the area ratio of the carboxylate represented by D / A is preferably 0.580 or more, more preferably 0.600 or more.
[1040] From the viewpoint of further improving the gas barrier performance after retorting, D / A is preferably 0.800 or less, more preferably 0.720 or less, further preferably 0.700 or less, and still more preferably 0.680 or less.
[1041] In addition, from the viewpoint of achieving a more ideal balance between the productivity and barrier properties of the gas barrier layered product, it is also preferred that the area ratio of the amide bond represented by B / A is greater than 0.200 and less than 0.370, the area ratio of the carboxylic acid represented by C / A is less than 0.150, and the area ratio of the carboxylate represented by D / A is greater than 0.580 and less than 0.800.
[1042] In the infrared absorption spectrum of the gas barrier layer 103, from the viewpoint of improving the barrier properties, the area ratio of the carboxylate represented by D / A relative to the area ratio of the amide bond represented by B / A is preferably 1.2 or more, more preferably 1.6 or more, and even more preferably 1.8 or more.
[1043] In addition, from the viewpoint of improving the barrier properties after retorting, the area ratio of the carboxylate represented by D / A relative to the area ratio of the amide bond represented by B / A is preferably 4.0 or less, more preferably 3.5 or less, further more preferably 3.0 or less, and further preferably 2.5 or less.
[1044] Here, in the gas barrier layer 103, at 1700 cm -1 The absorption of νC=O based on unreacted carboxylic acid in the near visible infrared absorption spectrum is at 1630-1685 cm -1 Nearby, absorption based on νC=O of the amide bond as a cross-linked structure can be seen at 1540~1560cm -1 The absorption of νC=O based on carboxylate can be seen nearby, at 1300~1490cm -1 Absorption of δN-H based on ammonia forming a complex is observed nearby.
[1045] It is believed that 1300cm in the infrared absorption spectrum -1 Above 1490cm -1The maximum peak height α of the absorbance in the following range is an indicator of the amount of ammonia present in the complex formed, 1690 cm -1 Above 1780cm -1 The maximum peak height γ in the following range represents an indicator of the amount of free, ie, unreacted, carboxylic acid present.
[1046] In the fifth embodiment, specifically, the maximum peak heights α and γ can be measured by the following steps. That is, a 1 cm × 3 cm sample for measurement is cut out from the gas barrier layer 103. Then, an infrared absorption spectrum of the surface of the gas barrier layer 103 is obtained by infrared total reflection measurement (ATR method). In the obtained infrared absorption spectrum, a straight line is connected between 900 cm -1 The absorbance at 1900 cm -1 The line formed by the absorbance is used as the baseline, and the maximum peak height within the range of each absorbance is calculated.
[1047] In addition, it is believed that the 1493 cm -1 Above 1780cm -1 The total peak area A in the following absorption band range is an indicator of the total amount of carboxylic acid, amide bond and carboxylate: 1598 cm -1 Above 1690cm -1 The total peak area B within the following absorption band range is an indicator of the amount of amide bonds present. -1 Above 1780cm -1 The total peak area C in the following absorption band range is an indicator of the amount of unreacted carboxylic acid present: 1493 cm -1 Above 1598cm -1 The total peak area D within the following absorption band range is an indicator of the amount of carboxylate present.
[1048] In the fifth embodiment, specifically, the total peak areas A to D can be measured by the following procedure.
[1049] First, a 1 cm×3 cm measurement sample is cut out from the gas barrier layer 103. Next, an infrared absorption spectrum of the surface of the gas barrier layer 103 is obtained by infrared total reflection measurement (ATR method). Based on the obtained infrared absorption spectrum, the total peak areas A to D are calculated by the following steps (1) to (4).
[1050] (1) 1780cm -1 With 1493cm -1 The absorbance of 1493cm -1 Above 1780cm -1The area surrounded by N in the absorption spectrum within the following absorption band is taken as the total peak area A.
[1051] (2) From 1690cm -1 Draw a straight line (O) vertically from the absorbance (Q) of N and O, and take the intersection of N and O as P. -1 Draw a straight line (S) vertically from the absorbance (R) of N, and take the intersection of N and S as T. -1 Above 1690cm -1 The area enclosed by the absorption spectrum within the following absorption band and the straight line S, point T, straight line N, point P, straight line O, absorbance Q, and absorbance R is taken as the total peak area B.
[1052] (3) will be 1690cm -1 Above 1780cm -1 The absorption spectrum within the following absorption band range and the area surrounded by absorbance Q, straight line O, point P, and straight line N are taken as the total peak area C.
[1053] (4) will be 1493cm -1 Above 1598cm -1 The absorption spectrum within the following absorption band range and the area surrounded by absorbance R, straight line S, point T, and straight line N are taken as the total peak area D.
[1054] Next, the area ratios B / A, C / A, and D / A are obtained from the areas obtained by the above method.
[1055] It should be noted that, in the fifth embodiment, for the measurement of infrared absorption spectrum (infrared total reflection measurement: ATR method), for example, an IRT-5200 device manufactured by JASCO Corporation can be used, with a PKM-GE-S (germanium) crystal installed, at an incident angle of 45 degrees, room temperature, and a resolution of 4 cm -1 , the cumulative number of times is 100 times.
[1056] The maximum peak heights α and γ of the gas barrier layer 103, and the area ratio of the amide bonds represented by B / A, the area ratio of the carboxylic acid represented by C / A, and the area ratio of the carboxylate represented by D / A can be controlled by appropriately adjusting the production conditions of the gas barrier layer 103. Specifically, as factors for controlling the maximum peak heights α and γ of the gas barrier layer 103, and the area ratio of the amide bonds represented by B / A, the area ratio of the carboxylic acid represented by C / A, and the area ratio of the carboxylate represented by D / A, the mixing ratio of the polycarboxylic acid, the polyamine compound, and the polyvalent metal compound, the method for preparing the mixture before curing, the method, temperature, and time of heating the mixture, etc. can be cited.
[1057] Next, components contained in the mixture (gas barrier coating material) before curing will be described.
[1058] (Polycarboxylic Acid)
[1059] Polycarboxylic acid is a compound having two or more carboxyl groups in the molecule. Specifically, homopolymers of α,β-unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, 3-hexenedioic acid, or copolymers thereof may be cited. In addition, copolymers of the above-mentioned α,β-unsaturated carboxylic acids with esters such as ethyl esters, olefins such as ethylene, etc. may also be mentioned.
[1060] Among them, preferred are homopolymers of acrylic acid, methacrylic acid, itaconic acid, fumaric acid, crotonic acid, and cinnamic acid, or copolymers thereof; more preferred are one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid; further preferred are at least one polymer selected from polyacrylic acid and polymethacrylic acid; and even more preferred are at least one polymer selected from homopolymers of acrylic acid and homopolymers of methacrylic acid.
[1061] Here, in the fifth embodiment, the polyacrylic acid includes both homopolymers of acrylic acid and copolymers of acrylic acid and other monomers. In the case of copolymers of acrylic acid and other monomers, the polyacrylic acid contains generally 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from acrylic acid in 100% by mass of the polymer.
[1062] In the fifth embodiment, the polymethacrylic acid includes both homopolymers of methacrylic acid and copolymers of methacrylic acid and other monomers. In the case of copolymers of methacrylic acid and other monomers, the polymethacrylic acid contains structural units derived from methacrylic acid in an amount of usually 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more, based on 100% by mass of the polymer.
[1063] The polycarboxylic acid is a polymer obtained by polymerizing carboxylic acid monomers. The molecular weight of the polycarboxylic acid is preferably 500 to 2,500,000, more preferably 5,000 to 2,000,000, more preferably 10,000 to 1,500,000, and even more preferably 100,000 to 1,200,000, from the viewpoint of excellent balance between gas barrier properties and handling properties.
[1064] Here, in the fifth embodiment, the molecular weight of the polycarboxylic acid is a weight average molecular weight calculated as polyethylene oxide, and can be measured using gel permeation chromatography (GPC).
[1065] At least a portion of the polycarboxylic acid can be neutralized with a volatile base. By neutralizing the polycarboxylic acid with a volatile base, the occurrence of gelation can be suppressed when a polyvalent metal compound, a polyamine compound and the polycarboxylic acid are mixed. Therefore, in the polycarboxylic acid, from the viewpoint of preventing gelation, it is preferred to prepare a partially neutralized or completely neutralized product of the carboxyl group with a volatile base. The neutralized product can be obtained by partially or completely neutralizing the carboxyl group of the polycarboxylic acid with a volatile base, that is, preparing the carboxyl group of the polycarboxylic acid partially or completely into a carboxylate. Thus, gelation can be prevented when a polyamine compound or a polyvalent metal compound is added.
[1066] The partially neutralized product can be prepared by adding a volatile base to an aqueous solution of a polycarboxylic acid polymer, and the desired neutralization degree can be obtained by adjusting the amount ratio of the polycarboxylic acid to the volatile base. In the fifth embodiment, from the viewpoint of fully suppressing gelation caused by the neutralization reaction with the amino group of the polyamine compound, the neutralization degree of the polycarboxylic acid obtained by the volatile base is preferably 70 to 300 equivalents, more preferably 90 to 250 equivalents, and further preferably 100 to 200 equivalents.
[1067] As the volatile base, any water-soluble base can be used.
[1068] Examples of the volatile base include ammonia, morpholine, alkylamines, tertiary amines such as 2-dimethylaminoethanol, N-methylmorpholine, ethylenediamine, and triethylamine, or aqueous solutions thereof, or mixtures thereof. From the viewpoint of obtaining good gas barrier properties, aqueous ammonia solutions are preferred.
[1069] (Polyamine compounds)
[1070] The mixture before curing contains a polyamine compound. By containing a polyamine compound, the barrier properties of the obtained gas barrier material can be improved.
[1071] The polyamine compound is a compound having two or more amino groups in the main chain, side chain or terminal, and is preferably a polymer. Specifically, aliphatic polyamines such as polyallylamine, polyvinylamine, polyethyleneimine, poly(propyleneimine) and the like; polyamides having amino groups in the side chains such as polylysine and polyarginine; and the like can be cited. In addition, a polyamine obtained by modifying a part of the amino groups may also be used.
[1072] From the viewpoint of obtaining good gas barrier properties, the polyamine compound preferably contains polyethyleneimine, and more preferably polyethyleneimine.
[1073] From the viewpoint of excellent balance between gas barrier properties and handleability, the number average molecular weight of the polyamine compound is preferably 50 to 2,000,000, more preferably 100 to 1,000,000, further preferably 1,500 to 500,000, further more preferably 1,500 to 100,000, further more preferably 1,500 to 50,000, further more preferably 3,500 to 20,000, further more preferably 5,000 to 15,000, further more preferably 7,000 to 12,000.
[1074] Here, in the fifth embodiment, the molecular weight of the polyamine compound can be measured using a boiling point elevation method or a viscosity method.
[1075] From the viewpoint of further improving the gas barrier performance after the retort treatment, (the number of moles of amino groups contained in the polyamine compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.20 or more, more preferably 0.25 or more, further preferably 0.30 or more, further more preferably 0.35 or more, and further preferably 0.40 or more.
[1076] From the same point of view, (the number of moles of amino groups contained in the polyamine compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.90 or less, more preferably 0.85 or less, further preferably 0.80 or less, further more preferably 0.75 or less, and further preferably 0.70 or less.
[1077] Although the detailed reason is unclear, it is believed that by forming a dense structure with good balance between amide crosslinking (which is formed by amino groups constituting polyamine compounds) and metal crosslinking (which is formed by polyvalent metals constituting salts of polycarboxylic acids and polyvalent metals), a gas barrier layer 103 with excellent gas barrier performance after steaming treatment and a gas barrier laminate having the same can be obtained.
[1078] (Polyvalent Metal Compounds)
[1079] The polyvalent metal compound specifically refers to metals and metal compounds belonging to Groups 2 to 13 of the periodic table, and more specifically, bivalent or higher metals such as magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), and aluminum (Al), and oxides, hydroxides, halides, carbonates, phosphates, phosphites, hypophosphites, sulfates, or sulfites of these metals. From the viewpoints of water resistance, impurities, etc., metal oxides or metal hydroxides are preferred.
[1080] From the viewpoint of further improving the gas barrier performance after retorting, the divalent or higher metal in the polyvalent metal compound is preferably one or more metals selected from the group consisting of Zn, Ca, Mg, Ba and Al, and more preferably Zn.
[1081] From the same viewpoint, the polyvalent metal compound is preferably a compound of one or more divalent or higher metals selected from the group consisting of Zn, Ca, Mg, Ba and Al, and more preferably a Zn compound.
[1082] From the same viewpoint, the polyvalent metal compound is preferably one or more compounds selected from the group consisting of oxides such as magnesium oxide, calcium oxide, barium oxide, zinc oxide, and magnesium hydroxide, and hydroxides such as calcium hydroxide, barium hydroxide, and zinc hydroxide, more preferably at least one of zinc oxide and zinc hydroxide, and further preferably zinc oxide.
[1083] In the fifth embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.10 or more, more preferably 0.13 or more, further preferably 0.15 or more, further more preferably 0.18 or more, further preferably 0.20 or more, further preferably 0.25 or more, and further preferably 0.28 or more.
[1084] From the same point of view, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the mixture) is preferably 0.80 or less, more preferably 0.70 or less, further preferably 0.60 or less, further more preferably 0.55 or less, and further preferably 0.50 or less.
[1085] In the fifth embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of the amino group derived from the polyamine compound in the mixture) is preferably 0.25 or more, more preferably 0.35 or more, and even more preferably 0.40 or more.
[1086] From the same viewpoint, (the number of moles of the polyvalent metal compound in the mixture) / (the number of moles of amino groups derived from the polyamine compound in the mixture) is preferably 0.75 or less, more preferably 0.65 or less, further preferably 0.60 or less, and further more preferably 0.55 or less.
[1087] The mixture before curing may contain components other than the above components.
[1088] For example, the mixture preferably further comprises carbonate ammonium salt. Carbonate ammonium salt is a substance added to make the polyvalent metal compound into a state of carbonate polyvalent metal ammonium complex, thereby improving the solubility of the polyvalent metal compound and preparing a uniform solution containing the polyvalent metal compound. By making the mixture before solidification contain carbonate ammonium salt, the dissolution amount of the polyvalent metal compound can be increased, and as a result, the mixture with the polyvalent metal compound can be made more uniform.
[1089] Examples of the carbonate-based ammonium salt include ammonium carbonate and ammonium hydrogen carbonate. Ammonium carbonate is preferred because it is easily volatilized and is unlikely to remain in the obtained gas barrier layer.
[1090] From the viewpoint of further improving the solubility of the polyvalent metal compound, (the number of moles of the carbonate-based ammonium salt in the mixture) / (the number of moles of the polyvalent metal compound in the mixture) is preferably greater than 0.05, more preferably greater than 0.10, further preferably greater than 0.25, further more preferably greater than 0.50, and further preferably greater than 0.75.
[1091] In addition, from the viewpoint of further improving the coating properties of the gas barrier coating material, (the number of moles of carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of polyvalent metal compound in the gas barrier coating material) is preferably 10.0 or less, more preferably 5.0 or less, further preferably 2.0 or less, and further more preferably 1.5 or less.
[1092] Furthermore, from the viewpoint of suppressing the generation of depressions when the mixture is applied as a gas barrier coating material, the mixture before curing preferably further contains a surfactant.
[1093] When the solid content of the mixture as a whole is 100% by mass, the amount of the surfactant added is preferably 0.01 to 3% by mass, and more preferably 0.01 to 1% by mass.
[1094] Examples of the surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. From the viewpoint of obtaining good coating properties, nonionic surfactants are preferred, polyoxyalkylene alkyl ethers are more preferred, and polyoxyethylene alkyl ethers are still more preferred.
[1095] Examples of the nonionic surfactant include polyoxyalkylene alkyl aryl ethers, polyoxyalkylene alkyl ethers, polyoxyalkylene fatty acid esters, sorbitan fatty acid esters, silicone-based surfactants, acetylene alcohol-based surfactants, and fluorine-containing surfactants.
[1096] Examples of the polyoxyalkylene alkyl aryl ethers include polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene dodecylphenyl ether, and the like.
[1097] Examples of the polyoxyalkylene alkyl ethers include polyoxyethylene alkyl ethers such as polyoxyethylene...
Claims
1. A gas barrier layered product comprising a substrate layer, a gas barrier layer provided on at least one surface of the substrate layer, and an inorganic layer provided between the substrate layer and the gas barrier layer, The composition ratio of Zn measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is 1 to 10 atomic %. In the case where the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, 64 ZnPO4H - The mass peak intensity is set as I( 64 ZnPO4H - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - )hour, I( 64 ZnPO4H - ) / I(C3H3O2 - ) is 6×10 -4 Above 5×10 -2 the following, The composition ratio of N measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is greater than 0 atomic % and less than 12 atomic %, In the case where the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, CN - The mass peak intensity is set as I(CN - )hour, I(CN - ) / I(C3H3O2 - ) is greater than 0 and less than 2.
2. The gas barrier layered product according to claim 1, wherein In the case where the gas barrier layer is subjected to the time-of-flight secondary ion mass spectrometry, PO2 - The mass peak intensity is set as I(PO2 - ) and PO3 - The mass peak intensity is set as I(PO3 - )hour, (I(PO2 - )+I(PO3 - )) / I(C3H3O2 - ) has a value of 0.02 or more and 5 or less.
3. The gas barrier layered product according to claim 1 or 2, wherein: The I(PO2 - ) and the I(PO3 - ) intensity ratio, that is, I(PO2 - ) / I(PO3 - ) has a value of 0.05 or more and 1 or less.
4. The gas barrier layered product according to any one of claims 1 to 3, wherein The gas barrier layer is composed of a cured product of a mixture containing at least a polycarboxylic acid, Zn, and a phosphorus compound containing one or more -P-OH groups or a salt thereof.
5. The gas barrier layered product according to claim 4, wherein The concentration of P atoms of the phosphorus compound or its salt in the mixture is 5×10 -4 mol or more and 0.3 mol or less.
6. The gas barrier layered product according to claim 4 or 5, wherein: The mixture also includes a polyamine.
7. The gas barrier layered product according to claim 6, wherein: The polyamine is polyethyleneimine.
8. The gas barrier layered product according to any one of claims 4 to 7, wherein The polycarboxylic acid includes one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.
9. The gas barrier layered product according to any one of claims 1 to 8, wherein The gas barrier layer has a thickness of 0.05 μm or more and 10 μm or less.
10. A gas barrier layered product comprising a substrate layer, a gas barrier layer provided on at least one surface of the substrate layer, and an inorganic layer provided between the substrate layer and the gas barrier layer, When the gas barrier layer was subjected to time-of-flight secondary ion mass spectrometry, PO2 - The mass peak intensity is set as I(PO2 - ), PO3 - The mass peak intensity is set as I(PO3 - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - ), {I(PO2 - )+I(PO3 - )} / I(C3H3O2 - ) is 0.02 to 5, The gas barrier layer contains one or more metal elements selected from the group consisting of Zn, Ca, Mg, Ba and Al, and the composition ratio of the metal elements in the gas barrier layer determined by performing X-ray photoelectron spectroscopy on the gas barrier layer is 1 to 15 atomic %.
11. The gas barrier layered product according to claim 10, wherein When the gas barrier layer was subjected to time-of-flight secondary ion mass spectrometry, CN - The mass peak intensity is set as I(CN - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - ), I(CN - ) / I(C3H3O2 - ) value is less than 2.
12. The gas barrier layered product according to claim 10 or 11, wherein In the absorption spectrum obtained by measuring the gas barrier layer by infrared spectroscopy using a total reflection measurement method, In will 1493cm -1 Above 1780cm -1 The total peak area within the following absorption band range is defined as A and the peak area at 1493 cm -1 Above 1598cm -1 When the total peak area in the following absorption band range is defined as D, the area ratio D / A is 0.5 or more.
13. The gas barrier layered product according to any one of claims 10 to 12, wherein The inorganic layer is in contact with the substrate layer, or a primer layer is provided between the inorganic layer and the substrate layer.
14. The gas barrier layered product according to any one of claims 10 to 13, wherein The inorganic layer includes one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide, and aluminum.
15. The gas barrier layered product according to any one of claims 10 to 14, wherein The thickness of the gas barrier layer is 0.01 to 15 μm.
16. The gas barrier layered product according to any one of claims 10 to 15, wherein Furthermore, a sealant layer is provided on the surface of the gas barrier layer opposite to the inorganic layer.
17. The gas barrier layered product according to claim 16, wherein The sealant layer is in contact with the gas barrier layer, or the gas barrier layer and the sealant layer are bonded to each other via an adhesive layer.
18. The gas barrier layered product according to claim 16, wherein A layer containing polyamide is provided between the gas barrier layer and the sealant layer.
19. The gas barrier layered product according to any one of claims 1 to 9, which is used for food packaging. 20 . The gas barrier layered product according to claim 10 , which is used for production of retort foods.
21. A packaging bag comprising the gas barrier layered product according to any one of claims 10 to 20.
22. A food packaged with the gas barrier layered product according to any one of claims 10 to 20.
23. A gas barrier layered product comprising a substrate layer, a gas barrier layer provided on at least one surface of the substrate layer, and an inorganic layer provided between the substrate layer and the gas barrier layer, The composition ratio of Zn measured by X-ray photoelectron spectroscopy analysis of the gas barrier layer is 1 to 10 atomic %. In the case where the gas barrier layer is subjected to time-of-flight secondary ion mass spectrometry, 64 ZnPO4H - The mass peak intensity is set as I( 64 ZnPO4H - ) and C3H3O2 - The mass peak intensity is set as I(C3H3O2 - )hour, I( 64 ZnPO4H - ) / I(C3H3O2 - ) is 7×10 -4 Above 5×10 -2 the following.
24. The gas barrier layered product according to claim 23, wherein In the case where the gas barrier layer is subjected to the time-of-flight secondary ion mass spectrometry, PO2 - The mass peak intensity is set as I(PO2 - ) and PO3 - The mass peak intensity is set as I(PO3 - )hour, (I(PO2 - )+I(PO3 - )) / I(C3H3O2 - ) has a value of 0.02 or more and 5 or less.
25. The gas barrier layered product according to claim 23 or 24, wherein The I(PO2 - ) and the I(PO3 - ) intensity ratio, that is, I(PO2 - ) / I(PO3 - ) has a value of 0.05 or more and 1 or less.
26. The gas barrier layered product according to any one of claims 23 to 25, wherein The gas barrier layer is composed of a cured product of a mixture containing at least a polycarboxylic acid, Zn, and a phosphorus compound containing one or more -P-OH groups or a salt thereof.
27. The gas barrier layered product according to claim 26, wherein The concentration of the phosphorus compound containing one or more -P-OH groups or its salt in the mixture is 5×10 -4 mol or more and 0.3 mol or less.
28. The gas barrier layered product according to claim 26 or 27, wherein The polycarboxylic acid includes one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.
29. The gas barrier layered product according to any one of claims 23 to 28, wherein The gas barrier layer has a thickness of 0.05 μm or more and 10 μm or less.
30. A gas barrier layered product comprising: Base material layer, a gas barrier layer provided on at least one surface of the substrate layer, and An inorganic layer disposed between the substrate layer and the gas barrier layer; The gas barrier layer is composed of a cured product of a mixture containing a polycarboxylic acid, a polyamine compound, a polyvalent metal compound, and a phosphorus compound containing one or more -P-OH groups or a salt thereof. 31 . The gas barrier layered product according to claim 30 , further comprising a primer layer provided between the base layer and the inorganic substance layer.
32. The gas barrier layered product according to claim 30 or 31, wherein The inorganic layer is a vapor-deposited film disposed on the substrate layer, or is a vapor-deposited film disposed on the intermediate layer when there is an intermediate layer between the substrate layer and the inorganic layer, and the inorganic layer is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum.
33. The gas barrier layered product according to any one of claims 30 to 32, wherein In the infrared absorption spectrum of the gas barrier layer, 1300cm -1 Above 1490cm -1 The maximum peak height of absorbance in the following range is defined as α, 1690cm -1 Above 1780cm -1 When the maximum peak height of the absorbance in the following range is γ, The ratio of the free carboxyl group to the NH3 complex represented by γ / α is 0.00 or more and 1.00 or less.
34. The gas barrier layered product according to any one of claims 30 to 33, wherein In the infrared absorption spectrum of the gas barrier layer, 1493cm -1 Above 1780cm -1 The total peak area within the following absorption band range is set as A, 1598cm -1 Above 1690cm -1 The total peak area within the following absorption band range is set as B, 1690cm -1 Above 1780cm -1 The total peak area within the following absorption band range is set as C, 1493cm -1 Above 1598cm -1 When the total peak area within the following absorption band range is set as D, The area ratio of the amide bond represented by B / A is 0.200 or more and 0.370 or less, The area ratio of carboxylic acid represented by C / A is 0.150 or less, The area ratio of the carboxylate represented by D / A is 0.580 or more and 0.800 or less.
35. The gas barrier layered product according to any one of claims 30 to 34, wherein The gas barrier layer has a thickness of 0.01 μm to 15 μm.
36. The gas barrier layered product according to any one of claims 30 to 35, wherein The polyvalent metal compound is a compound of one or more divalent or higher metals selected from the group consisting of Zn, Ca, Mg, Ba, and Al.
37. The gas barrier layered product according to any one of claims 30 to 36, wherein (The number of moles of P atoms derived from the phosphorus compound or the salt thereof in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is 0.001 or more and 0.3 or less.
38. The gas barrier layered product according to any one of claims 30 to 37, wherein The phosphorus compound is one or more selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, polyphosphoric acid, phosphonic acid, and salts thereof.
39. The gas barrier layered product according to any one of claims 30 to 38, wherein (The number of moles of the polyvalent metal derived from the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is 0.10 or more and 0.80 or less.
40. The gas barrier layered product according to any one of claims 30 to 39, wherein (The number of moles of the polyvalent metal derived from the polyvalent metal compound in the mixture) / (the number of moles of the amino groups derived from the polyamine compound in the mixture) is 0.25 or more and 0.65 or less.
41. The gas barrier layered product according to any one of claims 30 to 40, wherein The polycarboxylic acid includes one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.
42. The gas barrier layered product according to any one of claims 30 to 41, wherein The polyamine compound comprises polyethyleneimine.
43. The gas barrier layered product according to any one of claims 30 to 42, wherein The base layer includes one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate.
44. A gas barrier layered product comprising: Base material layer, a gas barrier layer provided on at least one surface of the substrate layer, and An inorganic layer disposed between the substrate layer and the gas barrier layer; The gas barrier layer is composed of a cured product of a mixture containing a polycarboxylic acid, a polyamine compound, and a polyvalent metal compound. The gas barrier layered product according to claim 44 , further comprising a primer layer provided between the base layer and the inorganic substance layer.
46. The gas barrier layered product according to claim 44 or 45, wherein The inorganic layer is a vapor-deposited film disposed on the substrate layer, or is a vapor-deposited film disposed on the intermediate layer when there is an intermediate layer between the substrate layer and the inorganic layer, and the inorganic layer is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum.
47. The gas barrier layered product according to any one of claims 44 to 46, wherein The inorganic layer includes an aluminum oxide layer composed of aluminum oxide.
48. The gas barrier layered product according to any one of claims 44 to 47, wherein In the infrared absorption spectrum of the gas barrier layer, 1300cm -1 Above 1490cm -1 The maximum peak height of absorbance in the following range is defined as α, 1690cm -1 Above 1780cm -1 When the maximum peak height of the absorbance in the following range is γ, The ratio of the free carboxyl group to the NH3 complex represented by γ / α is 0.00 or more and 1.00 or less.
49. The gas barrier layered product according to any one of claims 44 to 48, wherein In the infrared absorption spectrum of the gas barrier layer, 1493cm -1 Above 1780cm -1 The total peak area within the following absorption band range is set as A, 1598cm -1 Above 1690cm -1 The total peak area within the following absorption band range is set as B, 1690cm -1 Above 1780cm -1 The total peak area within the following absorption band range is set as C, 1493cm -1 Above 1598cm -1 When the total peak area within the following absorption band range is set as D, The area ratio of the amide bond represented by B / A is 0.200 or more and 0.370 or less, The area ratio of carboxylic acid represented by C / A is 0.150 or less, The area ratio of the carboxylate represented by D / A is 0.580 or more and 0.800 or less.
50. The gas barrier layered product according to any one of claims 44 to 49, wherein The gas barrier layer has a thickness of 0.01 μm to 15 μm.
51. The gas barrier layered product according to any one of claims 44 to 50, wherein The polyvalent metal compound is a compound of one or more divalent or higher metals selected from the group consisting of Zn, Ca, Mg, Ba, and Al.
52. The gas barrier layered product according to any one of claims 44 to 51, wherein (The number of moles of the polyvalent metal derived from the polyvalent metal compound in the mixture) / (the number of moles of -COO- groups derived from the polycarboxylic acid in the mixture) is 0.10 or more and 0.80 or less.
53. The gas barrier layered product according to any one of claims 44 to 52, wherein (The number of moles of the polyvalent metal derived from the polyvalent metal compound in the mixture) / (the number of moles of the amino groups derived from the polyamine compound in the mixture) is 0.25 or more and 0.75 or less.
54. The gas barrier layered product according to any one of claims 44 to 53, wherein The polycarboxylic acid includes one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.
55. The gas barrier layered product according to any one of claims 44 to 54, wherein The polyamine compound comprises polyethyleneimine.
56. The gas barrier layered product according to any one of claims 44 to 55, wherein The substrate layer is a layer including one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate.
Citation Information
Patent Citations
Gas barrier polymer and gas barrier laminate using same
CN113226762A
Exterior material for power storage device, method for manufacturing exterior material for power storage device, and power storage device
CN113348081A
Manufacturing method for gas barrier laminate
JP2018196941A
Gas barrier laminate
JP2022090979A
